Investigation into pore structure regulation and CO2 adsorption mechanisms during PVC synergistic activation of gasification fine slag - Yue Lu; Ying Zhou; Xudong Song; Peng Lv; Jie Xu; Lei Li; Linmin Zhang; Yuchen Shi; Yonghui Bai; Guangsuo Yu; Min Yao (Fuel, 2027)

Effect of magnetic field treatment on the structural and aggregation behavior of gluten, gliadin, and glutenin in potato pulp enriched dough - Jialin Song; Feng Han; Ying Sun; Dongliang Zhang; Shanfeng Chen; Hongjun Li (Innovative Food Science & Emerging Technologies, 2026)

Performance and mechanism investigation of CO2 adsorption materials prepared from rich carbon gasification fine slag and PVC synergy - Ying Zhou; Yue Lu; Mingxuan Yin; Xudong Song; Peng Lv; Qinghua Guo; Lei Li; Linmin Zhang; Yonghui Bai; Guangsuo Yu; Min Yao (Fuel, 2026)

A SASP-related four-gene signature associated with intervertebral disc degeneration: integrated bioinformatics analysis and validation of pinocembrin as a therapeutic candidate - Ge-Liang Yao; Shi-Jiang Wang; Ying Zhang; Jia-Ming Liu; Hong-Hai Song; Zhi-Li Liu (Molecular Biology Reports, 2026)

Genome-wide association study reveals acute mountain sickness susceptibility in Chinese population - Xiangyi Zheng; Wenyu Song; Yuanfeng Li; Nandi Bao; Wenhui Li; Yang Liu; Juanjuan Liu; Bin Li; Xi Yang; Xiaobo Han; Jialin Wu; Liqun Ma; et al. (Molecular Genetics and Genomics, 2026)

Long-term organic fertilization fosters modular microbial networks: A global analysis of soil bacteriome responses - Shu-Le Li; Cai Chen; Xiang-Yu Dai; Hai-Song Yan; Yao-Yang Xu; Meili Feng; Jun He; Jianfeng Ren; Wan-Ying Xie; Fang-Jie Zhao (Soil Ecology Letters, 2026)

Rosmarinic acid ameliorates radiation-induced intestinal injury through PI3K/AKT/NF-κB/MMP9 axis inhibition: From network pharmacology prediction to experimental validation - Xiaoxue Li; Jing Zhang; Yutong Dong; Zheng Zhou; Beier Jiang; Tianjiao Min; Bin Song; Gang Jin; Li Ma; Bolin Li; Luyao Yu; Ying He (Tissue and Cell, 2026)

Insulin-like peptide 3 facilitates sheep oocytes in vitro maturation and subsequent early embryo development - Qi Yang; Rui-Feng Zhang; Zhao-Yu Jiang; Dui Sun; Rui-Hao Tang; Xiao-Yi Zhang; Yi-Tong Li; Wen-Ying Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Theriogenology, 2026)

Soil degradation impacts on root water uptake and yield of soybean in the black soil region - Zhijie Li; Zhuohang Jin; Ying Song; Jinxia Fu; Xiaoling He; Fenli Zheng; Wenxiu Zou; Zhi Li (Soil and Tillage Research, 2026)

High-speed air circulation preserves curcumin bioactivity and enables pH-dependent intestinal release in oyster-based functional foods for IBD dietary intervention - Shuang Gao; Xue Jiang; Yi Rong; Huanhuan Chi; Ci Song; Shujia Wang; Ying Li; Jingjing Chen; Lida Yang; Huawei Ma (Food Research International, 2026)

An ultrasound-responsive piezoelectric nanoplatform for enhanced pancreatic cancer immunotherapy via lactate metabolism remodeling and dendritic cell activation - Zoujuan Cai; Haonan Wang; Xinxin Xie; Yan Wang; Tianjiao Zhang; Ruiqi Wu; Shuyu Xu; Yunli Xu; Yang Song; Zhiguang Chen; Sinong Li; Ying Zhang; et al. (Chemical Engineering Journal, 2026)

Integrated implementation of conservation agriculture enhances crop yield and sustains multiple ecosystem services in the black soil regions - Ying Song; Zhijie Li; Jiahui Ha; Xiaoling He; Jinxia Fu; Fenli Zheng; Zhi Li (Agriculture, Ecosystems & Environment, 2026)

Integrated transcriptomic and metabolomic analyses reveal the involvement of AtGASA1 and AtGASA4 in salicylic acid pathway-associated immune responses in Arabidopsis - Jian-Bo Song; Ya-Ru Li; Zi-Xin Zhao; Xian-Zhi Zuo; Cai-Feng Wang; Min Huang; Shu-Fan Liu; Yu-Fan Chen; Wen-Qian Song; Lin Wang; Ying-Juan Wang; Xuan Huang (Plant Science, 2026)

Multi-scale evolutionary forces shape the phylogeography of an Old World disjunct plant genus Girardinia (Urticaceae) - Zhi-Peng Li; Hai-Ling Qi; Fu-lv Liu; Ying Zhao; Alexandre K. Monro; Abdullah; Xiao-Yu Song; Yue-Hua Wang; Zeng-Yuan Wu; Jie Liu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Integrative taxonomic revision of Uropsilus (Uropsilinae, Talpidae) combining genomic, morphological and geographic evidence - Yi-Xian Li; Quan Li; Wen-Yu Song; Xue-You Li; Kenneth Otieno Onditi; Xiao-Xin Pei; Hong-Jiao Wang; Chang-Kun Fu; Shao-Ying Liu; Zhong-Zheng Chen; Xue-Long Jiang (Molecular Phylogenetics and Evolution, 2026)

Bio-inspired, recycled and durable construction of superhydrophobic/oleophilic and flame-retardant cotton fabrics with excellent oil/water separation ability based on calcium alginate - Xinmeng Lv; Ying Song; Haidi Li; Mengru Zhang; Xinqiang Wu; Zaihang Zheng; Yan Liu; Yunke Qu (Journal of Environmental Chemical Engineering, 2026)

Liupao tea alleviates high-fat diet-induced obesity by re-establishing metabolic homeostasis of short-chain fatty acids and chenodeoxycholic acid - Yuru Tan; Xuancheng Wang; Anlong Song; Song Xu; Xueting Lin; Bao Yang; Jichu Luo; Ying Tong; Mingsen Wen; Xuan Guan; Peiting Li; Zhe Luo; et al. (Food Research International, 2026)

Mechanistic insights into the structural and functional changes of myofibrillar proteins from bighead carp (Hypophthalmichthys nobilis) induced by high hydrostatic pressure combined with liquid immersion freezing - Tao Song; Yuyang Zhang; Xinxin Li; Yuxiao Mao; Sinan Zhang; Lihui Hu; Ying Liu; Hosahalli S. Ramaswamy; Yong Yu (Food Research International, 2026)

Enhancing grass carp surimi gel mechanical properties via a high-pressure-assisted double-network strategy - Sinan Zhang; Xinxin Li; Tao Song; Yuyang Zhang; Yuxiao Mao; Ying Liu; Linjiang Pang; Hosahalli S. Ramaswamy; Yong Yu (Food Research International, 2026)

From black box to transparency: Explainable artificial intelligence driven origin identification of Xinjiang Nilka black bee honey - Xiao-Hui Sun; Lin-Hua Shi; Xiang-Shuai Li; Xiu-Ying Tang; Hong-Song Ren; Sheng-Hong Liu (Food Chemistry, 2026)

A fully biomass-derived intrinsically flame-retardant phenolic resin: Robust adhesion, fire-safe coatings, and closed-loop upcycling for multifunctional cellulose fibers - Wei Tan; Lei Tan; Yin Tian; Ying Chang; Guixiang Song; Lu Bai; Ping Li; Yuanlin Ren; Xiaohui Liu (Chemical Engineering Journal, 2026)

Waste akebiae trifoliata-derived WO3 hierarchical tubes efficient detection of ppb-level triethylamine gas at low temperature and application in food freshness detection - Wen-Xiao Li; Jia-Wang Wang; Rui-Long Li; Qiu-Yue Zheng; Bao-Yu Song; Bo-Ya Liu; Li-Xia Zhao; Ying Fu; Ying-Ming Xu (Chemical Engineering Journal, 2026)

High-performance blue hyperfluorescence OLEDs with precise spatial control of the sensitizing layer in hetero-phase emissive layer for exciton dynamics optimization - Kunpeng Song; Haichang Wang; Chen Zhang; Zirun Zhao; Xiaowei Li; Ying Xu; Bo Qiao; Dandan Song; Ling Fan; Suling Zhao (Chemical Engineering Journal, 2026)

Hyaluronic acid-based core-shell microneedles for staged local delivery of psoralen toward anti-inflammatory and cartilage-protective therapy of rheumatoid arthritis - Qihui Lin; Zijian Yan; Qiangyu Chen; Yongan Lin; Dan Ying; Zhuhao Tan; Zheng Liu; Mengxing Lu; Wenjing Song; Li Ren (Carbohydrate Polymers, 2026)

Regenerated cellulose fibers functionalized with lignin-derived boron-containing phenolic networks for durable flame retardancy and UV protection - Wei Tan; Jieyun Zhao; Lei Tan; Yin Tian; Guixiang Song; Ying Chang; Lu Bai; Ping Li; Yuanlin Ren; Xiaohui Liu (Carbohydrate Polymers, 2026)

Chemical constituents from the leaves of Yulania denudata and their chemotaxonomic significance - Zhen-Quan Li; Qiu-Ye Zhao; Hui-Ling Zhou; Shi-Huan Yin; Xuan Jiang; Xin-Ying Wang; Lu Sai; Lin-Fen Ding; Liu-Dong Song (Biochemical Systematics and Ecology, 2026)

An integrated experimental and computational study on a COX-2-targeted AIE probe for precise cancer cell imaging via restriction of intramolecular rotation - Jianxi Liu; Shengfa Song; Yonglin Zhang; Jiale Hu; Shulin Chen; Lulu Zhu; Li Shen; Zhen Sun; Ying Xue; Hao Jiang; Wei Ji; Jinmei Sun; et al. (Analytica Chimica Acta, 2026)

Microbial succession and metabolic mechanisms driving flavor evolution in Northeast Chinese dajiang: a comprehensive review integrating insights from East Asian fermented soybean pastes - Wanying Song; Mohan Li; Xiaoxuan Yue; Ying Meng; Yuanfang Xie; Yuge Zhang; Yutong Hu; Yan Zheng; Xiqing Yue (Critical Reviews in Food Science and Nutrition, 2026)

Under greenhouse settings, mycorrhizal responsive herbs establish better in their own soil compared to less responsive counterparts - Stavros D. Veresoglou; Yang Liu; Jie Bai; Hanzhi Bao; Peipei Bao; Bolun Cai; Liqun Cai; Jiawei Cao; Chen Chen; Genrun Chen; Hongqiao Chen; Jiarong Chen; et al. (Plant and Soil, 2026)

Membrane-regulated seawater electrolysis for sustainable hydrogen production - Zhongting Liu; Jingfen Yuan; Sunpeng Shan; Guangpu Li; Song Gu; Cheng Chen; Wei Yu; Mingzhu Zhou; Saleem Raza; Ying Liu; Hongjun Lin; Yang Jiao; et al. (Water Research, 2026)

YgeP, a global regulator within the ETT2 pathogenicity island, coordinates motility-biofilm balance and negatively controls serum resistance in avian pathogenic Escherichia coli - Weiyang Su; Zhe Li; Siqi Feng; Zhaorong Yu; Shumei Li; Huiqi Lu; Xiangjun Song; Jian Tu; Zhao Qi; Ying Shao (Veterinary Microbiology, 2026)

SIRT7-mediated H3K79 desuccinylation modulates functional activities of goat ovarian granulosa cells - Yawen Li; Lei Wang; Shuaifei Song; Qiuyan Li; Ying Gong; Zihan Wang; Shiyi Yao; Zihan Ma; Yingping Xia; Cong Zhou; Xinyang Yao; Jia Luo; et al. (Theriogenology, 2026)

Flood sedimentary records and hydroclimatic drivers during the late mid-Holocene in central North China Plain - Xiangyue Kong; Xiaochen Xing; Qinmian Xu; Hongyu Song; Ying Wang; Yunfei Yang; Shiyao Chai; Xiaotian Zhang; Guoqiang Ding; Wensheng Zhang; Baoshuo Fan; Zhen Zhang; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Adaptive strategies of a model diatom Phaeodactylum tricornutum under atrazine exposure - Yunsheng Wang; Ying Chen; Zhengmao Li; Chen Gao; Xiangyang Jiang; Weiyun Wang; Fang Liu; Xiukai Song; Liqiang Yang (Journal of Hazardous Materials, 2026)

Metabolic alterations bridge exposure to urinary halogenated phenols and bisphenols to dyslipidemia: Evidence from an e-waste recycling area - Meng-Yang Li; Hong-Xuan Kuang; Tian-Hong Chen; Xiu-Fei Wang; Yin-Fei Song; Ming-Deng Xiang; Ying-Xin Yu; Yun-Jiang Yu (Environmental Pollution, 2026)

Regulation of quorum sensing for antibiotic resistance genes in freshwater plastisphere - Lijia Lu; Ying Li; Zhuoran Duan; Si Li; Ruiping Song; Jing Gao; Dayi Zhang; Jie Wang (Chemical Engineering Journal, 2026)

Charge-programmable carbon dots tailored by amino acid pKa spectrum for spatiotemporally controlled siRNA delivery and antiviral protection in plants - Fang Wang; Xueyang Ji; Yan Zhao; Jingyan Hu; Ziqi Zhang; Jinxuan Wang; Kailin Su; Jingyan Jia; Ao Zhou; Ning Li; Ying Song; Changjun Zhang; et al. (Chemical Engineering Journal, 2026)

Paternal intergenerational thyroid disruption in zebrafish induced by environmental prednisone exposure - Qianlin Cai; Xing Hu; Junhao Wu; Meixin Ye; Jinlin Yang; Ying Li; Xinyi Song; Yilin Huang; Jiahui Weng; Xiaoqing Xue; Lina Xie; Yuerong Zeng; et al. (Aquatic Toxicology, 2026)

Kit Ligand enhances in vitro oocyte maturation and early embryonic development in sheep - Qi Yang; Dui Sun; Zhao-Yu Jiang; Rui-Hao Tang; Rui-Feng Zhang; Xiao-Yi Zhang; Wen-Ying Li; Yi-Tong Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Animal Reproduction Science, 2026)

Effects of Low-intensity Crop Residue Burning on Soil Ecology, Yield, and Quality in Morchella Cultivation - Zihan Gao; Yixin Li; Jinyan Liu; Ying Ye; Wei Yin; Le Wang; Youming Qiao; Qian Song; Jian Liang (Journal of Soil Science and Plant Nutrition, 2026)

Corrigendum to “YgeP, a global regulator within the ETT2 pathogenicity island, coordinates motility-biofilm balance and negatively controls serum resistance in avian pathogenic Escherichia coli” [Vet. Microbiol. 320 (2026), 111147] - Weiyang Su; Zhe Li; Siqi Feng; Zhaorong Yu; Shumei Li; Huiqi Lu; Xiangjun Song; Jian Tu; Zhao Qi; Ying Shao (Veterinary Microbiology, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Climatic variability characteristics of the western coast of the Bohai Bay during the early-middle Holocene - Ran Zhang; Hanfei You; Ying Wang; Xiuyun Sun; Bing Li; Yawen Ge; Zhen Zhang; Hongyu Song; Yuecong Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Red mud valorization: From waste management to metal resource recovery in the circular economy - Tingting Song; Yifan Gu; Ying Wang; Fengting Li (Journal of Environmental Management, 2026)

Petrology and geochemistry of monzogranite and porphyritic granite in Laowan ore field of Qinling orogenic belt, China: Implications for gold and molybdenum mineralization - Ying-nan Chen; Cheng Xu; Wen-lei Song; Wei Fu; Ze-bang Yi; Zhi-xuan Han; Chengyu Zou; Jian-li Chen (Journal of Asian Earth Sciences, 2026)

Rapid determination of diesel density using near-infrared and mid-infrared spectroscopy data fusion modelling - Chaomin Ding; Ying Kan; Anni Liu; Xiaoyan Guo; Zhengdong Zhang; Junting Tong; Ke Li; Fan Liu; Xiaoping Song; Yong Yan; Qi Li; Tao Hong (Fuel, 2026)

Buffer-free BOZn coordination sites enable efficient Fe(VI) oxidation for organic pollutant removal - Xin-Jia Chen; Yu-Kun Huang; Ning Li; Pi-Jun Duan; Chang-Wei Bai; Zhi-Quan Zhang; Jing Wang; Ying Shao; Xiao-Wei Xu; Jin-Song Guo; Fei Chen (Chemical Engineering Journal, 2026)

Starch coating on low-sodium salt via fluidized bed granulation: Sensory improvement and health benefits - Xinyu Song; Xing Li; Xiangyu Liu; Zhaoxiang Ma; Zhi Fan; Zhiqiang Cui; Hui Xiong; Zhixin Li; Ying Zhou; Mingchun Lv; Yuan Li (Carbohydrate Polymers, 2026)

Advances in Alzheimer’s disease: mechanistic insights and therapeutic targets - Yu-Juan Jia; Yi-Jun Ge; Bowei Li; Ying Yang; Huaqiu Chen; Jie Liu; Jun-Hong Guo; Jin-Tai Yu; Ke-Qiang Ye; Jian-Zhi Wang; Weihong Song; Yan-Jiang Wang (Science China Life Sciences, 2026)

MECP2T203M mutation disrupts neurogenesis in human cerebral organoids by altering chromatin dynamics and transcriptional regulation - Zhihong Song; Qian Zhu; Rui Yang; Huihui Jiang; Ying Li; Liping Chen; Ting Wang; Yan Wu; Yan Liu; Haitao Wu (Science China Life Sciences, 2026)

Genome-wide analyses of the Nodulin-like gene family in sorghum - Shuhan Feng; Yaru Yu; Qian Wu; Xuanru Shi; Mengyao Song; Haojie Zhang; Mingjie Qi; Haoqi Lv; Kangqi Du; Huilin Zhang; Ying Li; Xiaolin Song; et al. (Genetic Resources and Crop Evolution, 2026)

Cross-species comparative transcriptomic analysis of spermatozoa reveals species-specific regulatory networks linked to fertilization-associated genes in cattle, sheep and goats - Yue Zhao; Linfeng Bai; Qiqi Jiang; Hao Xiao; Fangyuan Liu; Bilige Wuyun; Rihan Wu; Chunxia Hao; Rui Ding; Peng Yuan; Lizhi Wang; Ying Lu; et al. (Science China Life Sciences, 2026)

Cytotoxic properties of pentacyclic triterpenes isolated from the flowers of Rhododendron pachypodum - Jie Luan; Yang Liu; Yu Zhang; Ying Wang; Qin Song; Bing Chen; Gaohong Zhang; Jiangbo He; Xian Li (Natural Product Research, 2026)

Transcriptomic profiling reveals transcriptomic remodeling linked to inflammatory activation and cell cycle-related gene expression in the early hours of macrophage activation - Ding Li; Qinsong Ye; Tiantian Liu; Diqi Ying; Song Ye; Jishan Zheng; Zhiqiang Sun (Molecular and Cellular Biochemistry, 2026)

Spatiotemporal variation in soil available potassium in Central-Western China - Xiaoyan Li; Xiaodong Song; Chengchao Yang; Ying Xiao; Yunpeng Hong; Shuming Ding; Xudong Wang; Jiaojiao Lei (Environmental Monitoring and Assessment, 2026)

Two new monoterpene glycosides from the endophytic fungus Diaporthe nobilis and their cytotoxic effects - Ying Chen; Jian Wang; Cai-Lin Zhao; Xiu-Feng Yang; Jin Ye; Lin-Ping Zhang; Yun-Xiao Li; Fan-Wei Liu; Le Zhang; Bo Song (Natural Product Research, 2026)

Identification and knockout of SlHDZIV14 reveals fruit trichome-associated control of postharvest water loss in tomato - Ying Fu; Meng Li; Li Huang; Iben Sørensen; Xueting Liu; Chenhuan Fei; Wenran Song; Sen Zhang; Wei Zhang; Kexuan Tang; Jocelyn K.C. Rose; Qian Shen (Postharvest Biology and Technology, 2026)

Benzene-induced myelosuppression confers a survival advantage to hematopoietic progenitors: Single-cell analysis of malignant transformation dynamics in a murine model - Jin Zhou; Pinpin Sui; Ying Li; Jinxu He; Yedan Lu; Min Zheng; Xiangrong Song; Tao Yu; Xiurong Cheng; Caihong Xing (Journal of Hazardous Materials, 2026)

Facile fabrication of PTFE/PET composite membrane with reinforced hydrophilic and antifouling properties for sustainable decentralized water system purification - Ludi Song; Yujie Fang; Xin Chen; Ziyuan Zhou; Liping Chen; Jun Yang; Ying Li; Yaqin Wu; Haitao Zhu; Lin Zhang; Congjie Gao (Journal of Environmental Management, 2026)

Lactiplantibacillus plantarum 5.1 attenuates ovarian fibrosis by modulating the gut microbiota and ovarian metabolism in a rat model of letrozole-induced polycystic ovary syndrome (PCOS) - Qiu-Ping Huang; Li-Ying Huang; Gui-Lian Liao; Chun-Xiang Huang; Ke-Ying Wang; Jie-Jing Xu; Hao-Ran Sun; Tie-Min Jiang; Jia-Le Song (Food Bioscience, 2026)

Lignin degradation enhancement in poultry manure and maize residue composting via flax retting waste liquid and biochar: Dominant microbial generalist species mediated - Tong Yang; Xiujun Tu; Xuan Tang; Yuhao Guo; Yueyi Liu; Zhenchao Wu; Hao Zhang; Ying Yang; Shuo Li; Weige Yao; Jinyu Du; Tingting Xu; et al. (Food and Bioproducts Processing, 2026)

Comprehensive phylogenomic analyses of ciliated protists with a revised classification of the phylum Ciliophora (Eukaryota, Alveolata) - Yurui Wang; Ying Yan; Zhenzhen Yi; Yan Zhao; Qianqian Zhang; Yong Chi; Tengyue Zhang; Weiwei Liu; Mingjian Liu; Borong Lu; Mingzhen Ma; Wenbao Zhuang; et al. (Science China Life Sciences, 2026)

Overexpression of β-carotene hydroxylase gene (CiBCH) enhances salt stress tolerance in Arabidopsis thaliana - Ying Sun; Ying Song; Shuaitong Zang; Ruiqing Zhang; Hongyao Li; Qiang Li; Liran Yue; Changle Liu; Miao He (Physiology and Molecular Biology of Plants, 2026)

Molecular characterization of a novel partitivirus isolated from Fusarium solani, the causal agent of tobacco root rot - Xiao Wu; Ying Wang; Rui Guo; Ya Rong Wang; Si Jun Li; Xiang Ping Zhou; Jie Zhong; Yan Song Xiao; Tian Bo Liu (Archives of Virology, 2026)

A hybrid sparse-semantic image classification framework to support marine and coastal monitoring and management - Ying Shi; Lan Song; Luocheng Wu; Huanhuan Li (Ocean & Coastal Management, 2026)

Thermal stress drives coastal microbiome transitions from phototrophic carbon fixation to energy-conserving chemotrophy - Lijuan Ren; Ying Zhu; Haiming Chen; Dan He; Biao Li; Xingyu Song; Yang Yang; Qinglong L. Wu (Water Research, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Alstoyunnanines A and B, two new monoterpenoid indole alkaloids from the leaves and twigs of Alstonia yunnanensis - Yan-Song Li; Zhe Liu; Ying Xu; Xiang-Zhong Huang; Lei Fang (Phytochemistry Letters, 2026)

Numerical investigation on wave-induced roll motion of a floating barge in front of a vertical wall - Shu Li; Heng Jin; Lei Song; Jianye Yang; Guogang Ying (Ocean Engineering, 2026)

In situ reduction and recovery of Rh(III) from low-concentration solutions using iron-electrocoagulation flocs - Guofu Dai; Chao Peng; Chen Wang; Ying Cui; Song Wen; Jie Jiang; Chenlong Duan; Peng Li (Minerals Engineering, 2026)

High-rate partial nitritation of high ammonia permeate from anaerobic membrane reactor treating food waste: Kinetics, enriched Nitrosomonas and enhanced tolerance to free ammonia and free nitrous acid - Ying Song; Wenzhao Zhao; Shen Cui; Qian Li; Yu Qin; Yuanfan Zhang; Meizhen Wang; Yu-You Li (Journal of Water Process Engineering, 2026)

Reservoir operations for drought mitigation with dynamic hedging policy activated by drought limited water level and hedging coefficient intervals - Yan Kang; Haoyue Zhang; Ying Gao; Xinyu Zhao; Songbai Song; Lingjie Li (Journal of Hydrology, 2026)

All in one: Dual-mode probe for multivariate sensing heavy metal ions and cascade detecting biomarkers - Wei Tang; Ying Song; Siqi Chen; Yuxuan Lv; Yanfei Li; Changhong Guo; Fang Chai (Journal of Hazardous Materials, 2026)

Contrasting but complementary: divergent impacts of no-till and deep tillage on soil health in black soil regions globally - Ying Song; Zhijie Li; Jinxia Fu; Fenli Zheng; Yakov Kuzyakov; Zhi Li (Journal of Cleaner Production, 2026)

Unraveling molecular interactions in coal-derived phenolic–aromatic systems: A decoupling principle governing assembly - Lan Yi; Dandan Luo; Miaomiao Feng; Li Guo; Hongming Fang; Yuncai Song; Yi Huang; Xiaoqin Wu; Wen-Ying Li (Fuel, 2026)

Predictive Multi-Physics coupling coal combustion model under rapid heating - Hanjian Li; Ying Zhao; Shichen Ding; Xiaoxuan Lyu; Yi Wang; Sheng Su; Song Hu; Jun Xiang; Qingsong Mu; Yanfei Li; Xian Fan; Huanying Chi (Fuel, 2026)

Environmental heat and cold stress, thyrotropin abnormalities, and reduced fecundability in 14 million Chinese couples: A nationwide preconception cohort study - Xinghou He; Mengyao Li; Ying Yang; Xinyi Lv; Hongbing Xu; Bin Zhang; Long Wang; Chuanyu Zhao; Jiahui Liu; Yuan He; Jianbing Wu; Xinghua He; et al. (Environmental Research, 2026)

Template-free synthesis of nitrogen-doped hierarchically porous carbon nanospheres for superior sodium-ion storage - Kun Liu; Caicheng Song; Yunqi Gong; Huiyang Li; Yingxin Hu; Yihang Guo; Ying Liu; Li Liu; Yongyi Song; Decai Guo; Jia-ao Wang (Chemical Engineering Journal, 2026)

Bifunctional engineered carbon felts with high electrocatalytic activity and carbon defects for vanadium flow batteries - Qi-an Zhang; Yuanfang Song; Tao Gao; Ying Li; Wenjiao Ji; Ao Tang (Chemical Engineering Journal, 2026)

Multifunctional interface engineering enables high efficiency of semi-transparent CsPbBr3 solar cells - Ankang Shu; Mingming Li; Jiawei Song; Zhengyang Li; Qian Wang; Shangwei Huang; Jiahao Cheng; Wenjian Shen; Cong Geng; Rui Chen; Guijie Liang; Jun Yao; et al. (Chemical Engineering Journal, 2026)

Efficacy and Safety of Intravenous Thrombolysis with Tenecteplase in Patients with Wake-Up Branch Atheromatous Disease - Lili Zhu; Ying Zhang; Jiarong Li; Liang Song; Haoran Li; Yang Yang; Lijuan Liu; Shaolei Zhang; Xiaofei Gao; Weifeng Chen; Guo Rui; Haiqiang Qin; et al. (Translational Stroke Research, 2026)
Branch atheromatous disease (BAD), a subtype of acute ischemic stroke (AIS), is associated with a high risk of early neurological deterioration (END) and poor prognosis. Wake-up stroke (WUS), comprising 20%–30% of AIS cases, is typically excluded from thrombolysis because of unknown onset time. Using diffusion-weighted imaging/fluid-attenuated inversion recovery (DWI/FLAIR) mismatch, we evaluated the efficacy and safety of Tenecteplase (TNK) thrombolysis in patients with BAD-related WUS. We retrospectively recruited 1,062 patients from seven Zhengzhou hospitals between January 2021 and June 2025. The patients received either TNK (n = 338) or dual antiplatelet therapy (n = 724). Propensity score matching (PSM; 1:1, caliper 0.02) yielded 292 matched pairs. Early neurological changes were evaluated using the National Institutes of Health Stroke Scale (NIHSS), and 90-day outcomes were evaluated using the modified Rankin Scale (mRS). After PSM, TNK significantly reduced the risk of END (odds ratio [OR] = 0.425, 95% confidence interval [CI]: 0.262–0.689; P < 0.001). Patients treated with TNK were more likely to achieve good functional outcomes (modified Rankin Scale [mRS] 0–1 and 0–2) with fewer poor outcomes (mRS ≥ 4). There were no significant differences in symptomatic intracranial hemorrhage, other bleeding events, or mortality among the groups. DWI/FLAIR mismatch-guided TNK thrombolysis appears to overcome the limitations of an unknown onset time in WUS and may counteract the progressive pathophysiology of BAD. TNK intravenous thrombolysis may be a safe and effective treatment for patients with wake-up BAD and DWI/FLAIR mismatches.

Regulatory patterns and driving factors of soil aggregates on the environmental behavior of heavy metals: A global study based on meta-analysis and machine learning - Yu-Xuan Song; Yuhan Meng; Bingxuan Zhao; Tian-Hao Che; Zining Li; Zuozhou Yu; Xinyang Zhen; Yining Li; Chengyong Li; Quan-Ying Wang; Jing-Ya Zhou (Environmental Geochemistry and Health, 2026)

Sex-specific responses of intestinal health, microbiota composition, and transcriptome profiles in golden pompano (Trachinotus blochii) subjected to hypoxia and reoxygenation - Xiao Kun Wang; Shan Ying Han; Ze Xin Zhong; Zeng Tan Hu; Tian Xiu Li; Yue Gu; Chun Xiu Jin; Tian Jiang; Fei Biao Song; Jian Luo; Jun Long Sun (Frontiers in Marine Science, 2026)
Introduction Driven by global climate change and coastal eutrophication, severe hypoxic events have become a primary environmental stressor in marine ecosystems, posing a critical threat to commercially vital teleosts like the golden pompano ( Trachinotus blochii ). Understanding the dimorphic physiological and microbial responses between sexes under such stress is crucial for developing targeted mitigation strategies. Methods Golden pompano were subjected to hypoxia stress (3.0 ± 0.2 mg/L) for 14 days, followed by restoration of dissolved oxygen to normoxic state (7.0 ± 0.2 mg/L) and cultivation for another 14 days. Subsequently, the histology ( n = 3), digestive enzyme activity ( n = 9), microbial composition ( n = 3), and transcriptome ( n = 3) of intestinal tissue were evaluated. Results Hypoxia induces marked physiological stress and a shift toward intestinal dysbiosis across both genders, manifested by damaged intestinal integrity, oxidative stress, and an increased abundance of opportunistic pathogens (e.g., Spirochaetes ). Although reoxygenation further deteriorates the histological condition of female intestinal tissue, it also triggers more significant molecular and enzyme activity rebound effects compared to males. Moreover, females exhibit significant upregulation of lipid metabolism, antioxidant defense mechanisms, and key signaling pathways, suggesting that they may have adopted a high-energy “compensatory recovery” strategy. Correlation analyses reveal that these microbial shifts are closely linked to host metabolic regulation: beneficial bacteria ( Pseudoalteromonas and Lactococcus ) support sterol transport and signaling homeostasis, while opportunistic taxa ( Brevinema ) negatively impact lipid synthesis. Discussion Our findings reveal a distinct gender dimorphism in the hypoxia and reoxygenation response, providing a theoretical foundation for sex-specific management and nutritional interventions in golden pompano aquaculture.

Gallic acid-mediated semiquinone radicals drive a self-sustaining fenton-like system for PAH remediation in contaminated soil - Ying-Ying Wu; Xiao-Hong Ma; Song Yang; Li-Bang Ma; Fu-Zheng Zhao; Jing Sun (Journal of Hazardous Materials, 2026)

Moisture and interspecies interactions shape microbial communities and metabolites to define the sensory profile of fermented sausages - Di Zhang; Ruren Li; Liangyan Rong; Ying Xu; Futong Song; Nan Zhang; Ting Sun; Guoliang Li (Food Chemistry, 2026)

Adaptive polynomial combination optimization multidimensional Taylor network for fault diagnosis of HVAC AHU systems - Ying Yan; Huaixi Fan; Jun Cai; Zhihan Li; Edmond Qi Wu; Qiming Sun; Shuai Wu; Aiguo Song (Energy and Buildings, 2026)

High-voltage-tolerant zirconium-organic nanosheet separator enabling 5 V LiNi0.5Mn1.5O4|Li batteries with enhanced capacity density - Jian-Qiang Shen; Ya-Nan Gao; Ying-Li Song; Lingjuan Zhang; Gen Chen; Guoqiang Tan; Yunfeng Lu; Xian-Ming Zhang (Chemical Engineering Journal, 2026)

A novel dual-function biosensor based on polarity reversal of MFC for bioelectricity generation and detecting trimethylamine-N-oxide - Sheng-chao Gao; Yu-xuan Wang; Yong-dong Li; Ru-meng Zhang; Ya-nan Zhang; Jin-song Dong; Hong-xia Ni; Yi Chen; Xi-hui Shen; Ying Liu (Chemical Engineering Journal, 2026)

Light-at-night exposure drives myopia via melanopsin signalling - Jiaxin Li; Congying Li; Meijun Wang; Jianjun Meng; Jiajia Dang; Ying Huang; Di Shi; Xinyu Li; Shan Cai; Tianli Peng; Yunfei Liu; Yuting Kang; et al. (Science China Life Sciences, 2026)

Coordinating metabolic reprogramming and exosome secretion: A dual role for SIRT1/HIF-1α under hypoxia in golden pompano - Yue Chen; Shan Ying Han; Ze Xin Zhong; Chun Xiu Jin; Geng Hui Fang; Li Xiao Zhou; Fei Biao Song; Jian Luo; Jun Long Sun (Aquaculture, 2026)

Biodegradable microplastics-induced free-living nitrogen fixation enhancement and diazotrophic community differentiation in soils - Yujuan Han; Peixin Gao; Jiping Song; Yanning Li; Xiao Wang; Ning Yang; Xu Zhao; Bo Liu; Chuankun Zhang; Ran Li; Dan Wen; Ying Teng (Journal of Environmental Management, 2026)

Biopolymer-based edible film incorporating Melaleuca Bracteata F. Muell. Essential oil with antimicrobial and antioxidant properties: A promising approach for strawberry fruit preservation - Jinjie Yang; Yaqian Niu; Penghui Hu; Yunqing Song; Ruihan Dang; Linke Li; Yuke Zhang; Yanshu Gong; Yixuan Lin; Ying Xin (Food Research International, 2026)

Formation of advanced glycation end-products in powdered infant formula: A systematic investigation of macronutrient composition, interactions, and processing methods - Xiaoxiao Wei; Lulu Zhu; Zixiong Song; Ying Jing; Haizhen Li; Jianhua Xie; Mingyue Shen (Food Chemistry, 2026)

Interfacial assembly behavior of temperature-controlled surface-activated fat crystals at oil/water interfaces: characterization, interfacial dynamics, and emulsion-stabilizing capabilities - Yuting Song; Xia Zhang; Shuang Su; Ying Song; Bing Li; Lin Li (Food Hydrocolloids, 2026)

Crop yield–soil quality trade-offs under no-tillage and deep tillage in the black soil region of Northeast China - Ying Song; Xiaoling He; Jinxia Fu; Fenli Zheng; Zhi Li (Field Crops Research, 2026)

New early cretaceous paleomagnetic results from the Northern Lhasa Terrane and their tectonic implications - Zijian Li; Yalin Li; Xiaodong Tan; Zhongpeng Han; Shuai Li; Xingduo Ma; Ying Liang; Xu Zhang; Jizheng Song; Zihao Zhou; Yuanxiang Li; Shuqing Miao; et al. (Earth and Planetary Science Letters, 2026)

Synergistic inspiration of in situ growth technology and biomass phytic acid for designing durable flame retardant and antibacterial cellulose fibers - Yin Tian; Wei Tan; Lu Bai; Lei Tan; Ying Chang; Guixiang Song; Ping Li; Yuanlin Ren; Xiaohui Liu (Carbohydrate Polymers, 2026)

Dynamic vegetation responses to climate change and human activities in the eastern North China region over the past 3,500 years: Pollen record from the Caofeidian Wetland - Shiyao Chai; Ying Wang; Rongrong Wang; Hongyu Song; Ran Zhang; Xiangyue Kong; Yunfei Yang; Yawen Ge; Bing Li; Yuecong Li (CATENA, 2026)

Characterization of novel Vibrio parahaemolyticus JD2305 and comparative genomics of the Tc toxin mobilome in Vibrio pathogens associated with translucent postlarvae disease - Laizhuang Jin; Na Ying; Qianhui Song; Liguo Yang; Letian Li; Lei Feng; Hui Zhang; Mao Lin; Xinshu Li; Wenhong Fang (Aquaculture, 2026)

Corrigendum to “Superior reduction and immobilization of Cr(VI) in soil utilizing sulfide nanoscale zero-valent iron supported by phosphoric acid-modified biochar: Efficiency and mechanism investigation” [Sci. Total Environ. 907, (2024), 168133] - Kaige Li; Haijiao Song; Fuxuan Bi; Yuhui Li; Zhao Jiang; Yue Tao; Jianhua Qu; Ying Zhang (Science of The Total Environment, 2026)

Late Holocene temperature changes in eastern North China reconstructed from branched glycerol dialkyl glycerol tetraethers (brGDGTs) - Hongyu Song; Ying Wang; Huaying Wang; Can-Ge Li; Yuecong Li; Bing Li; Yawen Ge; Rongrong Wang; Xiuyun Sun; Ran Zhang; Hanfei You; Changhong Liu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Effect of CO2 and H2O on pyrolysis characteristics and structural evolution of Zhundong coal under rapid heating rate - Huanying Chi; Shichen Ding; Ying Zhao; Xiaoxuan Lyu; Yi Wang; Sheng Su; Song Hu; Jun Xiang; Qingsong Mu; Yanfei Li; Xian Fan; Hanjian Li (Fuel, 2026)

A molecular-level insight into the synergistic separation of acidic and basic heteroatoms from coal tar: A strategy for fuel upgrading - Dandan Luo; Lan Yi; Jialing Chen; Hao Luo; Yuncai Song; Yi Huang; Xiaoqin Wu; Wen-Ying Li (Fuel, 2026)

Alterations in cardiovascular biomarkers and gut microbiome associated with night shift work: Insights from the Chinese platform workers study - Tenglong Yan; Li Rong; Siyuan Wang; Xin Song; Binshuo Hu; Zhihui Wang; Xiaoshun Wang; Xiaowen Ding; Rui Guan; Hong Yu; Dongsheng Niu; Ying Zhang (Environmental Research, 2026)

Unraveling the regional dynamics of straw mulching and incorporation on crop yields in Northeast China - Ying Song; Zhijie Li; Xiaoling He; Jiaqiong Zhang; Jinxia Fu; Fenli Zheng; Zhi Li (European Journal of Agronomy, 2026)

Synergistic dual-engineering of poly (lactic acid) biodegradable plastics: Low-carbon toughening meets controlled degradation kinetics - Ying Jing; Xintong Jiang; Yutong Zhang; Weihan Chi; Siying Leng; Yongchao Li; Yongsheng Hao; Yuanxia Wang; Rongguang Li; Lixin Song (Chemical Engineering Journal, 2026)

East Asian dust-storm activity: onset, trends, and mechanisms across timescales - Jin-Chang Li; Ying-Hui Song; Cai-Xia Zhang (Regional Environmental Change, 2026)

Miexianling: a novel dual-action pesticide for sustainable pine wilt disease management through integrated beetle and nematode control - Min Li; Guanyi Cheng; Ming Xu; Mengyao Wang; Yue Li; Jingeng Tang; Yinchu Chai; Kangquan Chen; Muhammad Faizan Latif; Ying Pei; Ting Yang; Yajing Song; et al. (Journal of Pest Science, 2026)

Particle size and chemical constituents of ambient particulate pollution associated with conjunctivitis in southeastern coastal area of China - Liujie Zhu; Tao Zhang; Yingnan Xu; Ying Li; Dongyue Chai; Yanfeng Liao; Zuqiong Song; Jian Wang; Zhen Wang; Wei Shan; Wenhui Liu; Hui Guo; et al. (Air Quality, Atmosphere & Health, 2026)

First report of Hibiscus chlorotic ringspot virus in croton (Codiaeum variegatum) in China - Ying Wei Khoo; Yunlong Ma; Yijing Song; Shifang Li (Journal of Plant Pathology, 2026)

Analysis of the antibacterial activity and mechanism of Litsea cubeba essential oil against Vibrio parahaemolyticus JD2305 causing translucent postlarvae disease - Qianhui Song; Laizhuang Jin; Di Fang; Na Ying; Lei Feng; Letian Li; Xiong Zou; Wenhong Fang (Aquaculture, 2026)

Neoproterozoic three-stage evolution in the northern margin of the lower Yangtze Block: Evidence from low-grade metamorphic sedimentary sequence in the Zhangbaling uplift - Xing Wei; Shuang-ying Li; Zhen-sheng Li; Dong-Dong Yang; Song Wang; Wei Xie; Bo Hu; Min Li; Cheng Cheng (Precambrian Research, 2026)

A single-cell-resolution spatial transcriptomic atlas decodes wheat spike development and yield potential - Xiang Zhang; Yi Peng Wang; Xiehai Song; Liang-Zi Zhou; Haixia Yu; Lei Yang; Yan Kai Wang; Xin Yu Wang; Xin Yan Wan; Yongqi Liu; Yan Shi; Zhiliang Yue; et al. (Molecular Plant, 2026)

Spectral investigation of ignition and alkali metal release from single coal particles: Influence of particle size - Ying Zhou; Runmin Wu; Jinyun Li; Xudong Song; Peng Lv; Jiaofei Wang; Weiguang Su; Yonghui Bai; Guangsuo Yu; Min Yao (Fuel, 2026)

Fabrication of multifunctional cellulose aerogel materials with one-dimensional (fiber), two-dimensional (film), and three-dimensional (structure) structures based on ambient drying technology - Lei Tan; Wei Tan; Yin Tian; Guixiang Song; Ying Chang; Ping Li; Yuanlin Ren (Chemical Engineering Journal, 2026)

16S rRNA gene-based big data profiling and comparative statistical analysis of anammox communities under different feed regimes - Haotian Liu; Zijian Tao; Ying Song; Lan Lin; Jingpeng Li; Meizhen Wang (Bioresource Technology, 2026)

Quantifying nonlinear driving forces of land surface temperature dynamics in the Tarim River Basin under climate warming - Qiangyan Lei; Xiaoning Song; Jingjing Chang; Ying Zhao; Huaiwei Sun; Xin Liu; Li Li; Xinran Qiao; Jie Xue (Theoretical and Applied Climatology, 2026)

Functional analysis of LcHsp70-1 in enhancing temperature stress tolerance in Lotus corniculatus - Yilong Li; Jing Liu; Zouxian Gong; Ying Xu; Jiahai Wu; Li Song (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Convergence Threshold and Failure-Mode Shift in Granite: Effects of Grain-to-Particle Size Ratio Revealed by PFC3D-GBM and Numerical AE–MT Inversion - Lei Zhang; Jian Zhou; Xiao Peng; Lu-Qing Zhang; Xia-ying Li; Song Wang; Zi-qian Yan; Jiu-zun Wang (Rock Mechanics and Rock Engineering, 2026)

Design, synthesis and cytotoxic activity of sulfonylated derivatives of camptothecin - Xiong-Fei Luo; Zhi-Jun Zhang; Zi-Long Song; Zhi-Ping Wang; Jia-Xuan Yan; Xiao-Fei Liu; Li-Zeng Peng; Cheng-Jie Yang; Ying-Qian Liu (Natural Product Research, 2026)

Horizontal dynamic responses of pile groups in unsaturated soil considering the second-order effects - Zhenlin Chen; Longteng Li; Zhaowei Ding; Yingcong Li; Ying Xue; Chunyu Song (Soil Dynamics and Earthquake Engineering, 2026)

The impact of precipitation on N2O emissions during the freeze-thaw cycle in a typical grassland in Inner Mongolia - Wangchen Zhang; Ying Zhao; Jan Frouz; Pengfei Xue; Jinbo Li; Lizhu Suo; Bing Song; Haixia Wang (Soil and Tillage Research, 2026)

In situ reverse micelle-assisted extraction of rosemary antioxidants: A green solvent-free strategy for extending the oxidative stability of flaxseed oils - Huihui Zhang; Mengna Song; Shulin Deng; Yong Wang; Ying Li (Food Chemistry, 2026)

NnLOX1-mediated aroma formation in lotus (Nelumbo nucifera) through multi-omics integration and machine learning - Longyun Cao; Ying Xin; Zifu Ni; Linjie Song; Zongyou He; Peng Jia; Zhixin Zhai; Hao Li; Chen Dong (Food Chemistry, 2026)

Prenatal and postnatal exposure to environmental level arsenic declines male reproductive function by affecting spermatogenesis and maturation in offspring - Xiaochao Song; Xu Yang; Weixiang Fu; Ying Xing; Chenkai Cheng; Xiaohui Tian; Wei Yang; Liying Zhao; Yiguang Lu; Xiang Li; Ao Cheng; Shu Liu; et al. (Environmental Research, 2026)

“Triboelectric immunotherapy” powered osteogenesis and osteoimmune reprogramming for graft-free repair of bone defects - Jianghan Xia; Haimei Li; Yuchen Song; Xinyi Tan; Zheng Wang; Chao Jian; Ying Yuan; Peng Jiang; Aixi Yu (Chemical Engineering Journal, 2026)

Cuproptosis Inhibition by C-Phycocyanin Confers Neuroprotection against Copper-Induced Mitochondrial Damage and Cognitive Impairment - Run Song; Junwan Fan; Jiannan Wu; Shiyi Yin; Ying Zhang; Shihe Jiang; Yan Li; Xin Zhao; Mengjiao Sun; Weina Jin; Wenyan He; Junqiang Yan (Molecular Neurobiology, 2026)

Characterization of Early Nodulin 93 (ENOD93) on the mucilage secretion of aerial roots in sorghum - Haojie Zhang; Yaru Yu; Yuxue Wu; Ying Li; Lei Feng; Yanlian Li; Qiuli Du; Ranxing Zhao; Xiaoqiang Wang; Xiaolin Song; Si Xu (Genetic Resources and Crop Evolution, 2026)

Prediction Of Relative Permeability Curve Based On Machine Learning Driven By Logging Data - Jia-ru Zou; Shou-dong Huo; En-liang Liu; Tong-sheng Zeng; Lian-lian Hu; Ya-ying Song; Meng Li (Applied Geophysics, 2025)

Side-stream anaerobic membrane bioreactor system for energy-positive sewage treatment - Chao Rong; Weifu Yan; Ying Song; Chunxiao Wang; Zhiguo Yuan; Yu-You Li; Tong Zhang (Water Research, 2025)

Chi-miR-146a promotes the propagation of Neospora caninum by targeting the TGF-β1/SMAD2 pathway - Jin-Ming Chen; Jing-Yu Li; Jia-Yi Jin; Xiao-Qi Bao; De-Liang Tao; Xiao-Yun Zhao; Jun-Ke Song; Xin Yang; Ying-Ying Fan; Guang-Hui Zhao (Veterinary Parasitology, 2025)

Groundwater level prediction in urban karst regions: The comparison of ensemble learning and deep learning models by considering climate conditions - Xiaoqing Song; Ruihan Xiong; Zhenzhu He; Danyuan Luo; Shuyi Li; Ying Wang; Qin Peng; Shilong Yang; Yuxuan Fang; Aiguo Zhou; Xu Guo; Hanxiang Xiong (Urban Climate, 2025)

Distinct mechanisms of soil organic carbon formation in natural and legume-based grasslands on the Loess Plateau, China - Zi-Qiang Yuan; Chao Fang; Tian Ma; Jiu-Ying Pei; Xin Song; Guang-Qian Yao; Jordi Sardans; Josep Penuelas; Xiang-Wen Fang; Feng-Min Li (Soil Biology and Biochemistry, 2025)

Photocatalytic activation of peroxyacetic acid by MnFe₂O₄ for efficient caffeine degradation: Efficacy, mechanisms and reusability - Ying Yu; Gengwei Lin; Huilin Dai; Qingsong Li; Chao Huang; Yunbo Song (Journal of Environmental Chemical Engineering, 2025)

Enhanced persulfate activation on CoFeNi-layered double oxide-loaded activated carbon particle electrodes triggered by a weak electrical current: Catalytic performance and mechanism - Hongxiang Li; Changbin Wang; Jinli Qiu; Haiou Song; Qian Lai; Tiantian Zhou; Chunxiao Han; Jiarong Li; Shaogui Yang; Huan He; Aimin Li; Baoju Li; et al. (Journal of Environmental Chemical Engineering, 2025)

Microanalysis of silane coupling agent graft-activated waste crumb rubber and its interfacial interaction with asphalt-aggregate in the dry process - Guangyao Li; Ying Gao; Xiaoge Tian; Meijun Song; Jie Zhang; Naitian Zhang (Fuel, 2025)

Ultrasound-assisted fermentation of doughs enriched with 7S and 11S soy protein fractions: impacts on quality and protein–protein interactions - Feng Han; Ying Sun; Jialin Song; Xin Zhang; Chuangshuo Yan; Yufan Wang; Shanfeng Chen; Chengye Ma; Hongjun Li (Food Research International, 2025)

Antiswelling MXene-based membrane with enhanced permeability for dyeing wastewater treatment: From asymmetric cross-linking to stability evaluation - Ying Wang; Jiaxuan Yang; Zi Wang; Han Zhang; Langrun Song; Guibai Li; Heng Liang; Langming Bai (Chemical Engineering Journal, 2025)

A semi-interpenetrating network and dynamic key synergistic enhanced MXene-based skin sensor for long-term health monitoring and human-computer interaction sensing - Ying Song; Xinglai Tong; Ran Ding; Xiaogang Li; Jun Tang (Chemical Engineering Journal, 2025)

Synergetic phase transition suppression and air-stability engineering in layered cathode materials for sodium ion batteries - Li-Feng Zhou; Hao Wang; Lei Cao; Li-Ying Liu; He Jia; Yi-Song Wang; Tao Du (Chemical Engineering Journal, 2025)

Functional insights into JrWOX5: a WOX transcription factor regulating adventitious rooting and plant architecture in walnut - Rui-xue Gao; Pu Zhang; Ying-ying Chang; Li Song; Xiao-bo Song; Dong Pei (Plant Cell Reports, 2025)

The Bed Nucleus of the Stria Terminalis—Paraventricular Nucleus of the Hypothalamus Neural Circuit Regulates Neuropathic Pain Through the Brain-Spleen Axis - Shoumeng Han; Xin Chen; Li Ma; Xin Zeng; Ying Wang; Tingting Xie; Fancan Wu; Kun Song; Kenji Hashimoto; Hanbing Wang; Long Wang (Neuroscience Bulletin, 2025)
Neuropathic pain is a chronic condition caused by damage or dysfunction in the nervous system. While the spleen may influence neuropathic pain, its role has been poorly understood. This study demonstrates that the spleen plays a crucial role in regulating neuropathic pain through the bed nucleus of the stria terminalis (BNST) - paraventricular nucleus of the hypothalamus (PVN) neural circuit in a chronic constriction injury (CCI) mouse model. Splenectomy, splenic denervation, or splenic sympathectomy significantly increased the mechanical withdrawal threshold (MWT) and reduced macrophage infiltration in the dorsal root ganglia (DRG) of CCI mice. Pseudorabies virus injections into the spleen revealed connections to the BNST and PVN in the brain. Chemogenetic inhibition of the BNST-PVN circuit increased macrophage infiltration in the DRG and decreased the MWT; these effects were reversed by splenectomy, splenic denervation, or sympathectomy. These findings underscore the critical role of the spleen, regulated by the BNST-PVN circuit, in neuropathic pain.

Chrysin improves endothelial inflammation via the NFAT pathway in Kawasaki disease - Jin Ma; Yan Li; Yunjia Tang; Guanghui Qian; Haitao Lv; Xiudao Song; Ying Liu (Molecular Biology Reports, 2025)

Transcriptome analysis of the hypothalamus and testes in Brandt’s Vole: new insights into mechanisms of photoperiodic plasticity in postnatal testicular development - Lewen Wang; Yaqi Ying; Ning Li; Ying Song; Lijuan Zhao; Hong Sun; Zhenlong Wang; Xiao-Hui Liu; Dawei Wang (Functional & Integrative Genomics, 2025)

Limonoids and protolimonoid from Swietenia macrophylla - Yun-Peng Sun; Wen-Fang Jin; Ze-Rong Xu; Ying-Wei Liu; Li-Juan Sun; Yang Yu; Jin-Song Liu; Guo-Kai Wang (Natural Product Research, 2025)

Pore-Structure-Controlled Acoustic Characteristics for Predicting Shallow Gas Distribution in Polar Offshore Drilling - Lei Li; Li He; Ying Zhao; Yu Song; Shiming Wei; Guojing Zhu; Qingying Tang; Tiancong Cui (Journal of Marine Science and Engineering, 2025)
Shallow gas drilling in polar seas poses severe geological hazards, particularly unexpected eruptions that threaten platform safety and the marine environment. Accurate prediction of shallow gas occurrence and eruption risk is therefore essential for safe deep-water operations. However, previous studies seldom considered the coupled effects of gas pressure and pore-structure evolution on acoustic wave velocity, leading to deviations in hazard assessment. In this study, laboratory experiments and numerical simulations were conducted to clarify these mechanisms. Results revealed a non-monotonic relationship between porosity and P-wave velocity in shallow gas-bearing sediments: P-wave velocity decreases with increasing porosity at low porosity levels but increases beyond a critical threshold. This is attributed to changes in particle interactions and cementation that enhance the shear modulus. The inflection porosity for shallow gas (78%) highlights the diagnostic role of pore-structure evolution in predicting shallow gas distribution. A mathematical correlation between P-wave velocity and formation pressure was further established, and MP-PIC simulations showed that higher pressure coefficients significantly accelerate eruption rates, with a 0.1 increase in the pressure coefficient raising the instantaneous eruption velocity by 5.27 m3/min. Based on these findings, a quantitative evaluation method was developed to assess shallow gas hazard risk, providing engineering guidance for site selection and real-time risk prediction, and contributing to safer offshore drilling and ecological protection in polar environments.

Two new pregnane alkaloids from Pachysandra terminalis Sieb. et Zucc. and their cytotoxic activities - Ying Wu; Yun Rui; Chao Ding; Chenwang Liu; Dan Zheng; Zilong Zhang; Yuze Li; Xiaomei Song; Dongdong Zhang (Natural Product Research, 2025)

Responses of crop yield and soil quality to organic material application in the black soil region of Northeast China - Ying Song; Zhijie Li; Hanwen Chen; Jiayu Sun; Xiaoling He; Jinxia Fu; Fenli Zheng; Zhi Li (Soil and Tillage Research, 2025)

Short-term no-tillage improves soil water retention and maintains soil aeration at high moisture conditions despite reduced macroporosity - Jing Tan; Bingcheng Si; Ying Zhao; Yili Lu; Yuxin Chen; Ning An; Song Li; Weichao Wang; Han Fu; Wei Han; Yanli Yi (Soil and Tillage Research, 2025)

Lipid-mediated photoprotection confers strong light resilience in hyperaccumulator Sedum alfredii - Yanjiao Dai; Jin Chen; Yang Mao; Huidan Jiang; Wenwen Zhao; Jing Peng; Ruibing Li; Ying Wang; Purui Guo; Mengnan Zhang; Chao Zhang; Jiaming Li; et al. (Plant Science, 2025)

Eugenol-based meroterpenoids with neural differentiation activity from Eugenia caryophyllata - Cong Yan; Sheng-Rui Yan; Yutong Zhu; Mengjiao Cai; Rui-Li Huang; Xinyu Wang; Shiqing Zhang; Lei Shi; Li-Jun Hu; Wen-Cai Ye; Xiao-Jun Huang; Ying Wang; et al. (Phytochemistry, 2025)

Single-cyst morpho-molecular identification detected an unexpected high species diversity of dinoflagellate resting cysts from the coastal seas of China - Zhe Tao; Yuyang Liu; Xiaohan Liu; Caixia Yue; Xiaoying Song; Zhangxi Hu; Shuo Shi; Ruoxi Li; Yunyan Deng; Lixia Shang; Zhaoyang Chai; Ying Zhong Tang (Harmful Algae, 2025)

Feasibility assessment of online coal quality monitoring based on concentrating photothermal rapid combustion: Insights from neural network and explainability analysis - Ying Wu; Pengfeng Yu; Jun Xu; Hanjian Li; Kai Xu; Huanying Chi; Long Jiang; Yi Wang; Sheng Su; Song Hu; Jun Xiang (Fuel, 2025)

The intraspecies heterogeneity of wild Staphylococcus equorum in starter cultures drives differences in physicochemical and aroma characteristics in Chinese fermented sausage - Di Zhang; Ruren Li; Ying Xu; Futong Song; Nan Zhang; Ting Sun; Liangyan Rong (Food Bioscience, 2025)

Formoterol, a clinically approved drug, inhibits ferroptosis by suppressing lipid peroxidation and attenuates APAP-induced acute liver injury - Lin-Song Teng; Zhen-Dong Ying; Xiao-Han Sun; Hao-Cheng Hou; Shi-Dong Qiu; Peng Liu; Ke-Jing Li; Lei Zhang; Xie-Huang Sheng (Chemico-Biological Interactions, 2025)

Superficially ordered porous silica microspheres with smaller mesopore for the separation of structural isomers in liquid chromatography - Yan Chen; Yan-Xiang Wang; Yan-Li Wang; Hai-Tao Lv; Ji-Ying Song; Qi Wu (Analytica Chimica Acta, 2025)

Middle Campanian to Maastrichtian foraminifera and biomarkers: Seawater incursion events in the Songliao Basin, Northeast China - Ke-Ying Yue; Sha Li; Tian Jiang; Dang-Peng Xi; Bo-Wen Song; Yu Liang; Li-Xin Sun; Tian-Fu Zhang; Hai-Chun Zhang; Xiao-Qiao Wan; Bo Wang (Palaeoworld, 2025)

Active species generation and migration in alginate-iron bentonite composite gels: Mechanistic insights into organic pollutant remediation - Yinfei Wang; Xiaofei Li; Ying Sun; Wenbin Li; Xiaokang Li; Wanying Song; Mengsheng Li; Yuhong Su; Zitian Gao (Journal of Environmental Chemical Engineering, 2025)

Cr-induced built-in electric field engineering in Ni3S2/VS heterojunctions: Achieving a catalytic leap for oxygen evolution reaction - Yu Zhong; Yijun Wu; Yongmin Ying; Jiang Wu; Huanan Wang; Le Chen; Jili Wen; Chaoen Li; Jian Song; Yan Li (Journal of Environmental Chemical Engineering, 2025)

Synergistic effects of microbial mineralization and chemical reduction on soil properties in high-concentration Cr(Ⅵ) remediation - Yuanyuan Li; Yaru Song; Shuiyue Shen; Wei Wei; Ying Zhao; Tingting Zhang; Mingli Wei (Journal of Environmental Chemical Engineering, 2025)

Releasing ACE-inhibitory peptides from walnut protein via pulsed electric field: A multiscale mechanism-structure-function investigation - Xueying Song; Siliang Wu; Chenchen Cao; Yihan Mu; Ying Li; Ruili Liu; Guowan Su (Innovative Food Science & Emerging Technologies, 2025)

Intercropping increases land use efficiency and reduces soil salinity in salt-affected soils, but has minimal effect on pH - Ying Song; Jineng Sun; Zhi Li (Field Crops Research, 2025)

Torque work of origin-destination flows: Quantifying urban place centrality from a physical perspective - Xiaorui Yan; Tao Pei; Ci Song; Zidong Fang; Xiaohan Liu; Tianyu Liu; Linfeng Jiang; Ying Gao; Guangdong Li; Jie Huang; Yaqin Sun (Computers, Environment and Urban Systems, 2025)

Amorphous Zr-based MOF engineered carbon felt electrodes for high-performance all-Iron flow batteries with enhanced areal capacity - Yuanfang Song; Qi-an Zhang; Ying Li; Ao Tang (Chemical Engineering Journal, 2025)

Microbially induced phosphate precipitation disentangles sludge retention time trade-off enabling efficient phosphorus removal with minimal sludge discharge in aerobic granular sludge - Peng Bi; Xiaohui Yan; Yueying Song; Hebin Miao; Hui Sun; Ying Han; Long Chen; Kangxin Yan; Mingyang Li; Fan Xiong; Jingwei Ma; Qiulai He (Chemical Engineering Journal, 2025)

Hierarchically shortened b-axis ZSM-5 nanosheet endows super catalytic stability for methanol-to-hydrocarbons reaction - Zhan Liu; Ying-Jun He; Zhi-Yi Hu; Jia-Min Lyu; Shen Yu; Yu-Hang Song; Xiao-Qiang Liao; Zhi-Wen Yin; Ming-Hui Sun; Yu-Chun Zhi; Li-Hua Chen; Bao-Lian Su (Chemical Engineering Journal, 2025)

Multifunctional flexible multilayer pressure sensor for pressure sensing, energy harvesting and versatile applications - Fu-Rui Teng; Song Sun; Si-Chen Tan; Ying-Jie Ma; Yue Huang; Lin Zhu; Di Wu; Ai-Dong Li (Chemical Engineering Journal, 2025)

Waste cotton thread-derived SnO2 microfibres for enhanced sensing to trace triethylamine and application in meat freshness detection - Jing-Han Wang; Xiao-Na Zhang; Kuo Lin; Wen-Xiao Li; Bao-Yu Song; Fei Ye; Ying Fu; Ying-Ming Xu (Chemical Engineering Journal, 2025)

Self-templated fabrication of heterogeneous F doped NiCo-alkoxides/NiCo hydroxides yolk-shelled spheres with enhanced performance for supercapacitors - Xu Zhang; Ying Chen; Shuxian Song; Lu Song; Ruichen Zhai; Yulan Meng; Shaojie Li; Lijuan Wei; Xutong Yang; Anmin Liu (Chemical Engineering Journal, 2025)

Polyphenol-synthesized nanoparticles with ALDH3A1 delivery ability for activating estrogen signaling for diabetic wound healing - Xiaoxuan Ma; Yiqiong Liu; Jingsi Jiang; Yi Ru; Ying Luo; Jiankun Song; Zhan Zhang; Ying Zhang; Dan Yang; Haotian Xu; Haiqing Dong; Yongyong Li; et al. (Chemical Engineering Journal, 2025)

Hollow mesoporous silica nanoparticles for enhanced immune protection in a multi-epitope vaccine against pseudorabies virus - Qun Wang; Jian-Dong Zhang; Hong-Xia Hu; Ying-Lei Zhang; Zhen Cheng; Shuang-Yan Xiao; Han Feng; Lin-Tao Li; Jing-Song Liu; Qi Su; Huan-Chun Chen; Zheng-Fei Liu (Chemical Engineering Journal, 2025)

Vapor additive strategy enabling perfect crystallization of vacuum-evaporated photovoltaic perovskites - Lei Huang; Zhang Chen; Kai-Li Wang; Zi-Hao Song; Xiao-Ying He; Zhen-Huang Su; Jing Chen; Chun-Hao Chen; Yu Xia; Yu-Tong Yang; Xin Chen; Rui-Hao Qin; et al. (Chemical Engineering Journal, 2025)

Association Between Primary Dysmenorrhea and Mental Health Traits: A Study Based on Multi-Phenotype Correlation Network and Mendelian Randomization Analysis in Female College Students - Huiting Jiangzhou; Hanpeng Xu; Yanqin Wen; Zeyi Guan; Yang Zheng; Xuemin Jian; Weichen Song; Aamir Fahira; Jinmai Zhang; Qing Zhang; Ying Zhao; Manfei Zhang; et al. (Phenomics, 2025)

Advances in the transcriptional regulation and lipid droplet turnover in microalgae - Huidan Zhang; Er-Ying Jiang; Yingjun Zhou; Hui Wang; Yong Fan; Xiaojin Song; Ming Lu; Fuli Li (Algal Research, 2025)

Three new pregnane steroids from the whole plant of Pachysandra terminalis Sieb. et Zucc. - Yuying Zhang; Chao Ding; Ying Wu; Yu Sun; Yuze Li; Xin Zhang; Huawei Zhang; Xiaomei Song; Dongdong Zhang (Natural Product Research, 2025)

In vitro culture and comparative pathogenic characteristics of two ciliates prevalent in the sea cucumber Apostichopus japonicus - Dongmei Yue; Peipei Li; Jingwei Jiang; Ying Dong; Bai Wang; Shan Gao; Gang Song; Hongjuan Sun; Feifei Zhang; Pingzhe Jiang; Yongjia Pan; Zunchun Zhou (Aquaculture, 2025)

Manipulating electrochemical phosphate recovery from acidic wastewater for synthesizing LiFePO4/C cathode material - Bingnan Song; Wei Chen; Ying Pu; Weiquan Li; Zhengshuo Zhan; Haisheng Fang; Yang Lei (Water Research, 2025)

Multi-omics profiling reveals infectious bursal disease virus-induced alterations in gene expression and metabolism in chicken bursa of fabricius - Cuiping Song; Siyu Li; Yanmei Yuan; Wei Gao; Xusheng Qiu; Lei Tan; Yingjie Sun; Ning Tang; Yang Qu; Ying Liao; Chan Ding (Veterinary Microbiology, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Bio-inspired, recycled and durable construction of superhydrophobic/oleophilic cotton fabrics with excellent oil/water separation ability based on dual carbon materials - Xinmeng Lv; Ying Song; Zhishuang Han; Zhenlin Tang; Haidi Li; Mengru Zhang; Xinqiang Wu; Zaihang Zheng; Yan Liu; Wenjing Tang (Process Safety and Environmental Protection, 2025)

Dual-functional berberine-magnolol co-assembled nanoparticles inhibit Fusarium graminearum growth and mycotoxin production - Chenguo Li; Wei He; Yao Cui; Shimin Wu; Qing'ao Song; Ying Li; Jimin Guo; Xizhen Ge; Pingfang Tian (Pesticide Biochemistry and Physiology, 2025)

Complete genome of Thalassotalea piscium NK451B, an Antarctic bacterium with abundant extracellular proteases - Jia-Yi Song; Zi-Ying Li; Xiao-Hui Yang; Jin-Rong Wei; Kang Li; Yi Zhang (Marine Genomics, 2025)

Green synthesis of pyrazole-DUT-67 for efficient selenite removal based on synergistic Zr-O-Se and NH-O-Se bonding interactions - Jiaqian Wang; Sufang Song; Bo Li; Ying Wang; Xudong Zhao (Journal of Water Process Engineering, 2025)

Associations Between Pre- and Post-Diagnosis Dietary Inflammatory Patterns and Ovarian Cancer Survival: Results From the Ovarian Cancer Follow-Up Study - Jia-Xin Liu; Rui-Han Bao; Meng Luan; Chuan Liu; Lang Wu; Fang-Hua Liu; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Qian Xiao; Dong-Hui Huang; Xiao-Ying Li; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

Short-chain chlorinated paraffins at environmentally relevant doses disrupt glucose homeostasis and insulin signaling by macrophage-mediated inflammation - Ying-Wen Mu; Wen-Huan Yao; Hui Li; Cui-Li Zhang; Yan-Jing Zhang; Xiu-Ning Zhang; Ge Song; Xiu-Lan Zhao; Tao Zeng (Journal of Hazardous Materials, 2025)

Elevated CO2 enhances Pb availability and desorption kinetics at the root-soil interface: Role of dissolved organic matter in soil solution - Lei Wang; Xiang Gong; Xiaohui Ren; Zhihui Sun; Yankun Song; Kexin Li; Haifeng Su; Jianhua Qu; Ying Zhang (Journal of Environmental Management, 2025)

“Three-in-One” MIL@PDA-UiOL@AIEgens driven lateral flow immunosensor for multimodal detection of aflatoxin B1 - Wenjuan Wu; Pengyue Song; Qingbin Xu; Ying Li; Jianlong Liu; Tingting Di; Jiabo Wang; Bin Fu; Yujiao Hou; Weijun Kong (Food Chemistry, 2025)

Preparation and characterization of a starch-based active packaging with pH-sensitive release via tea tree essential oil loaded in a covalent organic framework - Peiqin Cao; Yiping Song; Dongliang Jin; Yuxia Zhang; Panliang Zhang; Kewen Tang; Ying Li; Rongrong Wang; Kang Zhang (Food Chemistry, 2025)

Coffee mitigated cognitive impairments in sleep-deprived mice by regulating circadian rhythm, inflammation, oxidative stress, and intestinal ecology - Hui-Bin Jiang; Fen-Fen Wei; Wen-Ting Li; Zi-Han Lin; Chuang Zhu; Yan Wu; Ying Wang; Li-Hua Song (Food Bioscience, 2025)

Metabolomic profiling unveils biochemical dynamics in spontaneously fermented grape leaf by-products: towards sustainable agricultural waste valorization - Jia-Lin Xing; Yun-Lu Song; Yan-Ge Li; Lu Yang; Ke-Ying Duan; Ding-Ding Zuo; Jing Zhang; Hai-Nan Liu; Tong-Lu Wei; Mao-Song Pei; Da-Long Guo (Food Bioscience, 2025)

Photoinduced spectral narrowing in perovskite/organic heterostructures for high-selectivity near-infrared detection - Yu Zhang; Yaoyao Li; Heng Liu; Xiaowei Li; Ying Xu; Ziqi Zhu; Zhiqin Liang; Bo Qiao; Dandan Song; Swelm Wageh; Guangcai Yuan; Zheng Xu; et al. (Chemical Engineering Journal, 2025)

3D printing of a beehive-inspired tissue-engineered auricular cartilage scaffold for reconstruction of autologous microtia - Wilson Adrian Wijaya; Boqing Zhang; Jun Tang; Fengqin Song; Jingting Huang; Yuxiang Qin; Taoyu Liu; Zhenyu Zhang; Zhengyong Li; Ying Cen; Changchun Zhou (Chemical Engineering Journal, 2025)

Beyond convention: Construction of β-cyclodextrin-based shape-changing particles capable of light-responsive control and bioactivity application - Pu-Ying Qi; Li-Hong Shi; Zhi-Cheng Zheng; Yu-Mei Feng; Tai-Hong Zhang; Rong-Shuang Luo; Shuai Tan; A-Ling Tang; Hou-Yun Huang; Xiang Zhou; Hong-Mei Xiang; Li-Wei Liu; et al. (Carbohydrate Polymers, 2025)

A Comparative Analysis of Subtyping Methodologies on Cross-sectional sMRI Data - Shirui Zhang; Baitong Zhang; Kun Zhao; Zhuangzhuang Li; Pan Wang; Dawei Wang; Chengyuan Song; Jie Lu; Zengqiang Zhang; Hongxiang Yao; Tong Han; Chunshui Yu; et al. (Neuroscience Bulletin, 2025)

Analgesic Effects of Acupressure on Jing-jiaji Acupoints in a Rat Model of Cervical Spondylotic Radiculopathy - Shang-Hong Jiang; Song Yang; Ling Meng; Ling-Yao Xie; Jia-Ni Yang; Si-Qi Li; Ke-Ying Liao; Zhi-Fang Qiu; Yao-Yao Xiao; Man-Di Fu; Zhi-Li Liu; Xue-Yu Jiang (Molecular Neurobiology, 2025)

TAT-T407 Mitigates Apoptosis and Cognitive Impairments Following Cerebral Ischemia Through Disruption of TRPV1-CDK5 Interaction - Qian Feng; Ying Li; Xiangru Wen; Hui Li; Chengyu Qi; Nan Wang; Guang Zhu; Yanyan Fu; Changdong Liu; Dan Liu; Zhen Zhang; Fan Yang; et al. (Molecular Neurobiology, 2025)

Discovery of indole-carbohydrazide hybrids as novel broad-spectrum fungicidal lead compound though membrane-targeting mechanism - Ying Wu; Li-Hui Shao; Xian-Qun Hu; Yu Long; Yuan-Yuan Wu; Pei-Bu Yu; Ai-Ping Yan; Long-Fei Li; Xiang Zhou; Song Yang (Molecular Diversity, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Biomimetic design and construction of bio-based, superhydrophobic and multifunctionality-integration cotton fabrics for efficient oil/water separation - Zhishuang Han; Xinmeng Lv; Yingge Li; Zhenlin Tang; Haidi Li; Mengru Zhang; Ying Song; Xinqiang Wu; Xu Tang; Zaihang Zheng; Yan Liu; Wenjing Tang (Journal of Environmental Chemical Engineering, 2025)

Soil thinning dominates crop yield reduction among various degradation types in the typical black soil region of Northeast China - Ying Song; Zhijie Li; Jiayu Sun; Hanwen Chen; Jinxia Fu; Xiaoling He; Asim Biswas; Fenli Zheng; Zhi Li (European Journal of Agronomy, 2025)

Optimizing fertilizer N rates to maximize the N legacy effects of peanut for obtaining high wheat yields with low N surplus in a peanut-wheat rotation - Wenhai Huang; Jun Zou; Ying Yang; Jørgen Eivind Olesen; Yuhao Yang; Robert M. Rees; Hongbao Sun; Shuaijie Shen; Wenjie Li; Li Zhang; Haoyu Zheng; Zhenwei Song; et al. (European Journal of Agronomy, 2025)

Multidimensional impacts of ocean alkalinity enhancement on aquatic ecosystems and fisheries carbon sequestration capacity - Chang Liu; Chengzhuang Chen; Ying Wang; Mingxing Zhang; Xihong Song; Ling Liu; Ping Li; Zhi-Hua Li (Environmental Impact Assessment Review, 2025)

Sulfur-bonded hard carbon with enhanced interfacial and bulk kinetics for potassium-ion hybrid capacitors - Chuang Qiu; Anuj Kumar; Mohammad Tabish; Xinzhuo Mai; Liewen Guo; Ying Zhao; Yibo Zhu; Ang Li; Ghulam Yasin; Xiaohong Chen; Huaihe Song (Chemical Engineering Journal, 2025)

Rare earth ions-reinforced polycationic gel polymer electrolytes for enhancing ionic conductivity and zinc anode interface stability in flexible zinc-air batteries - Hang Zhang; Jianrong Liang; Ziran You; Ying Gao; Yachu Song; Junjie Ge; Yanhao Duan; Xingchen Yan; Da Lei; Chuanling Si; Zhengzheng Li (Chemical Engineering Journal, 2025)

Unveiling interactions between anammox and denitrification from long-term steady-state scale and transient kinetic scale in a granular sludge system - Hao Tan; Fengjun Yin; Jinjin Zheng; Xuehai Yue; Ying Zhao; Sha Wang; Cheng Song; Yongzhi Li; Hong Liu (Bioresource Technology, 2025)

Research progress on the bioactivity of platycodin D from Platycodon grandifloras - Ying Song; Xin Lv; Chuanbo Ding; Xinglong Liu; Yuanyuan Han; Shengyue Chen; Min Li; Ting Zhao (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Uptake and ecotoxicity of microplastics of different particle sizes in crop species - Ying Wang; Fei Li; Wei Chen; Zhaozheng Chen; Yunlong Huo; Jingrong Song (NanoImpact, 2025)

Boosting curcumin’s chemical stability and intestinal absorption via nanostructured lipid carriers: The impact of lipid composition - Jin Feng; Zhen Wang; Haizhao Song; Wuyang Huang; Lujing Xu; Cong Teng; Ying Li (Food Chemistry, 2025)

Establishment of mud crab (Scylla paramamosain) spermatogonial stem cell line: A potential tool for immunological research - Ying Song; Yanchuang Duan; Haiqing Luo; Linying Yun; Ming Zhang; Ngoc Tuan Tran; Huaiping Zheng; Qicun Zhou; Shengkang Li (Fish & Shellfish Immunology, 2025)

High-efficiency and stable perovskite solar cells via bidentate chelation for facet-engineered growth of FAPbI3 (111) crystals - Song Zhang; Yucong Zhou; Zhitao Shen; Yingying Li; Jian Song; Yicong Gao; Zezhi Wang; Bohao Zhang; Chong Chen; Rong Liu; Ying Liu; Ruirui Cao; et al. (Chemical Engineering Journal, 2025)

Semaphorin 3A protects against thoracic aortic aneurysm dissection by suppressing aortic angiogenesis - Li-Fei Wu; Jiao-Jiao Zhang; Xing Zhang; De-Ping Wang; Zhi-Fa Zheng; Jing Shen; Ying Zhou; Li-Juan Gao; Xuan Shang; Jun-Ya Ning; Qing-Hua Liu; Lan Zhou; et al. (Angiogenesis, 2025)

Electrochemical nitrite sensing using mass transfer signal with a catalyst-free small-sized rotating disk electrode for wastewater monitoring - Fengjun Yin; Xiaohui Yang; Shun Lu; Hanlin Zhang; Ying Zhao; Sha Wang; Cheng Song; Yongzhi Li; Zhaoming Chen; Hong Liu (Water Research, 2025)

Incidence, risk factors, and prognosis of hospitalized mechanical eye injuries in China: data from China Ocular Trauma Study (COTS) 2021–2023 - Han Han; Yongjie Chen; Gao Si; Guowei Huang; Jiayi Song; Wenfang Zhang; Danyan Liu; Jie Zhong; Xuemin Jin; Dawei Sun; Shenwen Liu; Yanming Huang; et al. (Science Bulletin, 2025)

Greenness, nighttime light, and couple fecundability: A national cohort study between 2014 and 2020 - Mengyao Li; Xinghou He; Bin Zhang; Hongbing Xu; Jianbin Wu; Xuyang Shan; Ya Zhang; Huiying Xu; Hongguang Zhang; Yuan He; Yan Fang; Zuoqi Peng; et al. (Environmental Research, 2025)

Chromosome-level genome assembly of a high-yield Chinese soybean variety Mengdou1137 unlocks genetic potential of disease and lodging resistance - Rujian Sun; Bincheng Sun; Zihao Zheng; Qi Zhang; Xingguo Hu; Rongqi Guo; Lei Feng; Shen Chai; Jingshun Wang; Ping Qiu; Ping Yu; Ying Liu; et al. (Theoretical and Applied Genetics, 2025)

Study on Failure Mechanism and Mechanical Properties of Sliding Protection Structure in Gob-Side Entry Retaining Formed by Roof Cutting - Jun Yang; Changjiang Li; Yubing Gao; Ying Zhao; Hongxu Song; Yuxuan Liu (Rock Mechanics and Rock Engineering, 2025)

Statins and the risk of dementia: a meta-analysis - Xue Li; Yuzhen Liu; Tiantian Song; Xiaoxuan Wu; Ying Xing (Acta Neurologica Belgica, 2025)

PRDX1 affects acrylamide-induced neural damage through the PTEN/AKT signaling pathway - Dong-Xue Fu; Ya-Ting Lei; Hai-Bo Guo; Ting Chen; Xiang-Ying Gao; Xiao-Li Wang; Xiang Huang; Ling-Ling Song; Sheng-Yuan Wang; Qin-Xue Dai (NeuroToxicology, 2025)

Formation of advanced glycation end-products and N-nitrosamines in salami of different recipes and fermented at different stages - Wenjing Wang; Zixiong Song; Ying Jing; Xiaoxiao Wei; Haizhen Li; Jianhua Xie; Mingyue Shen (Food Chemistry, 2025)

Mechanistic insights into advanced glycation end products production in glucose-lysine model system involved with ascorbic acid - Zixiong Song; Ying Jing; Xiaoxiao Wei; Haizhen Li; Jianhua Xie; Mingyue Shen (Food Chemistry, 2025)

Fungi in biocrusts facilitate ecosystem restoration during long-term vegetation succession in arid environments - Song Guang; Zheng Ying; Yang Haotian; Xinrong Li (CATENA, 2025)

Effects of iron/aluminum mineral phases on soil organic carbon storage in different clay soils of subtropical acidic forests - Yi Li; Chen-chen Wang; Cui Zou; Yang Zhao; Pei Wei; Yu-ying Liu; Xiao-jun Zhao; Dun-mei Lin; Xian-jin He; Jun-long Huang; Jin-song Guo; Guang-yu Zhu (CATENA, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Experimental and Theoretical Studies of Novel Cadmium(II) N2O-Schiff Base Complexes: Synthesis, Spectroscopic Characterization, X-ray Crystal Structure, and Fluorescent Properties - Yang Song; Yangyang Zhao; Zhengnan Zhou; Jinyao Deng; Ying Li; Guohua Dong (Journal of Fluorescence, 2025)

Impact of Faba Bean (Vicia faba L.) Diet and Subsequent Withdrawal on GIFT Tilapia (Oreochromis niloticus) Muscle Quality - Guanling Xu; Wei Xing; Tieliang Li; Shibo Wei; Ying Zhang; Tingting Song; Huanhuan Yu; Lin Luo (Fishes, 2025)
To systematically evaluate FB’s effects on tilapia muscle quality, two distinct experimental phases are designed, the crispy texture development phase (0–16 weeks) and the crispy texture retention phase (17–24 weeks), which can determine the minimum faba bean (FB) feeding duration required to achieve optimal textural modification and can assess the persistence of improved textural properties following FB withdrawal, respectively. The results demonstrated that a 60% FB inclusion diet administered for 16 weeks did not adversely affect tilapia growth performance. Significant improvements in textural parameters, including hardness, springiness, chewiness, and shear force, were observed in FB-fed tilapia as early as 8 weeks, with these enhancements being maintained throughout the 16-week feeding period. These superior textural characteristics persisted during the subsequent retention phase following FB withdrawal. Microstructural analysis revealed that the 60% FB diet significantly enhanced muscle-fiber density while reducing fiber diameter in tilapia during the 8–16 week feeding period. These microstructural modifications persisted throughout the texture retention phase, maintaining significant differences compared to the control group. Serological analysis demonstrated the FB group elevated Superoxide dismutase (SOD) activity and reduced malondialdehyde (MDA) levels at 4 weeks, though these differences normalized thereafter. qRT-PCR showed the 60% FB clearly increased the expression of mstn at 8 weeks, while col1a-2 and myog expressions also obviously improved at 12 weeks. In summary, dietary 60% FB improved tilapia muscle crispiness by altering texture and microstructure via gene-expression regulation. The minimum duration was 8 weeks to achieve crispiness in tilapia by the 60% FB diet without adverse effects on growth, immunity, and hepatopancreas function. Furthermore, the crispy texture of tilapia fillets was maintained for at least 2 months following withdrawal of the 60% FB diet after 16 weeks of continuous feeding.

Effects of hypoxic stress on gastric sieve (GS) filtering function of Litopenaeus vannamei - Letian Li; Yuan Wang; Laizhuang Jin; Lei Feng; Qianhui Song; Di Fang; Na Ying; Xincang Li; Wenhong Fang (Aquaculture, 2025)

A feasibility study on cortisol and cortisone as biomarkers for psychological stress in wastewater-based epidemiology - Xue-Ting Shao; Yan-Song Wang; Zhen-Fang Gong; Yan-Ying Li; Jian-Guo Lin; De-Gao Wang (Water Research, 2025)

Kuenenia-enriched hydroxyapatite granules enable stable high-rate nitrogen removal of high-strength food waste permeate in an EGSB-anammox system: Insights into granule performance and process scalability - Lan Lin; Wenzhao Zhao; Shen Cui; Ying Song; Yuanfan Zhang; Yu-You Li (Journal of Water Process Engineering, 2025)

The combination of metagenomics and metabolomics reveals the effect of nitrogen fertilizer application driving the remobilization of immobilization remediation cadmium and rhizosphere microbial succession in rice - Huan-Zhan Zhou; Bu-Qing Wang; Yong-Hong Ma; Yu-Ying Sun; Huan-Lin Zhou; Zhen Song; Yuan Zhao; Wei Chen; Jie Min; Jing-Wen Li; Tao He (Journal of Hazardous Materials, 2025)

High-Voltage aqueous supercapacitors based on l-lysine pH Self-Buffering Coating-modified carbon cloth electrode - Ang Xu; Jie Gao; Huan Li; Xiyu Song; Bo Xu; Ying Liu; Yuanyuan Yu; Ping Wang; Qiang Wang; Man Zhou (Chemical Engineering Journal, 2025)

Dextran from human feces-derived Weissella cibaria facilitates intestinal mucosal barrier function by modulating gut bacteria and propionate levels - Huan Zhao; Sakandar Abbas; Jing Ren; Haibin Huang; Ying Song; Xiaoning Su; Qiuyang Wu; Yane Ma; Hao Tang; Yi-Zhou Gao; Yuanzhe Li; Xiaoming Gu; et al. (Carbohydrate Polymers, 2025)

Antifungal Susceptibility of Melanized Fungi Isolated from CARD9 Deficient Patients: Implications for Treatment of Refractory Infections - Ying Ji; Yalong Li; Weiwei Wu; Sybren de Hoog; Zhe Wan; Qian Wang; Hao Zhang; Jin Yu; Xueke Niu; Ruoyu Li; Wei Liu; Yinggai Song (Mycopathologia, 2025)

Molecular characterization of a novel non-segmented double-stranded RNA mycovirus isolated from the phytopathogenic fungus Lasiodiplodia pseudotheobromae - Zhengzhe Guan; Mengjiao Wang; Jiayi Ma; Mengyuan Mu; Xinyu Li; Peimeng Sun; Mengyuan Zhang; Yuanyuan Zhang; Luyang Song; Caiyi Wen; Ying Zhao (Archives of Virology, 2025)

Re-exploration of phenolic compounds from natural waste rice husks: Combined synthesis of novel herbicide and evaluation of herbicidal activity - Li-xia Zhao; Ruo-nan Song; Jing-yi Li; Yue-chun Zou; Shuang Gao; Ying Fu; Fei Ye (Pesticide Biochemistry and Physiology, 2025)

Dual-scale modified BiOBr with enhanced structural self-transformation at wide pH for bifunctional treatment of Cr(VI) - Ningning Song; Yueyang Li; Tianye Wang; Quanying Wang; Guopeng Zhu; Ying Zeng; Xiutao Yang; Hongwen Yu (Journal of Hazardous Materials, 2025)

Impacts of straw return methods on crop yield, soil organic matter, and salinity in saline-alkali land in North China - Ying Song; Mingxiu Gao; Zhi Li (Field Crops Research, 2025)

The influence of microplastics on hypertension-associated cardiovascular injury via the modulation of gut microbiota - Siyuan Wang; Kaixin Yan; Ying Dong; Yihang Chen; Jiawei Song; Yufei Chen; Xiaoyan Liu; Ruiqiang Qi; Xinyu Zhou; Jiuchang Zhong; Jing Li (Environmental Pollution, 2025)

Shifting soil N regimes over a 70-year chronosequence of wetland reclamation and restoration - Kexin Li; Nannan Wang; Rui Su; Yunjiang Zuo; Jianzhao Liu; Ying Sun; Xinhao Zhu; Ziyu Guo; Lihua Zhang; Changchun Song; Ning Chen; Sergei Lupakov; et al. (CATENA, 2025)

Comparative genomics provides insights into the evolutionary history of the phylum Ciliophora (Eukaryota, Alveolata) and uncovers the adaptive evolution of anaerobic ciliate classes - Ying Zhang; Fasheng Liang; Yu Fu; Yong Chi; Wen Song; Alan Warren; Lifang Li (Zoologica Scripta, 2025)
Ciliophora are one of the most diverse phyla of unicellular eukaryotes. Members of this group are widely distributed and have been found in several environments including those that are anaerobic. However, the paucity of sufficient omics data for the major classes of the phylum Ciliophora, especially the anaerobic ciliate lineages, has been a serious impediment to research thus far. In this study, omics data were expanded to include representatives of 16 ciliate classes (excluding Cariacotrichea and Copemetopea) using single‐cell sequencing techniques. Using omics data of 57 ciliates and two apicomplexans, we conducted a comparative genomics study. Phylogenomic analysis based on 156 orthologous genes showed that: there are two superclades within the subphylum Intramacronucleata, i.e., Colpodea + Oligohymenophorea + Nassophorea + Plagiopylea + Prostomatea + Phyllopharyngea (CONThreeP), and Spirotrichea + Armophorea + Litostomatea + Odontostomatea + Muranotrichea + Parablepharismea (SALOMP); with the exception of Armophorea, all ciliate classes are monophyletic; neither Metopus nor Plagiopyla is monophyletic; Paraspathidium has a close affiliation with prostomateans. The results of the divergence time estimations indicated that: the radiation of Ciliophora occurred ca. 1067 million years ago (Mya); the SALOMP and CONThreeP lineages diverged from the intramacronucleatean common ancestor ca. 892 Mya and 851 Mya, respectively; the split between Muranotrichea and Parablepharismea occurred ca. 712 Mya; Odontostomatea are the youngest class, with a crown age estimated at ca. 19 Mya. In addition, we profiled stop codon usage and programmed ribosomal frameshifting (PRF) events. Our analyses revealed that: most of the species investigated use either TAA or TGA as the biased stop codon; stop codon usage in Paraspathidium sp. resembles that of Prostomatea; almost all ciliates included in the analyses have prevalent +1 and −1 PRF events. Finally, through GO enrichment analysis for group‐shared orthogroups of five anaerobic ciliate classes, we successfully identified the biological process and molecular function GO terms that were related to the adaptation of this particular group of ciliates to anaerobic environments. Together, these findings provide new insights into the evolutionary history of the Ciliophora and deepen our understanding of the adaptation of anaerobic ciliate groups to anaerobic environments from an evolutionary perspective.

An integrated photocatalytic redox architecture for simultaneous overall conversion of CO2 and H2O toward CH4 and H2O2 - Muhammad Salman Nasir; Bowen Sheng; Ying Zhao; Haotian Ye; Jun Song; Jinglin Li; Ping Wang; Tao Wang; Xinqiang Wang; Zhen Huang; Baowen Zhou (Science Bulletin, 2025)

Molecular disturbances and thyroid gland dysfunction in rats chronically exposed to a high dose of NaAsO₂: Insights from proteomic and phosphoproteomic analyses - Jie Xiang; Lili Fan; Hui Li; Qian Song; Ying Jin; Rui He; Xueli Pan; Dapeng Wang (Journal of Hazardous Materials, 2025)

Unveiling the metabolic heterogeneity and formation mechanism in Chinese typical Daqu based on Qu-omics - Yu Mu; Shangjie Yao; Ying Huang; Zhiyu Zhu; Dong Li; Ya Song; Zehuan Liu; Chunlin Zhang; Shirui Yu (Food Research International, 2025)

Surfactant-free W/O high internal phase emulsions co-stabilized by beeswax and phytosterol crystal scaffold: A promising fat mimetic with enhanced mechanical and mouthfeel properties - Ying Song; Xia Zhang; Jiarong Li; Rixin Zhang; Bing Li; Lin Li (Food Research International, 2025)

UPLC-HDMS revealed numerous novel compounds in soybean crude oil - Zhaohui Sun; Feng Dong; Rui Zhang; Xinyu Song; Xiaocai Huang; Yingran Dong; Xiaofei Jia; Shunian Luo; Ying Li; Maoqing Wang (Food Chemistry, 2025)

Design, synthesis and antifungal activity of novel pyrazole-amide-isothiazole derivatives as succinate dehydrogenase inhibitors - Ai-ling Bao; Xian-song Xie; De-yuan Wang; Zi-quan Deng; Yun Chen; Dan Liu; Wei-yi Li; Xiao-rong Tang; Wei Cheng; Ying-kun Yan (Food Chemistry, 2025)

A series of colorimetric and self-calibrated fluorescent sensors based on Ln-BTCs for detection of aflatoxin B1 in food - Jun-Ying Li; Xi-Hui Diao; Chao Chen; Hao Wang; Wei Li; Chuan-Song Qi; Jun-Xuan Li; Yun-Wu Li (Chemical Engineering Journal, 2025)

Design of F doped sulfide bifunctional catalyst and investigation on the mechanism transformation of oxygen evolution reaction - Nianwen Song; Keyi Lv; Bo Feng; Ziyong Zhang; Xiangwen Tan; Yanfei Wei; Ziyang Yan; Yuchao Zhang; Xiaofei Yu; Lanlan Li; Xinghua Zhang; Xiaojing Yang; et al. (Chemical Engineering Journal, 2025)

Correlation analysis of transcriptome and metabolomics and functional study of Galactinol synthase gene (VcGolS3) of blueberry under salt stress - Fan Zhang; Tianjie Li; Longfei Gao; Dinakaran Elango; Jiaxin Song; Chaijing Su; Mingxuan Li; Weihua Zhang; Ming Chi; Xiaoyu Wang; Ying Wu (Plant Molecular Biology, 2025)

Whole genome re-sequencing to reveal genetic diversity and to develop snp array in common tobacco - Fangchan Jiao; Tianbao Li; Ying Gao; Congwei Sun; Xingfu Wu; Zhongbang Song; Xuejun Chen; Yongping Li; Lifeng Gao (Biologia, 2025)

Seasonal changes of species- and guild-based benthic diatom communities in the transitional water zone of the Yellow River Delta - Xing Liu; Yan Zhao; Xiaoqiu Yu; Ying Song; Yun Li; Guanpin Yang; Yuhang Li; Baohua Zhu; Kehou Pan (Marine Environmental Research, 2025)

Construction of Bi2MoO6/CdS S-scheme heterojunction for highly efficiency photocatalytic reduction of Cr(VI) under visible light - Yuhang Wu; Jianping He; Ying Liu; Xiaohui Ma; Songbo Li; Guibao Guo; Yiguo Su; Meiting Song (Journal of Water Process Engineering, 2025)

Enhanced chemiluminescence by carbon dots for rapid detection of bisphenol A and nitrite - Yujie Xiao; Xiaoqin Long; Xue Zhang; Junjie Mu; Qiuxiong Chen; Yuxian Mai; Ying Li; Hao Xue; Pengyang Song; Xian Yang; Hong Zheng (Food Chemistry, 2025)

Identification and characterization of 16 tripartite motif-containing proteins from Takifugu obscurus - Li-Fan Cui; Rui Shen; Xiao-Rui Song; Yan Shi; Zhe Zhao; Ying Huang (Fish & Shellfish Immunology, 2025)

Significantly improving the stability of high-entropy PtFeNiCoMn nanoalloys by nitrogen doping in oxygen electrocatalysis - Mang Niu; Qinhe Guan; Weiyong Yuan; Chun Xian Guo; Dapeng Cao; Chang Ming Li; Lian Ying Zhang; Xiu Song Zhao (Chemical Engineering Journal, 2025)

The protective effect of two highly branched polysaccharides from corn silk fermented by Lactobacillus plantarum against acute liver injury - Yuxiang Wu; Ying Song; Ruiting Li; Ziyan Han; Liyin Li; Yishu Yan (Carbohydrate Polymers, 2025)

Space heterogeneity of nitrogen removal functional genes, nitrogen transformation pathways and mechanisms in MEBR treating mariculture wastewater - Wenhao Xu; Zhiwei Chen; Yu Ba; Jia Zhang; Weizhao Wang; Yihan Li; Qian Zhang; Jing Song; Ying Liu (Bioresource Technology, 2025)

Investigating the role of two-dimensional and three-dimensional urban structures in seasonal surface radiation budget - Jingyi Chen; Shisong Cao; Meng Du; Mingyi Du; Xianglei Liu; Wen Song; Ying Liang; Wen He; Ling Li; Nuan Wang (Building and Environment, 2025)

Progress in Transdifferentiation of Autologous Alternative Cell Sources into Corneal Epithelial Cells - Bei Wang; Jiang-Lan Zhao; Wan-Ying Cai; Gong-Yue Wang; Yu-Zhi Li; Jia-Song Wang; Hua-Tao Xie; Ming-Chang Zhang (Stem Cell Reviews and Reports, 2025)

Navβ2 Intracellular Fragments Contribute to Aβ1-42-Induced Cognitive Impairment and Synaptic Deficit Through Transcriptional Suppression of BDNF - Min-Nan Lu; Dan Wang; Chen-Jun Ye; Guo-Ji Yan; Jing-Feng Song; Xin-Ying Shi; Shan-Shan Li; Li-Na Liu; Hui-Xiang Zhang; Xiao-Han Dong; Tao Hu; Xu-Yang Wang; et al. (Molecular Neurobiology, 2025)

Dual emission chiral carbon dots as fluorescent probe for fast chiral recognition of tryptophan enantiomers - Qi Wu; Yuan Chen; Yan-Li Wang; Ji-Ying Song; Hai-Tao Lv; Ya-Ming Sun (Analytica Chimica Acta, 2025)

Investigating the psammophilic karyorelictean ciliate families Kentrophoridae and Cryptopharyngidae (Protista, Ciliophora): molecular phylogeny, geographic distributions and a brief revision including descriptions of a new genus, a new species and a new combination - Mingzhen Ma; Danxu Tang; Wen Song; Lifang Li; Igor V. Dovgal; Khaled A. S. Al-Rasheid; Hunter N. Hines; Ying Yan (Marine Life Science & Technology, 2024)
Psammophillic ciliates are an integral part of the foodweb despite being underrepresented in terms of molecular phylogeny and modern taxonomy. To investigate the karyorelictean group, sampling was conducted in interstitial marine habitats in China for ciliates living between the sand grains, resulting in an examination of the families Cryptopharyngidae Jankowski, 1980 and Kentrophoridae Jankowski, 1980. Three species, i.e., Cryptopharynx setigerus Kahl, 1928, Kentrophoros fasciolatus (Sauerbrey, 1928) Foissner, 1995 and K. fistulosus (Fauré-Fremiet, 1950) Foissner, 1995, are clearly recognized as being cosmopolitan, while other species await further recording. Phylogenetic analyses were carried out based on updated data. These revealed that the families Cryptopharyngidae and Kentrophoridae are closely related, and most genera studied are monophyletic, although Cryptopharynx qingdaoensis n. sp. is located within the Kentrophoridae branch. Brief revisions of two genera, namely Cryptopharynx Kahl, 1928 and Kentrophoros Sauerbrey, 1928, are provided including keys to the identification of nine species belonging to the former and 12 species belonging to the latter. One new genus, Parakentrophoros n. gen., and one new species, Cryptopharynx qingdaoensis n. sp., are described and a new combination, Parakentrophoros canalis (Wright, 1982) n. comb., is established. Finally, it appears that the subapical oral apparatus undergoes a gradual degeneration process from Cryptopharyngidae to Kentrophoridae.

Vkorc1 polymorphisms of the Norway rats in China: Implications for rodent management and evolutionary origin of anticoagulant resistance mutations - Xiuhui Wang; Xiaohui Ma; Meng Qin; Ting Sun; Dawei Wang; Ning Li; Xiaohui Liu; Meidong Jing; Deng Wang; Ying Song (Science of The Total Environment, 2024)

Probing fragile topology with dislocations - Ying Wu; Zhi-Kang Lin; Yating Yang; Zhida Song; Feng Li; Jian-Hua Jiang (Science Bulletin, 2024)

Long-term cereal-legume intercropping accelerates soil organic carbon loss in subsoil of dryland - Wei Wang; Guang-Rong Chen; Meng-Ying Li; Yinglong Chen; Yang Wang; Hong-Yan Tao; Hui-Zhi Hou; Muhammad Maqsood Ur Rehman; Muhammad Ashraf; Yajie Song; Levis Kavagi; Bao-Zhong Wang; et al. (Resources, Conservation and Recycling, 2024)

New insights into thallium(I) behaviors at birnessite surfaces: Effects of an organic buffer and goethite - Wen Zhuang; Tianqiang Zhu; Feng Li; Chuanyong Jing; Samantha C. Ying; Macon J. Abernathy; Jinming Song; Hui Yin (Journal of Hazardous Materials, 2024)

Daily gaseous air pollution and pediatric conjunctivitis: A case-crossover study across ten cities in China's southeastern coastal region - Zengliang Ruan; Amanda Högdén; Tao Zhang; Ying Li; Yingnan Xu; Jian Wang; Dongyue Chai; Zhen Wang; Wei Shan; Yanfeng Liao; Zuqiong Song; Wenhui Liu; et al. (Journal of Hazardous Materials, 2024)

Transformation of exogenous hexavalent chromium in soil: Factors and modelling - Ying Li; Jiaping Lin; Yang Wu; Song Jiang; Chaoran Huo; Tongxu Liu; Yang Yang; Yibing Ma (Journal of Hazardous Materials, 2024)

Key Maillard intermediates - α-dicarbonyl compounds in foods: Occurrence, analysis, toxicity, and mitigation strategies - Yafei Kou; Zixiong Song; Ying Jing; Haizheng Li; Xiaoxiao Wei; Jianhua Xie; Mingyue Shen (Food Control, 2024)

Corrigendum to ‘Heavy metals and metalloids exposure and liver function in Chinese adults - A nationally representative cross-sectional study’ [Environ. Res. 252-P2 (2024) 118653] - Shiyu Wang; Yuebin Lyu; Saisai Ji; Nankun Liu; Bing Wu; Feng Zhao; Zheng Li; Yingli Qu; Yuanduo Zhu; Linna Xie; Yawei Li; Zheng Zhang; et al. (Environmental Research, 2024)

Swine wastewater co-exposed with veterinary antibiotics enhanced the antibiotic resistance of endophytes in radish (Raphanus sativus L.) - Wei-Li Jia; Fang-Zhou Gao; Chao Song; Chang-Er Chen; Chuan-Xin Ma; Jason C. White; Guang-Guo Ying (Environmental Pollution, 2024)

Effective partial nitritation of dewatered liquor from dry methane fermentation using the submerged aerobic fixed film reactor (SAFFR) - Ying Song; Yue Huang; Zhen Ma; Jialing Ni; Tong Zhang; Yu-You Li (Chemical Engineering Journal, 2024)

Two new furanone derivatives from the endophytic fungus Byssochlamys sp. and their cytotoxic activities - Jie Wang; Wen-Bin Gao; Fan-Wei Liu; Qi Liu; Bo Song; Jin Ye; Ying Chen; Cai-Lin Zhao; Wei Dong; Li-Na Guo; Bo Song (Natural Product Research, 2024)

Community of Arbuscular Mycorrhizal Fungi in the Rhizosphere Soils with Different Generations of Hybridized Progeny of Wild Erianthus arundinaceus and Sugarcane - Jin-Lian Zhang; Yi-Hao Kang; Juan Song; Huan-Ying Xu; Wei Zhang; Ying-Jie Nong; Qian Wang; Qin-Nan Wang; Ting-Su Chen; Yang-Rui Li (Sugar Tech, 2024)

The roles of abscisic acid and ethylene in cadmium accumulation and tolerance in plants - Jiayou Liu; Liu Yang; Ying Wen; Yuxuan Li; Sergey Shabala; Jie Zhang; Won-Yong Song (Plant and Soil, 2024)

Functional diversification of contact calls contribute to the cohesion of a multi-level society - Yi-Jun Yang; Ying Yan; Gu Fang; Yu-Ting Song; Jing Zang; Wen-Yong Tian; Dai-Bo Zhu; Paul A. Garber; Bao-Guo Li; Xiao-Guang Qi (Behavioral Ecology and Sociobiology, 2024)

Sirtuin 7 ameliorates cuproptosis, myocardial remodeling and heart dysfunction in hypertension through the modulation of YAP/ATP7A signaling - Yu-Fei Chen; Rui-Qiang Qi; Jia-Wei Song; Si-Yuan Wang; Zhao-Jie Dong; Yi-Hang Chen; Ying Liu; Xin-Yu Zhou; Jing Li; Xiao-Yan Liu; Jiu-Chang Zhong (Apoptosis, 2024)

Characteristics of Salivary Iodine Concentration in Elderly Residents of High-iodine Areas - Mengxin Liu; Junjing Li; Hexi Zhang; Yantong Liu; Zhangzhao Wang; Zhiyuan Ren; Chunxi Wang; Qi Jin; Ying Zhang; Haohao Meng; Qiuyi Song; Wenxing Guo; et al. (Biological Trace Element Research, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Bioaccessibility and bioavailability assessment of cadmium in rice: In vitro simulators with/without gut microbiota and validation through in vivo mouse and human data - Fei-Fei Xu; Ying-Si Chen; Xiu-Qin Lin; Ai-Hua Zhong; Min Zhao; Yue-Qi Li; Zi-Yin Li; Yue-Fei Lai; Jia Song; Jia-Liang Pan; Zhan-Fan Cai; Xu-Xia Liang; et al. (Science of The Total Environment, 2024)

Visible-light-driven photobiocatalytic synthesis of chiral sulfoxides over immobilized chloroperoxidase on magnetic yolk–shell Fe3O4@Cu-H-TiO2 photocatalyst - Xiaoyang Yue; Yuying Hou; Cuiyao Cao; Xue Cao; Haolei Song; Yanjun Jiang; Liya Zhou; Ying He; Xiaobing Zheng; Li Ma; Shijie Li (Journal of Cleaner Production, 2024)

Bioconversion of lignans in flaxseed cake by fermented tofu microbiota and isolation of Enterococcus faecium strain ZB26 responsible for converting secoisolariciresinol diglucoside to enterodiol - JiaQi Zhu; Zizhe Cai; Ziliang Song; Ying Li; Youn Young Shim; Martin J.T. Reaney; Yee Ying Lee; Yong Wang; Ning Zhang (Food Chemistry, 2024)

Tailoring stability in oil-in-water high internal phase Pickering emulsions (HIPPEs) through surface modification of beeswax-based solid lipid particles (SLPs) with various surfactants - Rixin Zhang; Bing Li; Ying Song; Lin Li; Xia Zhang (Food Hydrocolloids, 2024)

Weakly solvated electrolyte enables the robust solid electrolyte interface on SiOx anodes for lithium-ion battery - Zuojie Xu; Rong Huang; Pengfei Huang; Chaowei He; Shenwen Liu; Haonan Zheng; Wenlong Song; Lu Shi; Weiwei Gao; Dan Li; Hui Huang; Hangjun Ying; et al. (Chemical Engineering Journal, 2024)

An unsaturated chain carbonate additive contributing to high-performance LiFePO4//graphite battery at broad temperature range - Xin-Lin Zhang; Bin Dong; Yi Jin; Jia-Shun Song; Li Li; Jia-Yu Wang; Yu-Ying Zhu; Yan-Yun Sun (Chemical Engineering Journal, 2024)

Constructing asymmetric-electron-density Pd-Zn dual-atoms on N-doped defective mesoporous carbon for electrochemical reduction of CO2 - Yanlong Gong; Xiaohong Yang; Ying Zhang; Jingyun Li; Liang Xu; Song Li; Haitao Fu; Xizhong An (Chemical Engineering Journal, 2024)

Sustainable and high performance MXene hydrogel with interlocked structure for machine learning-facilitated human-interactive sensing - Ying Song; Qi Ao; Tuohao Jiang; Xinglai Tong; Ran Ding; Xiaogang Li; Jun Tang (Chemical Engineering Journal, 2024)

Novel dopamine-derived carbon modified fe-based metal–organic framework enhanced aptasensor rendering ultrasensitive electrochemical detection of oxytetracycline - Jialing Song; Xiaoxuan Fan; Liang Ying Ee; Xuanhao Lin; Dengsong Zhang; Sam Fong Yau Li; Manhong Huang (Chemical Engineering Journal, 2024)

Molecularly tailored bifunctional nano-overlayers for efficient and stable inverted perovskite solar cells - Lu-Lu Jiang; Shao-Jie Li; Qi Li; Shuai-Ke Guo; Zhen-Rong Song; Ying-Zhuo Shen; Xiao-Nan Zhang; Dong-Sheng Zheng; Xiao-Dan Tang; Hai-Rui Liu (Chemical Engineering Journal, 2024)

Enhancement of stress resistance of electroactive biofilms against hypersaline shock via exogenous electron mediator addition - Tao Li; Chen-ying Li; Han-lin Liang; Xiao-xue Li; Xiao-li Yang; Hua Li; Hai-liang Song (Chemical Engineering Journal, 2024)

Exploring the remarkable effects of microwave treatment on starch modification: From structural evolution to changed physicochemical and digestive properties - Mengdi Cai; Yu Zhang; Hongwei Cao; Sen Li; Ying Zhang; Kai Huang; Hongdong Song; Xiao Guan (Carbohydrate Polymers, 2024)

Investigation on the 2018 prolonged freezing event in South China using the WRF model at convection-permitting resolution: Model performance and sensitivity analysis of physical parameterizations - Entao Yu; Lili Song; Binglan Wang; Ying Li; Xia Chen; Dong Chen; Xiashu Su (Atmospheric Research, 2024)

GW3, encoding a member of the P450 subfamily, controls grain width by regulating the GA4 content in spikelets of rice (Oryza sativa L.) - Xiaojing Dang; Qing Xu; Yulong Li; Shaojie Song; Changmin Hu; Chunyu Jing; Ying Zhang; Dezheng Wang; Delin Hong; Jianhua Jiang (Theoretical and Applied Genetics, 2024)

Zika virus infection induces glycometabolic disorder in northern pig-tailed macaques - Qing Li; Ren-Hua Yang; Yan Hu; Bei-Bei Tang; Ying-Jie Jiang; Chang-Bo Zheng; Tian-Zhang Song (Science China Life Sciences, 2024)

Phytochemical constituents from rhizomes of Dryopteris crassirhizoma and their anti-inflammatory activity - Xiao-Jun Li; Xiong-Hui Song; Si-Qi Tang; Kai-Xin Wei; Zong-Wu Suo; Yi Xu; Jiao Luo; Hao Huang; Chun-Ying Li; Dong-Xu Liu; Xiang-Qian Liu (Natural Product Research, 2024)

Comparing the Efficacy of Seaweed Rafts and Light Traps in Monitoring the Variation in Abundance and Diversity of Juvenile Fish Assemblage During Diurnal and Nocturnal Periods in Tropical Coastal Waters - Chufeng Fan; Zhongbo Miao; Yongxiang Li; Wentong Xia; Ying Lu; Songguang Xie; Yiqing Song (Fishes, 2024)
This study evaluates the relative and combined effectiveness of seaweed rafts and light traps in attracting juvenile fish, focusing on diel variations in juvenile fish assemblage in the tropical coastal waters of Gaolong Bay, Wenchang City, Hainan Province. Sampling was conducted in May 2023 during various time periods using self-made artificial drifting seaweed rafts and light traps. The nonparametric Kruskal–Wallis was employed to compare the diversity and catch per unit effort of juvenile fish across different time periods and sampling methods. The Permutational Multivariate Analysis of Variance, heatmaps, and Principal Coordinates Analysis were used to analyze and visualize the differences between juvenile fish assemblages. Our findings indicate that light traps were particularly effective during nocturnal periods, capturing a diverse array of species and achieving the highest richness and evenness indices. Seaweed rafts demonstrated the lowest diversity indices, largely due to the dominance of specific species, which likely contributed to the competitive exclusion of other species. Seaweed rafts showed significant effectiveness during noon, providing critical habitat and shelter that attracted juvenile fish despite the lower diversity. While each method demonstrated specific advantages, their combined approach did not significantly improve juvenile fish aggregation compared to the individual method. These findings underscore the importance of considering diel and tidal cycles in the selection of sampling methods, as aligning the method with the time of day can greatly enhance the accuracy of biodiversity assessments, leading to more informed conservation and management strategies for tropical coastal waters.

Ozone-Induced Lung Injury are Mediated Via PPAR-Mediated Ferroptosis in Mice - Juan Li; Huai Wei; Ning Wang; Jing Chen; Ying Zhang; Zhen An; Jie Song; Tianqi Niu; Weidong Wu (Biological Trace Element Research, 2024)

Multi-scale matching and simulating flows of ecosystem service supply and demand in the Wuhan metropolitan area, China - Ying Chen; Yina Lu; Ruolin Meng; Suran Li; Linzi Zheng; Min Song (Journal of Cleaner Production, 2024)

Effects of soil-groundwater environmental factors on BTEX transport and transformation: A review - Haohao Li; Xuefan Gu; Jing Song; Kunlong Hui; Gang Chen; Wenbing Tan; Hui Wang; Yu Jiang; Ying Yuan (Journal of Environmental Chemical Engineering, 2024)

Recurrent marine anoxia in the Paleo-Tethys linked to constriction of seaways during the Early Triassic - Yuyang Wu; Alexandre Pohl; Li Tian; Jacopo Dal Corso; Ying Cui; Daoliang Chu; Jinnan Tong; Huyue Song; Hanchen Song; Haijun Song (Earth and Planetary Science Letters, 2024)

Quinary metal oxide NiCoMnCeCaOx nanorod as a multifunctional catalyst towards hydrogen production from ethanol steam reforming: Synergistic effect of polymetallic component - Mingzheng Liao; Chunrun Qin; Liujie Xu; Sihan Guo; Chao Wang; Yi Li; Wei Liu; Qingbin Song; Ying Chen; Yanping Du (Chemical Engineering Journal, 2024)

Anti-biofouling amidoxime-quaternized polyethyleneimine hemp fiber for efficient uranium extraction from seawater - Xiang Li; Qi Liu; Shusen Chen; Jiahui Zhu; Yan Song; Haotian Wu; Ying Li; Rongrong Chen; Jing Yu; Jingyuan Liu; Jun Wang (Chemical Engineering Journal, 2024)

Influence of scion cultivar on the rhizosphere microbiome and root exudates of Phaseolus vulgaris in grafting system - Xiuli Wei; Yuanyuan Cui; Jiaqi Wang; Guoyuan Song; Ying Cao; Long Liu; Zhixin Liu; Jing Yang; Chen Li; Jiao Wang; Moran Li; Xiao Xiao (Plant and Soil, 2024)

Metabolic Heterogeneity and Potential Immunotherapeutic Responses Revealed by Single-Cell Transcriptomics of Breast Cancer - Shicong Tang; Qing Wang; Ke Sun; Ying Song; Rui Liu; Xin Tan; Huimeng Li; Yafeng Lv; Fuying Yang; Jiawen Zhao; Sijia Li; Pingping Bi; et al. (Apoptosis, 2024)

Dominant role of soil iron and organic matters in arsenic transfer from soil to plant in a mine area in Hunan Province, Central China - Yang Song; Fenglin Zhang; Haipu Li; Ya Gao; Yang Liu; Zhaoxue Zhang; Ying Fang; Xinghao Liu; Zhaoguang Yang (Environmental Science and Pollution Research, 2024)

Enhanced 1,2-dichloroethane removal using g-C3N4/Blue TiO2 nanotube array photoanode in microbial photoelectrochemical cells - Shaoyu Li; Zanyun Ying; Ruijian Peng; Yu Zhou; Shihan Zhang; Jingkai Zhao; Shuang Song; Jianmeng Chen; Jiexu Ye (Chemosphere, 2024)

Ozone sensitivity regimes vary at different heights in the planetary boundary layer - Xin Li; Wenjie Wang; Suding Yang; Yafang Cheng; Limin Zeng; Xuena Yu; Sihua Lu; Ying Liu; Min Hu; Shaodong Xie; Xiaofeng Huang; Jun Zhou; et al. (Science of The Total Environment, 2024)

Preliminary assessments of carbon release driven by Late Pleistocene Arctic ice sheets - Liming Ye; Xiaoguo Yu; Yeping Bian; Weijia Fan; Zhongqiang Ji; Sai Song; Ziyin Wu; Qian Ge; Dong Xu; Weiyan Zhang; Haiyan Jin; Xiaohu Li; et al. (Quaternary Science Reviews, 2024)

Antiviral C-geranylated flavonoids from Artocarpus communis - Rui-Li Huang; Wei Tang; Chaoqun Wang; Cong Yan; Yun Hu; Hai-Xia Yang; Hai-Yang Xiang; Xiao-Jun Huang; Li-Jun Hu; Wen-Cai Ye; Jian-Guo Song; Ying Wang (Phytochemistry, 2024)

Insights to the cooperation of double-working potential electroactive biofilm for performance of sulfamethoxazole removal: ARG fate and microorganism communities - Tao Li; Chen-Ying Li; Yan-Fei Wang; Jing-Nan Zhang; Hua Li; Hui-Fang Wu; Xiao-Li Yang; Hai-Liang Song (Journal of Hazardous Materials, 2024)

The impact of a natural resource protection policy on economic development: Based on a policy evaluation of China’s coal resource tax reform - Shuhong Wang; Weiyao Li; Ying Zhang; Malin Song; Xueli Chen; Lianbiao Cui (Energy Policy, 2024)

Research on the thermo-hydro-mechanical coupling simulation and deformation spatiotemporal evolution for the entire process of oil shale in-situ mining - Shengyuan Song; Shidi Mei; Ying Hu; Qiang Li; Zijian Chen; Shuo Zhang (Engineering Geology, 2024)

Probing the AFF4–CCNT1 protein–protein interaction using a metal–organic conjugate for treating triple-negative breast cancer - Ying-Qi Song; Yiwen Xu; Li-Jun Yang; Ling Wang; Shaozhen Jing; Guan-Jun Yang; Daniel Shiu-Hin Chan; Chun-Yuen Wong; Wanhe Wang; Vincent Kam Wai Wong; Chung-Hang Leung (Chemical Engineering Journal, 2024)

Erratum to “CO2-induced reconstruction for ORR-enhanced solid oxide fuel cell cathode” [Chem. Eng. J. 462 (2023) 142216] - Yuan Zhang; Junbiao Li; Heping Xie; Zhipeng Liu; Suling Shen; Ying Teng; Daqin Guan; Shuo Zhai; Yufei Song; Wei Zhou; Bin Chen; Meng Ni; et al. (Chemical Engineering Journal, 2024)

Reduction of c-type cytochromes by Fe(II)-ligand under oxic conditions: Roles of Fe(II)-heme complexation and reactive oxygen species - Kuan Cheng; Yunlu Yin; Ying Wang; Guoyong Huang; Dandan Pan; Milan Wang; Xuxin Song; Tongxu Liu; Xiaomin Li (Chemical Geology, 2024)

Convergent Neuroimaging and Molecular Signatures in Mild Cognitive Impairment and Alzheimer’s Disease: A Data-Driven Meta-Analysis with N = 3,118 - Xiaopeng Kang; Dawei Wang; Jiaji Lin; Hongxiang Yao; Kun Zhao; Chengyuan Song; Pindong Chen; Yida Qu; Hongwei Yang; Zengqiang Zhang; Bo Zhou; Tong Han; et al. (Neuroscience Bulletin, 2024)
The current study aimed to evaluate the susceptibility to regional brain atrophy and its biological mechanism in Alzheimer’s disease (AD). We conducted data-driven meta-analyses to combine 3,118 structural magnetic resonance images from three datasets to obtain robust atrophy patterns. Then we introduced a set of radiogenomic analyses to investigate the biological basis of the atrophy patterns in AD. Our results showed that the hippocampus and amygdala exhibit the most severe atrophy, followed by the temporal, frontal, and occipital lobes in mild cognitive impairment (MCI) and AD. The extent of atrophy in MCI was less severe than that in AD. A series of biological processes related to the glutamate signaling pathway, cellular stress response, and synapse structure and function were investigated through gene set enrichment analysis. Our study contributes to understanding the manifestations of atrophy and a deeper understanding of the pathophysiological processes that contribute to atrophy, providing new insight for further clinical research on AD.

The romantic history of signaling pathway discovery in cell death: an updated review - Lei-Yun Wang; Xing-Jian Liu; Qiu-Qi Li; Ying Zhu; Hui-Li Ren; Jia-Nan Song; Jun Zeng; Jie Mei; Hui-Xiang Tian; Ding-Chao Rong; Shao-Hui Zhang (Molecular and Cellular Biochemistry, 2024)

A local rainfall-triggered giant landslide occurred in a region along a high-speed railway on the Qinghai–Tibetan Plateau - Qingpeng Li; Wenhui Liu; Renjie He; Chunye Ying; Hairui Liu; Zengning Dou; Yabing Liu; Sha Yang; Xianteng Song (Journal of Mountain Science, 2024)

Effect of hydraulic retention time on denitrification performance and microbial communities of solid-phase denitrifying reactors using polycaprolactone/corncob composite - Hongwu Cui; Yuna Feng; Weibin Lu; Lu Wang; Hao Li; Yu Teng; Ying Bai; Keming Qu; Yingying Song; Zhengguo Cui (Marine Pollution Bulletin, 2024)

Population connectivity of small yellow croaker (Larmichthys polyactis) in the southern Yellow Sea: Implications from multiple otolith-based approaches - Dade Song; Ying Xiong; Zhongjie Kang; Long Liang; Xiaorui Wu; Dongjia Li; Dongyan Liu (Fisheries Research, 2024)

Safety and environmental protection application of high performance solid waste unburned ceramsite and its lightweight high strength concrete - Kai-jing Tang; Hong-na An; Chuan-bei Liu; Ying-ding Li; Lu-jun Jia; Yun Tang; Qi-qiang Wang; Yong Jiang; Zi-jian Song (Sustainable Chemistry and Pharmacy, 2024)

Modeling the molecular composition of secondary organic aerosol under highly polluted conditions: A case study in the Yangtze River Delta Region in China - Qi Huang; Hutao Lu; Jingyi Li; Qi Ying; Yaqin Gao; Hongli Wang; Song Guo; Keding Lu; Momei Qin; Jianlin Hu (Science of The Total Environment, 2024)

Increasing structure diversity of farnesylated chalcones by a fungal aromatic prenyltransferase - Ying Wu; Shiyunhua Qian; Xiang Zhou; Shu-Ming Li; Chun-Mao Yuan; Song Yang; Kang Zhou (Phytochemistry, 2024)

Phytochrome B interacts with LIGULELESS1 to control plant architecture and density tolerance in maize - Qingbiao Shi; Ying Xia; Qibin Wang; Kaiwen Lv; Hengjia Yang; Lianzhe Cui; Yue Sun; Xiaofei Wang; Qing Tao; Xiehai Song; Di Xu; Wenchang Xu; et al. (Molecular Plant, 2024)

A two-step method of cyclolinopeptide (linusorb) preparation from flaxseed cake via dry-screening - Zi-zhe Cai; Chen-xin Xu; Zi-liang Song; Jun-le Li; Ning Zhang; Jian-hao Zhao; Yee-Ying Lee; Martin J.T. Reaney; Fu-rong Huang; Yong Wang (Food Chemistry, 2024)

Metabolomic insights into the effects of seasonal shifts on the dynamic variation of non-volatile compounds of abalone (Haliotis discus hannai) - He-He Tian; Yu-Lian Li; Xu-Song Wang; Xu-Hui Huang; Yu-Ying Zhang; Zi-Chun Zhang; Da-Yong Zhou; Lei Qin (Food Chemistry, 2024)

Revisiting Neoproterozoic tectono-magmatic evolution of the northern margin of the Yangtze Block, South China - Peng Wu; Yuan-Bao Wu; Shao-Bing Zhang; Yong-Fei Zheng; Long Li; Ying Gao; Hao Song; Zhengqi Xu; Zeming Shi (Earth-Science Reviews, 2024)

Role of NiO in wide-bandgap perovskite solar cells based on self-assembled monolayers - Afei Zhang; Mingyu Li; Chong Dong; Wenjiang Ye; Yongxin Zhu; Jiakuan Yang; Long Hu; Xiong Li; Ling Xu; Ying Zhou; Haisheng Song; Chao Chen; et al. (Chemical Engineering Journal, 2024)

Multifunctional flexible carbon fiber felt@nickel composite films with core–shell heterostructure: Exceptional Joule heating capability, thermal management, and electromagnetic interference shielding - Shuai Liu; Jiaxin Yang; Ying Yu; Dongming Liang; Yun Li; Xingyu Si; Shasha Song; Mengmeng Meng; Jiahang Zhang; Yang Zhang (Chemical Engineering Journal, 2024)

Stable 3D porous N-MXene/NiCo2S4 network with Ni–O atomic bridging for printed hybrid micro-supercapacitors - Pengcheng Sun; Jingyuan Liu; Qi Liu; Jing Yu; Rongrong Chen; Jiahui Zhu; Gaohui Sun; Ying Li; Dalei Song; Jun Wang (Chemical Engineering Journal, 2024)

Fabrication of natural microcapsule with intrinsic core–shell structure as building blocks for achieving source control of obesity - Dan Li; Liwen Sun; Lingjuan Shi; Ying Zhang; Jun Liu; Mingqing Qiu; Yanhong Ma; Nana Kou; Wanting Song; Le Zhuo; Li Yang; Yang Wang; et al. (Chemical Engineering Journal, 2024)

A novel bio-based film-forming helper derived from Leuconostoc mesenteroides: A promising alternative to chemicals for the preparation of biomass film - Yukun Chen; Xiaofang Gong; Jie Song; Yinan Peng; Yang Zeng; Juan Chen; Zhiye Wang; Zhilong Li; Ying Zhu (Chemical Engineering Journal, 2024)

Sponge iron-coupled biochar solution can achieve the synergistic augmentation of carbon sequestration, carbon sink capacity, and denitrification in ecological ditches - Bi–Ni Jiang; Ying–Ying Zhang; Yan Wang; Hai–qin Liu; Qing Zhou; Yi–Jing Yang; Zhi–Yong Zhang; Yu–Li Yang; Wen–jing Guo; Hai–Liang Song (Chemical Engineering Journal, 2024)

Enhanced sludge granulation and stable performance of an anammox expanded granular sludge bed (EGSB) reactor through the utilization of hydroxyapatite (HAP) particles - Lan Lin; Ying Song; Yanlong Zhang; Zibin Luo; Qian Li; Wenzhi Cao; Yu-You Li (Bioresource Technology, 2024)

Cell-Free DNA in Plasma Reveals Genomic Similarity Between Biliary Tract Inflammatory Lesion and Biliary Tract Cancer - Ruimei Liu; Yueqiang Song; Rulin Hua; Shariq Ahmed; Yunxiao Xie; Cong Lai; Jialu Xu; Fuyuan Li; Ying Li; Zhiguang Li; Yinping Wang; Dekang Lv; et al. (Phenomics, 2024)

Identification of the Galactinol Synthase (GolS) Family in Medicago truncatula and Expression Analysis Under Abiotic Stress and Phytohormone Treatment - Hua Li; Ying Di Gao; Li Qing Kang; Hong Yang Yu; Li Ming Zeng; Yi Hua Wang; Rong Rong Chen; Jian Bo Song (Journal of Plant Growth Regulation, 2024)

A recombinase polymerase amplification–SYBR Green I assay for the rapid and visual detection of Brucella - Jiang Chang; Nan Wang; Jun-Peng Zhan; Shi-Jun Zhang; De-Ying Zou; Feng Li; Ying Zhang; Yan-Song Li; Pan Hu; Shi-Ying Lu; Zeng-Shan Liu; Hong-Lin Ren (Folia Microbiologica, 2024)

Evolution of weathering intensity in the Qaidam Basin, northeastern Tibetan Plateau, since the middle Miocene: Insights from clay mineral records - Jing Bao; Yibo Yang; Chengcheng Ye; Chunhui Song; Ying Feng; Bingshuai Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Molecular-level insight into the behavior of metal cations and organic matter during the aggregation of polystyrene nanoplastics - Ying Chen; Huan Tang; Hangzhe Li; Yue Yin; Wenhu Song; Honghong Guo; Tinglin Huang; Baoshan Xing (Journal of Hazardous Materials, 2024)

Dietary seafood as a potential modifier in the relationship between per- and polyfluoroalkyl substances (PFASs) burden and prediabetes/diabetes: Insights from a nationally representative cross-sectional study - Yingli Qu; Nan Sheng; Saisai Ji; Zheng Li; Jinghua Wang; Yitao Pan; Xiaojian Hu; Xulin Zheng; Yawei Li; Haocan Song; Linna Xie; Wenli Zhang; et al. (Journal of Hazardous Materials, 2024)

The role of OsBZR4 as a brassinosteroid-signaling component in mediating atrazine and isoproturon degradation in rice - Xiangning Su; Chuan Ying Li; Xue Song Liu; Yu Ping Zhang (Journal of Hazardous Materials, 2024)

Per- and polyfluoroalkyl substances and human health outcomes: An umbrella review of systematic reviews with meta-analyses of observational studies - Wei-Yi Xing; Jia-Nan Sun; Fang-Hua Liu; Li-Shen Shan; Jia-Li Yin; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Jia-Xin Liu; Wen-Rui Zheng; Ying-Ying Zhang; Xin-Jian Song; et al. (Journal of Hazardous Materials, 2024)

Unraveling the relationship between aroma characteristics and lipid profile of abalone (Haliotis discus hannai) during seasonal fluctuation and thermal processing - He-He Tian; Yu-Lian Li; Xu-Song Wang; Xu-Hui Huang; Yu-Ying Zhang; Zi-Chun Zhang; Da-Yong Zhou; Lei Qin (Food Chemistry, 2024)

Heavy metals and metalloids exposure and liver function in Chinese adults — A nationally representative cross-sectional study - Shiyu Wang; Yuebin Lyu; Saisai Ji; Nankun Liu; Bing Wu; Feng Zhao; Zheng Li; Yingli Qu; Yuanduo Zhu; Linna Xie; Yawei Li; Zheng Zhang; et al. (Environmental Research, 2024)

Metagenomic data highlight shifted nitrogen regime induced by wetland reclamation - Kexin Li; Nannan Wang; Fenghui Yuan; Xinhao Zhu; Yunjiang Zuo; Jianzhao Liu; Ziyu Guo; Ying Sun; Rui Su; Lihua Zhang; Sergei Lupakov; Yanyu Song; et al. (Biology and Fertility of Soils, 2024)

Influence of point bars on nitrogen transport and reaction in riparian zones - Xunchuan Song; Ying Liu; Defu Liu; Jinghong Feng; Linlin Li; Yongsheng Guo; Junxiong Luo; Weiping Jiang (Journal of Hydrology, 2024)

Synergistic signal amplification of ultrathin nanowire-like PtCoFeRuMo high-entropy nanozyme and Z-scheme WO3/ZnIn2S4 heterostructure for split-typed photoelectrochemical aptasensing of myoglobin - Fan Xu; Ben-Fang Xu; Qing-Ying Ai; Ai-Jun Wang; Li-Ping Mei; Pei Song; Jiu-Ju Feng (Chemical Engineering Journal, 2024)

Therapeutic effects and mechanisms of isoxanthohumol on DSS-induced colitis: regulating T cell development, restoring gut microbiota, and improving metabolic disorders - Ya-Na Yang; Bing Han; Mao-Qing Zhang; Na-Nan Chai; Feng-Lin Yu; Wen-Hui Qi; Meng-Yuan Tian; Dong-Zhi Sun; Ying Huang; Qing-Xin Song; Yan Li; Mao-Cui Zhu; et al. (Inflammopharmacology, 2024)

Simulation of Large Span Chamber Stability: Hoek Brown and Point Safety Factor Optimization - Liufang Li; Song Chen; Chunsheng Qiao; Zhao Yang; Ying Yuan; Yibo Zheng (Geotechnical and Geological Engineering, 2024)

Validation of endogenous U6 promoters for expanding the CRISPR toolbox in Nicotiana tabacum - Pan Luo; Siyuan Li; Lulu Li; Yanyan Li; Ying Qiao; Xianzhi Wu; Meiling Wu; Zhihao Song; Yong Yang; Ji Feng; Xingchun Tang (In Vitro Cellular & Developmental Biology - Plant, 2024)

Visitation-based classification of urban parks through mobile phone big data in Tokyo - Yichun Zhou; ChengHe Guan; Longfeng Wu; Ying Li; Xuanyi Nie; Jihoon Song; Seung Kyum Kim; Yuki Akiyama (Applied Geography, 2024)

Formulation and Characterization of Ethosomes for Transdermal Delivery of Prinsepia Utilis Rogle Seed Oil with Ameliorative Effects against UVB-Induced Skin Damage - Qianqian Fang; You Li; Fei Xiong; Xiaolong Hu; Ying Song; Wenbing Shen; Haijuan Dong; Xinhong Shi; Hao Wang (AAPS PharmSciTech, 2024)

Research on channel selection of low-carbon product considering advertising promotion under substitute competition - Haiyan Li; Qihan Cui; Lei Dou; Han Song; Ying Dai; Xinran Hu (Environment, Development and Sustainability, 2024)

Toxicity, Oxidative Stress, and Tissue Distribution of Butachlor in the Juvenile Chinese Mitten Crab (Eriocheir sinensis) - Song Wu; Peng Wang; Ying Zhang; Li Huang; Qirui Hao; Lei Gao; Dongli Qin; Xiaoli Huang (Fishes, 2024)
The Chinese mitten crab (Eriocheir sinensis) is one of the most commercially important crustacean species in China. The aim of this study was to characterize the toxic effects of butachlor (an herbicide of the acetanilide class) on juvenile E. sinensis crabs. The lethal effects and the acute toxicity of butachlor on juvenile E. sinensis specimens were assessed through a semi-static in vitro experiment. We determined the activities of superoxide dismutase (SOD) and catalase (CAT) as well as the levels of glutathione (GSH) and malondialdehyde (MDA) in the gills and the hepatopancreas of the juvenile crabs, at different time points over a 14-day short-term exposure to butachlor. Moreover, we measured the residual levels of butachlor in three different tissues (gills, hepatopancreas, and muscles) of the juvenile crabs over a longer period. Our findings revealed that butachlor is highly toxic for juvenile E. sinensis crabs. In fact, the median lethal concentration (LC50) values of butachlor at 24, 48, 72, and 96 h were found to be 4.22, 1.84, 0.34, and 0.14 mg/L, respectively, while the safe concentration was 0.014 mg/L. The antioxidant defense ability of the juvenile E. sinensis crabs against butachlor was induced after exposure to the herbicide at a concentration of 0.01 mg/L. After 14 days of exposure to butachlor at 0.04 and 0.16 mg/L, both SOD and CAT were found to be significantly inhibited (p

Subregions of the fusiform gyrus are differentially involved in the attentional mechanism supporting visual mental imagery in depression - Jun-He Zhou; Bin-Kun Huang; Di Wang; Bai-Le Ning; Xue-Song Liang; Chang-Hong Li; Zeng-Jian Wang; Ying Deng; Xi-Chang Huang; De-Long Zhang; Wen-Bin Fu (Brain Imaging and Behavior, 2024)

The formation mechanism, analysis strategies and regulation measures of cereal aroma: A review - Yao Feng; Hongwei Cao; Hongdong Song; Kai Huang; Yu Zhang; Ying Zhang; Sen Li; Yingjie Li; Jun Lu; Xiao Guan (Trends in Food Science & Technology, 2024)

The impact of arbuscular mycorrhizal fungi and endophytic bacteria on peanuts under the combined pollution of cadmium and microplastics - Zi-tian Pu; Dan-dan Wang; Wei-xing Song; Chao Wang; Zhao-yu Li; Ying-long Chen; Tori Shimozono; Zhao-min Yang; Yong-qiang Tian; Zhi-hong Xie (Journal of Hazardous Materials, 2024)

Transoceanic ships as a source of alien dinoflagellate invasions of inland freshwater ecosystems - Lixia Shang; Zhangxi Hu; Yunyan Deng; Jing Li; Yuyang Liu; Xiaoying Song; Xinyu Zhai; Zifeng Zhan; Wen Tian; Jinxiang Xu; Yangchun Han; Hao Shen; et al. (Harmful Algae, 2024)

Surface engineered carbon felt toward highly reversible Fe anode for all-iron flow batteries - Yuanfang Song; Hui Yan; Zhongxiao Cong; Jing Yang; Ying Li; Ao Tang (Chemical Engineering Journal, 2024)

First report of Sordaria macrospora causing collar rot of peanut in Shandong province, China - Xinying Song; Kang He; Ying Li; Jing Yu; Manlin Xu; Zhiqing Guo; Xia Zhang; Yucheng Chi (Journal of Plant Pathology, 2024)

Humic substances mediated superior photochemical pollutant conversion on defective TiO2 in environmentally relevant matrices: The key roles of oxygen vacancy in surface interactions, oxidant activation and radical generation - Song Hu; Lyumeng Ye; Bing-Jie Tian; Jia-Ying Li; Ai-Yong Zhang; Lu Zhao; Chi Zhang; Chu Jiang; Zhi-Xian Lin; Wei Da; Qi-Xin Wei (Science of The Total Environment, 2024)

Potential effects of individual and combined exposure to tetraconazole and cadmium on zebrafish from the perspective of enantioselectivity and intestinal microbiota - Shanshan Di; Ying Li; Beibei Song; Chao Guo; Peipei Qi; Zhiwei Wang; Zhenzhen Liu; Huiyu Zhao; Xinquan Wang (Science of The Total Environment, 2024)

Dominant contribution of combustion-related ammonium during haze pollution in Beijing - Libin Wu; Peng Wang; Qiang Zhang; Hong Ren; Zongbo Shi; Wei Hu; Jing Chen; Qiaorong Xie; Linjie Li; Siyao Yue; Lianfang Wei; Linlin Song; et al. (Science Bulletin, 2024)

Outer membrane vesicles of avian pathogenic Escherichia coli induce necroptosis and NF-κB activation in chicken macrophages via RIPK1 mediation - Zhe Li; Wenbin Shang; Ting Mei; Dandan Fu; Feng Xi; Ying Shao; Xiangjun Song; Zhenyu Wang; Kezong Qi; Jian Tu (Research in Veterinary Science, 2024)

Analysis of China's PM2.5 and ozone coordinated control strategy based on the observation data from 2015 to 2020 - Liuwei Kong; Mengdi Song; Xin Li; Ying Liu; Sihua Lu; Limin Zeng; Yuanhang Zhang (Journal of Environmental Sciences, 2024)

A complex synthetic surface for assessing flow direction algorithms based on total contributing area - Ying Song; Tao Yang; Zhenya Li; Chong-Yu Xu (Geomorphology, 2024)

Bioinspired electrostatic layer-by-layer assembly membranes constructed based on mild strategy for uranium extraction from seawater - Yan Yu; Jingyuan Liu; Shusen Chen; Yan Song; Rongrong Chen; Jing Yu; Jiahui Zhu; Ying Li; Qi Liu; Jun Wang (Chemical Engineering Journal, 2024)

Holistic investigation of structural evolution in corn stover lignin under pretreatment with varying γ-valerolactone concentrations - Xiaohong Hu; Ying Xia; Haiyong Wang; Xiuzheng Zhuang; Qiying Liu; Song Li; Qi Zhang; Longlong Ma (Biomass and Bioenergy, 2024)

A Pollution Barrier Self-Healing Material: Investigating the Effect of Individual Components on Its Performance and Determining Optimal Ratios and Healing Compositions - Fuhao Fan; Haibo Li; Liuyu Song; Ying Lin; Xiaofei Qin; Yang Liu; Sihan Li; Wei Yu; Yingying Wu (Water, Air, & Soil Pollution, 2024)

Carboniferous integrative stratigraphy, biotas, and paleogeographical evolution of the Qinghai-Tibetan Plateau and its surrounding areas - Keyi Hu; Xiangdong Wang; Wenqi Wang; Yingfan Song; Xunyan Ye; Lu Li; Yukun Shi; Sunrong Yang; Ying Li (Science China Earth Sciences, 2024)

CRISPR/Cas9-mediated knockout of Bsr-d1 enhances the blast resistance of rice in Northeast China - Ying Zhang; Xiu-Feng Lin; Li Li; Ri-Hua Piao; Songquan Wu; Anqi Song; Mengmeng Gao; Yong-Mei Jin (Plant Cell Reports, 2024)

Environmental exposure to per- and polyfluoroalkyl substances mixture and asthma in adolescents - Yi-Fan Wang; Li Li; Xu Wang; Ya-Nan Yun; Xue-Lin Wang; En-Yang He; Ming-Kun Song; Xue-Hong Xia; Ying-Xue Zou (International Archives of Occupational and Environmental Health, 2024)

Cobalt-doped CdS quantum dots enhanced photoelectroreduction of CO2 to formic acid with high selectivity - Shengqi Liu; Zhenyan Guo; Ying Yang; Pei-dong Wu; Zhengyi Li; Keping Wang; Heng Zhang; Hu Li; Song Yang (Environmental Chemistry Letters, 2024)

Associations of residential greenness exposure and ambient air pollutants with newly-diagnosed drug-resistant tuberculosis cases - Wan-mei Song; Yi Liu; Dan Men; Shi-jin Li; Ning-ning Tao; Qian-yun Zhang; Si-qi Liu; Qi-qi An; Xue-han Zhu; Qi-lin Han; Yu-zhen Zhang; Ying-ying Li; et al. (Environmental Science and Pollution Research, 2024)

Mechanical performance of CRTS II slab tracks in reinforced-unreinforced transition zone in extreme heat events - Yang Li; Haiyan Li; Rui Zhou; Jinjie Chen; Ying Song; Kailin Cao (Transportation Geotechnics, 2024)

Ornidazole degradation by PMS activated by Co-Zr-TiO2 with abundant oxygen vacancies: Performance, mechanism and degradation pathway - Xiaofei Qin; Haibo Li; Kaixuan Wang; Yang Liu; Liuyu Song; Ying Lin; Fuhao Fan; Sihan Li; Ting Ma (Process Safety and Environmental Protection, 2024)

Resveratrol improves meat quality traits by activating the lncRNAs-KEAP1-NRF2 axis in pigs - Sanbao Zhang; Peng Pan; Hongyue Xie; Chongwan Wei; Qian Wang; Bao Yang; Yanjie Sun; Yin Li; Yunyan Luo; Ying Song; Qinyang Jiang; Yanna Huang (Meat Science, 2024)

UiOL@AIEgens-assisted lateral flow immunosensor for the ultrasensitive dual-modal point-of-care detection of aflatoxin B1 - Wenjuan Wu; Ying Li; Pengyue Song; Qingbin Xu; Doudou Lei; Jiabo Wang; Bin Fu; Weijun Kong (Journal of Hazardous Materials, 2024)

Tree-structured parzen estimator optimized-automated machine learning assisted by meta–analysis for predicting biochar–driven N2O mitigation effect in constructed wetlands - Bi-Ni Jiang; Ying-Ying Zhang; Zhi-Yong Zhang; Yu-Li Yang; Hai-Liang Song (Journal of Environmental Management, 2024)

Analysis of key enzyme activity and aroma volatile compounds in microwave-irradiated quinoa during storage - Hongwei Cao; Jinzhe Han; Rulian Sun; Zhaoxia Li; Yu Zhang; Hongdong Song; Kai Huang; Ying Zhang; Xiao Guan (Journal of Cereal Science, 2024)

Does saponin in quinoa really embody the source of its bitterness? - Lin Meng Song; Yuan Yu; Li Dong Du; Xue Ying Ji; Hui Gao; Yu Qing Cai; Chang Jian Li; Peng Xue (Food Chemistry, 2024)

Precision-SELEX aptamer screening for the colorimetric and fluorescent dual-readout aptasensing of AFB1 in food - Ying Li; Boyu Jia; Pengyue Song; Nan Long; Linchun Shi; Peng Li; Jiabo Wang; Lidong Zhou; Weijun Kong (Food Chemistry, 2024)

Long-life high-voltage all-solid-state batteries enabled by bismuth (III)triflate mediated polymer electrolytes - Hao Yan; Jiaqi Hu; Yi-Xiao Deng; Ying Hu; Jin-Cheng Zheng; Wenrong Li; Tinglu Song; Yang Dai (Chemical Engineering Journal, 2024)

Accelerating the generation of NiOOH by in-situ surface phosphating nickel sulfide for promoting the proton-coupled electron transfer kinetics of urea electrolysis - Xin Guo; Longyu Qiu; Menggang Li; Fenyang Tian; Xue Ren; Sheng Jie; Shuo Geng; Guanghui Han; Yarong Huang; Ying Song; Weiwei Yang; Yongsheng Yu (Chemical Engineering Journal, 2024)

Effect of different operation conditions on PCDD/F inhibition by ammonium dihydrogen phosphate: concentrations, distributions and mechanisms - Jiayao Wu; Weican Xiang; Xiaoxiao Wang; Wenlong Song; Yuxuan Ying; Xiaoqing Lin; Xiaodong Li (Waste Disposal & Sustainable Energy, 2024)

Endothelial extracellular vesicles induce acute lung injury via follistatin-like protein 1 - Hao-Xiang Yuan; Ya-Ting Chen; Yu-Quan Li; Yan-Sheng Wang; Zhi-Jun Ou; Yan Li; Jian-Jun Gao; Meng-Jie Deng; Yuan-Kai Song; Li Fu; Hong-Bo Ci; Feng-Jun Chang; et al. (Science China Life Sciences, 2024)

Identification of a novel adenovirus in liver tissue sample of the Great Himalayan leaf-nosed bat (Hipposideros armiger) - Ling Cao; Xulai Song; Yu Qian; Ying Li; Jian Xu; Xurong Chen; Xiaochun Wang; Jianguo Chen (Brazilian Journal of Microbiology, 2024)

Correction to: Pre-Injection of Small Interfering RNA (siRNA) Promotes c-Jun Gene Silencing and Decreases the Survival Rate of Axotomy-Injured Spinal Motoneurons in Adult Mice - Ying-qin Li; Fa-huan Song; Ke Zhong; Guang-yin Yu; Prince Last Mudenda Zilundu; Ying-ying Zhou; Rao Fu; Ying Tang; Ze-min Ling; Xiaoying Xu; Li-hua Zhou (Journal of Molecular Neuroscience, 2024)

Leucine improves dietary protein use efficiency by regulating protein synthesis by activating amino acid transporters and the mTORC1 pathways in Chinese mitten crab (Eriocheir sinensis) - Ming-Qi Song; Qiu-Ran Yu; Er-Chao Li; Ying Song; Xin-Yu Cai; Yu-Xiang Huang; Chuan-Jie Qin; Xiao-Dan Wang; Jian-Guang Qin; Li-Qiao Chen (Aquaculture, 2024)

Faster cycling but lower efficiency: A microbial metabolic perspective on carbon loss after wetland conversion to cropland - Nannan Wang; Kexin Li; Fenghui Yuan; Yunjiang Zuo; Jianzhao Liu; Xinhao Zhu; Ying Sun; Ziyu Guo; Lihua Zhang; Chao Gong; Yanyu Song; Changchun Song; et al. (Soil Biology and Biochemistry, 2024)

Enhanced indigenous consortia for the remediation of uranium-contaminated groundwater by bioaugmentation: Reducing and phosphate-solubilizing consortia - Guo-hua Wang; Jian Song; Zhi-yue Zhang; Quan-jin Xiao; Shan He; Tao-tao Zeng; Ying-jiu Liu; Shi-you Li (Science of The Total Environment, 2024)

Unveiling the inhibition of chlortetracycline photodegradation and the increase of toxicity when coexisting with silver nanoparticles - Yajun Tian; Chuhan Ying; Liqiu Zhang; Huimin Huang; Shuang Song; Rongwu Mei; Jun Li (Science of The Total Environment, 2024)

Towards inclusive green growth in China: Synergistic roles and mechanisms of new infrastructure construction - Yuwei Song; Heping Huang; Ying Li; Jinglin Xia (Journal of Environmental Management, 2024)

Enhanced and accelerated degradation of PFOA using visible light—Applying semiconductor carbon nitride as an accelerator - Juying Li; Ying Liu; Yiqian Song; Li Cao; Yezhi Dou; Jia Yu; Yueqing Zhang; Jian He; Wei Dai; Cheng Yao; Deyang Kong (Journal of Environmental Chemical Engineering, 2024)

A transition from porphyry Mo to vein-style Zn-Pb mineralization: Insights from hydrothermal fluid evolution of the Chalukou deposit, NE China - Lu-Ying Jin; Ke-Zhang Qin; Brian Rusk; Jun-Xing Zhao; Zhen-Zhen Li; Guang-Ming Li; Guo-Xue Song (Journal of Asian Earth Sciences, 2024)

Regulating the continuous and concentrated distribution of Quasi-2D perovskite phases to achieve Sky-Blue Light-Emitting diodes with efficiency approaching 17% - Zhiqiang Bao; Shilei Yu; Xiaoyang Guo; Yunpeng Wang; Ying Lv; Deyue Zou; Li Song; Xingyuan Liu (Chemical Engineering Journal, 2024)

Enhancing structural response via macro-micro hierarchy for piezoelectric nanogenerator and self-powered wearable controller - Ying Han; Li Song; Hongwu Du; Geng Wang; Tongrui Zhang; Lei Ni; Yijun Li (Chemical Engineering Journal, 2024)

In-situ sodium chloride template synthesis of γ-WO3 hollow cubes for high-sensing and dual-selective hydrazine/dibutylamine detection at different temperatures - Guo-Li Chen; Ming-Song Lv; Jing Zhang; Zhao-Peng Deng; Ying-Ming Xu; Li-Hua Huo; Shan Gao (Chemical Engineering Journal, 2024)

Chemical constituents from the stem of Ficus pumila - Wen-Lin Xiao; Wen-Hao Chen; Wei Li; Guang-Ying Chen; Xiao-Ping Song; Chang-Ri Han (Natural Product Research, 2024)

The Community of Arbuscular Mycorrhizal Fungi in Sugarcane Rhizosphere Soils in Guangxi, China - Jin-Lian Zhang; Juan Song; Yi-Hao Kang; Yun-Ying Wen; Ying-Jie Nong; Qian Wang; Xiao-Juan Qin; Ting-Su Chen; Yang-Rui Li (Sugar Tech, 2024)

The lncRNA lnc-TSI antagonizes sorafenib resistance in hepatocellular carcinoma via downregulating miR-4726-5p expression and upregulating KCNMA1 expression - Fengrong Chen; Jiong Jiang; Dong Liu; Hong Li; Lei Dong; Yahua Song; Ying Zhang; Jing Wang; Yun Qin; Gang Zhao (Journal of Molecular Histology, 2024)

Intravenous immunoglobulin for treatment of hospitalized COVID-19 patients: an evidence mapping and meta-analysis - Mei-xuan Li; Yan-fei Li; Xin Xing; Jun-qiang Niu; Liang Yao; Meng-ying Lu; Ke Guo; Mi-na Ma; Xiao-tian Wu; Ning Ma; Dan Li; Zi-jun Li; et al. (Inflammopharmacology, 2024)

Quantitative contribution of cryogenic vacuum extraction and radial water transport to xylem-source water deuterium offsets - Yue Li; Xianfang Song; Lixin Wang; Matthias Sprenger; Ying Ma (Agricultural and Forest Meteorology, 2024)

Superior reduction and immobilization of Cr(VI) in soil utilizing sulfide nanoscale zero-valent iron supported by phosphoric acid-modified biochar: Efficiency and mechanism investigation - Kaige Li; Weijie Xu; Haijiao Song; Fuxuan Bi; Yuhui Li; Zhao Jiang; Yue Tao; Jianhua Qu; Ying Zhang (Science of The Total Environment, 2024)

Spatiotemporal variability of organic carbon in streams and rivers of the Northern Hemisphere cryosphere - Ying Wang; Genxu Wang; Xiangyang Sun; Jinlong Li; Chunlin Song (Science of The Total Environment, 2024)

Soil microbial diversity and network complexity drive the ecosystem multifunctionality of temperate grasslands under changing precipitation - Changchun Zhai; Lili Han; Chao Xiong; Anhui Ge; Xiaojing Yue; Ying Li; Zhenxing Zhou; Jiayin Feng; Jingyi Ru; Jian Song; Lin Jiang; Yunfeng Yang; et al. (Science of The Total Environment, 2024)

Sesquiterpenoids from aged Artemisia argyi and their 3D-QSAR for anti-HBV activity - Yu-Ying Song; Yong-Zhi Zhou; Yun-Fen Wang; Teng-Yun Shu; Yang Feng; Min Xu; Li-Hua Su; Hai-Zhou Li (Phytochemistry, 2024)

Aspartic acid/arginine enhance the stability of gelatin emulsions - Hui-min Yan; Yu Song; Man-man Yu; Xiu-ning Yao; Wen-wen Zhang; Ying Xu; Xue-qing Li; Yu-qin Xu; Shun Fang; Jun Qi; Guo-yuan Xiong; Chao Li; et al. (Journal of Food Engineering, 2024)

Characterization of odor properties of human milk: Effect of inter-individual nutrient differences on key odor-active compounds and odor attributes - Mingguang Yu; Qinggang Xie; Han Sun; Ying Wang; Yuan Tang; Baosong Wang; Huanlu Song; Lijin Wang; Shilong Jiang; Kaifeng Li; Yongjiu Zhang; Chengdong Zheng (Food Chemistry, 2024)

Identification and characterization of an L-type lectin from obscure puffer Takifugu obscurus in response to bacterial infection - Fu-Hui Jiang; Ying Huang; Xin-Yue Yu; Li-Fan Cui; Yan Shi; Xiao-Rui Song; Zhe Zhao (Fish & Shellfish Immunology, 2024)

Membrane fouling mitigation and EPS reduction by CNTs-TiO2-PEDOT modified anode-membrane in Membrane Electro-Bioreactor (MEBR) treating mariculture wastewater - Jing Song; Yihan Li; Shihan Wang; Rui Han; Yu Ba; Ying Liu; Shengqiang Fan (Desalination, 2024)

Low temperature relaxor, polarization dynamics and energy storage properties of Ca0.28Ba0.72Nb2O6 tungsten bronze ceramics - Lei Cao; Yuanyuan Wang; Ying Yuan; Jianguo Zhu; Hadi Barzegar Bafrooei; Minmin Mao; Bing Liu; Hao Li; Dawei Wang; Zhilun Lu; Ge Wang; Kaixin Song (Chemical Engineering Journal, 2024)

On-demand detachable adhesive hydrogel based on dual dynamic covalent cross-linked with NIR/pH dual-responsive properties for diabetic wound healing - Kaize Su; Duanyu Deng; Xiaoxian Wu; Yumu Song; Ying Sun; Xu Wang; Zhen Zhang; Jinxuan Li; Zhenping Yan; Xiangcun Shang; Chen Li; Kun Zhang; et al. (Chemical Engineering Journal, 2024)

Feeding strategy determine flexible biogas via shaping microbial abundance and interaction in anaerobic digestion - Pengjie Wu; Tianyu Bai; Ying Yang; Kunyao Li; Hao Tan; Suyu Zhuang; Fuyu Song; Zuopeng Lv; Hongyu Wen; Haiying Yu (Biomass and Bioenergy, 2024)

Progression of an emission inventory of China integrating CO2 with air pollutants: A chance to learn the influence of development on emissions - Guorui Zhi; Jinhong Du; Aizhong Chen; Wenjing Jin; Na Ying; Zhihui Huang; Peng Xu; Di Wang; Jinghua Ma; Yuzhe Zhang; Jiabao Qu; Hao Zhang; et al. (Atmospheric Environment, 2024)

The clinical trajectory of peripheral blood immune cell subsets, T-cell activation, and cytokines in septic patients - Xuan Lu; Cong-Ying Song; Ping Wang; Li Li; Li-Ying Lin; Shuai Jiang; Jia-Ning Zhou; Meng-Xiao Feng; Yun-Mei Yang; Yuan-Qiang Lu (Inflammation Research, 2024)

Surveillance of COVID-19 and influenza A(H1N1) prevalence in China via medicine-based wastewater biomarkers - Xue-Ting Shao; Yan-Song Wang; Zhen-Fang Gong; Yan-Ying Li; Dong-Qin Tan; Jian-Guo Lin; Wei Pei; De-Gao Wang (Water Research, 2023)

ASC/Caspase-1-activated endothelial cells pyroptosis is involved in vascular injury induced by arsenic combined with high-fat diet - Qiang Su; Meng Li; Lingling Yang; Linhua Fan; Penghui Liu; Xiaodong Ying; Yannan Zhao; Xiaolin Tian; Fengjie Tian; Qian Zhao; Ben Li; Yi Gao; et al. (Toxicology, 2023)

Marine chlorophyll-a prediction based on deep auto-encoded temporal convolutional network model - Chen Ying; Li Xiao; Zhao Xueliang; Song Wenyang; Xu Chongxuan (Ocean Modelling, 2023)

Effects of NH+4 concentration on the vaterite formation via direct carbonation use waste carbide slag under the different ammonium systems - Xuewen Song; Yuxin Tuo; Ying Liang; Ziwei Tang; Mingfei Li; Xinrui Hua; Renhe Yang; Xianzhong Bu; Xianping Luo (Journal of Environmental Chemical Engineering, 2023)

The crucial elements for lettuce (Lactuca sativa L.) growth under DMA stress and the linkage with DMA behavior: A new application of ionome - Yang Song; Yang Liu; Haipu Li; Ying Fang; Denglong Lu; Zhaoguang Yang (Journal of Environmental Management, 2023)

Dietary pectin attenuates Salmonella typhimurium-induced colitis by modulating the TLR2-NF-κB pathway and intestinal microbiota in mice - Jun Li; Jun Bai; Zhuan Song; Yun Ji; Zhaohui Chen; Ying Yang; Zhenlong Wu (Food and Chemical Toxicology, 2023)

Construction of a synthetic microbial community based on multiomics linkage technology and analysis of the mechanism of lignocellulose degradation - Jinmeng Chen; Yafan Cai; Zhi Wang; Zhengzhong Xu; Jia Li; Xiaotian Ma; Wei Zhuang; Dong Liu; Shilei Wang; Andong Song; Jingliang Xu; Hanjie Ying (Bioresource Technology, 2023)

Effects of Mixed Cropping on Sugarcane Growth and the Community of Arbuscular Mycorrhizal Fungi - Ying-Jie Nong; Qian Wang; Juan Song; Jin-Lian Zhang; Xiao-Juan Qin; Yi-Hao Kang; Xiang-Hua Wei; Ting-Su Chen; Yang-Rui Li (Sugar Tech, 2023)

scAAV9-VEGF alleviates symptoms of amyotrophic lateral sclerosis (ALS) mice through regulating aromatase - Ying Wang; Shuo Sun; Jingxu Zhai; Yuanyuan Liu; Chaoyuan Song; Cuimei Sun; Qiang Li; Jianqiang Liu; Hong Jiang; Yaling Liu (Experimental Brain Research, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Lead exposure induces neuronal apoptosis via NFκB p65/RBBP4/Survivin signaling pathway - Hui Chen; Wei Zhang; Song Luo; Yanshu Li; Qian Zhu; Yongli Xia; Hong Tan; Ying Bian; Yaobing Li; Jianmin Ma; Wei Chen; Xietian Luo; et al. (Toxicology, 2023)

Shifting of nutrient limitation dominates the recovery of aboveground net primary productivity of mixed forests in northeastern China after selective logging - Zhaopeng Song; Hongyan Liu; Jihua Hou; Yanhong Liu; Ying Li; Liang Shi; Jing Cao (Science of The Total Environment, 2023)

Monitoring and detecting coal miners' fatigue status using MPA-LSSVM in the vision of smart mine - Ying Chen; Caiwu Lu; Shuicheng Tian; Qinghua Gu; Song Jiang; Xinhong Li; Yuan Zou (Process Safety and Environmental Protection, 2023)

Unravelling chilling-stress resistance mechanisms in endangered Mangrove plant Lumnitzera littorea (Jack) Voigt - Xinhui Xia; Lulu Hao; Yifei Sun; Yiqing Lv; Yihong Wang; Haiyu Wu; Zongjin Jiang; Xinru Li; Yuhan Yan; Xiaojian Chen; Binghou Li; Hao Li; et al. (Marine Environmental Research, 2023)

Effect of regulating dissolved oxygen concentration in pulp with aerated gas on pyrite flotation - Ximei Luo; Wen Yang; Shuming Wen; Qiqiang Lin; Dayong Wei; Chao Li; Ying Zhang; Zhenguo Song; Yunfan Wang (Minerals Engineering, 2023)

Changes in soil organic carbon stocks of forestlands and grasslands on the Loess Plateau, 1980–2015 - Gang Li; Shaobo Sun; Nan Lu; Rong Huang; Jianwu Yan; Fan Song; Jichang Han; Ying Wang (Journal of Cleaner Production, 2023)

Organophosphate esters (OPEs) in a heavily polluted river in South China: Occurrence, spatiotemporal trends, sources, and phase distribution - Yi-Shan Liu; Hui-Ru Li; Zhi-Lang Lao; Sheng-Tao Ma; Zi-Cong Liao; Ai-Min Song; Ming-Yang Liu; You-Sheng Liu; Guang-Guo Ying (Environmental Pollution, 2023)

Phosphorus fertilization affects litter quality and enzyme activity in a semiarid grassland - Jirui Gong; Xuede Dong; Xiaobing Li; Kexin Yue; Jiayu Shi; Liangyuan Song; Zihe Zhang; Weiyuan Zhang; Ying Li (Plant and Soil, 2023)

Genetic Architecture and Functional Implications of the CSF-Contacting Nucleus - Siyuan Song; Yumin Yuan; Lingling Xu; Jun Jiang; Ying Li; Yao Yan; Qing Li; Fang Zhou; Junli Cao; Licai Zhang (Neuroscience Bulletin, 2023)
We previously identified a unique nucleus, the cerebrospinal fluid (CSF)-contacting nucleus. This study aims to understand its gene architecture and preliminarily suggest its functions. The results showed that there were about 19,666 genes in this nucleus, of which 913 were distinct from the dorsal raphe nucleus (non-CSF contacting). The top 40 highly-expressed genes are mainly related to energy metabolism, protein synthesis, transport, secretion, and hydrolysis. The main neurotransmitter is 5-HT. The receptors of 5-HT and GABA are abundant. The channels for Cl – , Na + , K + , and Ca 2+ are routinely expressed. The signaling molecules associated with the CaMK, JAK, and MAPK pathways were identified accurately. In particular, the channels of transient receptor potential associated with nociceptors and the solute carrier superfamily members associated with cell membrane transport were significantly expressed. The relationship between the main genes of the nucleus and life activities is preliminarily verified.

Customized fluorescent probe for peering into the expression of butyrylcholinesterase in thyroid cancer - Wenxin Kang; Mo Ma; Lanlan Xu; Shuai Tang; Jingkang Li; Pinyi Ma; Daqian Song; Ying Sun (Analytica Chimica Acta, 2023)

Association between long-term exposure to low level air pollutants and incident end-stage kidney disease in the UK Biobank: A prospective cohort - Jing Li; Liang Dai; Xiaowei Deng; Jingwen Zhang; Congying Song; Junjie Xu; Anxin Wang; Zuying Xiong; Ying Shan; Xiaoyan Huang (Chemosphere, 2023)

Late-Permian subduction-to-collision transition and closure of Paleo-Asian Ocean in eastern Central Asian Orogenic Belt: Evidence from borehole cores in the Songliao Basin, Northeast China - Haihua Zhang; Liang Qiu; Dan-Ping Yan; Zifu Zhao; Keda Cai; Jian Zhang; Shuwang Chen; Yongfei Li; Ying Song; Yuejuan Zheng; Shouliang Sun; Fanhao Gong; et al. (Gondwana Research, 2023)

Polydopamine-coated HKUST MOFs-based strip lateral flow immunoassay for on-site ultrasensitive detection of aflatoxin B1 in foods - Wenjuan Wu; Ying Li; Qingbin Xu; Nan Long; Pengyue Song; Jiabo Wang; Lidong Zhou; Bin Fu; Weijun Kong (Food Control, 2023)

Combining HUMSC secretome and a conductive hydrogel enhances angiogenesis and electrical transmission at myocardial infarct sites to support cardiac repair - Shu-yi He; Lin-yu Long; Zhi-cun Wang; Wen-qi Liu; Wen Zhang; Cheng Hu; Xiao-feng Wu; Ruiqi Dong; Hong-song Fan; Qing-Jiang; Ying-ying Tong; Guang-hua Yang; et al. (Chemical Engineering Journal, 2023)

An abradable and anti-corrosive CuAl-Ni/C seal coating for aero-engine - Hui Yan; Yingjie Yu; Yuanfang Song; Bing Lei; Yumeng Ni; Ao Tang; Ying Li (Chemical Engineering Journal, 2023)

Temperature-dependent NO2/diisopropylamine sensor based on SnO2 squama-wrapped tubes derived from waste bamboo shoot skin - Bao-Yu Song; Cong Chen; Ya-Nan Li; Xian-Fa Zhang; Xiao-Li Cheng; Zhao-Peng Deng; Ying-Ming Xu; Li-Hua Huo; Shan Gao (Chemical Engineering Journal, 2023)

cPKCγ-Modulated Autophagy Contributes to Ischemic Preconditioning–Induced Neuroprotection in Mice with Ischemic Stroke via mTOR-ULK1 Pathway - Ying Zhang; Longhui Ma; Yi Yan; Li Zhao; Song Han; Di Wu; Cesar V. Borlongan; Junfa Li; Xunming Ji (Translational Stroke Research, 2023)

Multi-valent mRNA vaccines against monkeypox enveloped or mature viron surface antigens demonstrate robust immune response and neutralizing activity - Niubing Zhang; Xiang Cheng; Yilong Zhu; Ouyang Mo; Huiqing Yu; Liqi Zhu; Juan Zhang; Linlin Kuang; Ying Gao; Ruiyuan Cao; Xiaozhen Liang; Haikun Wang; et al. (Science China Life Sciences, 2023)

Prediction of seawater pH by bidirectional gated recurrent neural network with attention under phase space reconstruction: case study of the coastal waters of Beihai, China - Chongxuan Xu; Ying Chen; Xueliang Zhao; Wenyang Song; Xiao Li (Acta Oceanologica Sinica, 2023)

Tigliane-and daphnane-type diterpenoids from the buds of Daphne genkwa with their cytotoxic activities - Ying Chen; Cai-Lin Zhao; Wei Dong; Fei-Fan Song; Li-Na Guo; Hong-Lian Zhang; Lv Zhen; Li Li; Jin Ye; Bo Song (Natural Product Research, 2023)

Dynamic valuation of the provisioning services of marine fisheries ecosystem based on BeiDou VMS data: A case study of TACs project for Acetes chinensis in the Yellow Sea - Guodong Li; Dongjia Li; Ying Xiong; Xiaming Zhong; Jinjin Shi; Hushun Zhang; Dade Song; Fan Yang; Zhongjie Kang; Xiaorui Wu; Shuyan Wang; Long Liang (Ocean & Coastal Management, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Dammarane-type saponins from Gynostemma pentaphyllum and their anti-aging activities via up-regulating mitochondria related proteins - Hai-Zhen Liang; Peng-Xin Lu; Li-Li Chu; Gang Li; Chuan-Biao Li; Xiao-Juan Chen; Jie Zhang; Juan Song; Tao Zhang; Ying Luo; Ying Hu; Bai-Ping Ma (Phytochemistry, 2023)

Electronic modulation and surface reconstruction on heterostructured CoP-Ni2P nanosheets with phosphate-rich surface for synergistically triggering oxygen evolution reaction - Fei Nie; Xueli Yin; Yihua Cao; Zhi Li; Xiaoping Dai; Weiyu Song; Yujie Liu; Yonghao Gan; Ying Ye; Run Cai; Xin Zhang (Fuel, 2023)

Plant facilitation improves carbon production efficiency while reducing nitrogen input in semiarid agroecosystem - Wei Wang; Meng-Ying Li; Shuang-Guo Zhu; Aziz Khan; Xiu-Ping Tao; Guang-Fu Huang; Hai-Ying Liu; Wei Zhang; Hong-Yan Tao; Dong-Shan Gong; Chao Song; You-Cai Xiong (CATENA, 2023)

Biocrust mediates the complexity and stability of bacterial networks in both biocrust and subsoil layers in the Tengger Desert - Song Guang; Zheng Ying; Yang Haotian; Li Xinrong (Plant and Soil, 2023)

Integration of eQTL and GWAS analysis uncovers a genetic regulation of natural ionomic variation in Arabidopsis - Chaoqun Xu; Ling-Yu Song; Ying Zhou; Dong-Na Ma; Qian-Su Ding; Ze-Jun Guo; Jing Li; Shi-Wei Song; Lu-Dan Zhang; Hai-Lei Zheng (Plant Cell Reports, 2023)

Spautin-1 Protects Against Mild TBI-Induced Anxiety-Like Behavior in Mice via Immunologically Silent Apoptosis - Hui-Tao Miao; Rong-Xin Song; Yue Xin; Lu-Ying Wang; Jin-Meng Lv; Na-Na Liu; Zhi-You Wu; Wei Zhang; Yan Li; Dong-Xue Zhang; Li-Min Zhang (NeuroMolecular Medicine, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Metal-organic framework (MOF)-based sensors for exogenous contaminants in food: Mechanisms, advances, and prospects - Wenjuan Wu; Ying Li; Pengyue Song; Qingbin Xu; Nan Long; Peng Li; Lidong Zhou; Bin Fu; Jiabo Wang; Weijun Kong (Trends in Food Science & Technology, 2023)

New α-pyrone and unsaturated ketone analogues from the endophytic fungus Lasiodiplodia sp. and their cytotoxic effects - Wei Dong; Wen-Bin Gao; Fan-Wei Liu; Jin-Ye; Ying Chen; Hong-Lian Zhang; Zhen Lv; Li-Na Guo; Bo Song (Phytochemistry Letters, 2023)

Rational design of anti-interference Fe/Co MOF-coupled PMS process for As(III) removal in DOM-rich groundwater: 1O2-dominated As(III) oxidation and chemisorption of As(V) - Ying Fang; Qianwen Liu; Yang Song; Feiyue Jia; Ying Yang; Haipu Li (Chemical Engineering Journal, 2023)

Thrombospondin-2 Couples Pressure-Promoted Chondrogenesis through NF-κB Signaling - Jing Niu; Fan Feng; Songbai Zhang; Yue Zhu; Runfang Song; Junrong Li; Liang Zhao; Hui Wang; Ying Zhao; Min Zhang (Tissue Engineering and Regenerative Medicine, 2023)

Integrative Identification by Hi-C Revealed Distinct Advanced Structural Variations in Lung Adenocarcinoma Tissue - Tingting Song; Menglin Yao; Ying Yang; Zhiqiang Liu; Li Zhang; Weimin Li (Phenomics, 2023)

In-situ detection equipment for radon-in-water: unattended operation and monthly investigations - Chunqian Li; Meng Li; Guangquan Chen; Huaming Yu; Chenglun Zhang; Wen Liu; Jinjia Guo; Shibin Zhao; Lijun Song; Xiliang Cui; Ying Chai; Lu Cao; et al. (Acta Oceanologica Sinica, 2023)

Green organic-inorganic coatings for flexible polyurethane foams: Evaluation of the effects on flame retardancy, antibacterial activity, and ideal mechanical properties - Ping Li; Xu-Chen Jiang; Wan-Meng Song; Li-Yao Zhang; Ying-Jun Xu; Yun Liu; Ping Zhu (Journal of Cleaner Production, 2023)

Physicochemical, structural, and functional properties of microfluidic modified dietary fiber from fresh corn bracts - Ningning Geng; Hongjuan Wang; Yan Zhang; Jiangfeng Song; Ying Li; Caie Wu (Journal of Cereal Science, 2023)

Effect of boiling on texture of scallop adductor muscles and its mechanism based on label-free quantitative proteomic technique - Zi-Xuan Wu; Yan-Hong Bai; Zi-Ye Wang; Ying-Chen Fan; Liang Song; Yu-Xin Liu; De-Yang Li; Peng-Fei Jiang; Da-Yong Zhou (Food Chemistry, 2023)

A callus-derived regeneration and Agrobacterium-mediated gene transformation developed for bilberry, Vaccinium myrtillus - Yanping Song; Wenbo Luo; Ying Wu; Xiaojie Li; Nick W. Albert; Yinhai Zhang; Xiangtao Chen; Kui Lin-Wang; Cecilia H. Deng; Zhubing Hu; Bingsong Zheng; Xiaofei Wang; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Associations of long-term joint exposure to various ambient air pollutants with all-cause and cause-specific mortality: evidence from a large population-based cohort study - Zhi-Hao Li; Xiao-Meng Wang; Jia-Xuan Xiang; Ying Nan; Ying-Jun Chen; Pei-Dong Zhang; Dan Liu; Dong Shen; Xi-Ru Zhang; Wen-Fang Zhong; Pei-Liang Chen; Qing-Mei Huang; et al. (Environmental Science and Pollution Research, 2023)

Association between short-term exposure to ambient air pollution and outpatient visits for pulpitis in Hefei, China: a time series study - Wuli Li; Xirun Zong; Yi-Sheng He; Tiantian Meng; Ying Tang; Qi Yang; Qing Huang; Yuanyin Wang; Song Li; Hai-Feng Pan (Environmental Science and Pollution Research, 2023)

Controllable synthesis of yellow emissive carbon dots by mild heating process and their utility as fluorescent test paper for detection of mercury(II) ions assistants by smartphone - Yunqi Hao; Ying Song; Tingting Li; Yuzhuo Tuo; Miaomiao Tian; Fang Chai (Journal of Environmental Chemical Engineering, 2023)

Salinity variations of the inner Yangtze Sea during the Ordovician-Silurian transition and its influences on marginal marine euxinia - Guangyao Cao; Yu Liu; Chao Li; Ping'an Peng; Mingcai Hou; Gary G. Lash; Xiaolin Zhou; Yuanchun Li; Ying Song (Global and Planetary Change, 2023)

PSS modified by 3-aminopropyltrimethoxysilane linking large-area GNPs/PSS to silicone rubber with stable interface combination for high sensitivity flexible resistive sensor - Han Feng; Ping Liu; Xu Guo; Junliang Li; Yifan Sun; Shunge Wu; Ruohai Hu; Zhi Liu; Helei Tian; Yuanming Ma; Caixia Liu; Houzhu Huang; et al. (Chemical Engineering Journal, 2023)

Social and paternal female choice for male MHC genes in golden snub‐nosed monkeys ( Rhinopithecus roxellana ) - Pei Zhang; Bingyi Zhang; Derek W. Dunn; Xiaoyue Song; Kang Huang; Shixuan Dong; Fei Niu; Meijing Ying; Yingying Zhang; Yixin Shang; Ruliang Pan; Baoguo Li (Molecular Ecology, 2023)
Genes of the major histocompatibility complex (MHC) play important roles in vertebrate immunocompetence. MHC genes thus offer females indirect benefits to mate choice through the production of offspring of an optimal MHC genotype. Females may choose males with specific MHC haplotypes, dissimilar MHC genotypes, MHC heterozygous males or MHC‐diverse males. We tested these four alternatives for both female social and paternal choice in wild golden snub‐nosed monkeys ( Rhinopithecus roxellana ) by examining overall genetic variability (via microsatellites) and four MHC‐genes ( DRB1 , DRB2 , DQA1 and DQB1 ). Monte Carlo randomization tests showed that MHC dissimilarity was favoured for social choice (males to which females were socially affiliated) and intermediate MHC dissimilarity was favoured in paternal choice (fathers of offspring). No evidence of inbreeding avoidance was found for either social or paternal mates. We found that MHC heterozygotes, higher microsatellite multilocus heterozygosity and higher microsatellites diversity were favoured for social mates, and higher microsatellite diversity was favoured for paternal mates. Independent of male age, we found that the formation of male–female social pairings is significantly predicted by compatibility based on the sharing of MHC haplotypes. However, we found no evidence of independent genetic effects on the duration of male–female social pairings, male social status (achieving OMU leader male status or not), the number of females with which individual leader males paired, the likelihood of potential male–female pairings producing offspring, or whether males fathered offspring or not. Overall, our findings suggest different genetic factors are involved in social and paternal choice in R. roxellana .

Changes in overwintering ground of small yellow croaker ( Larimichthys polyactis ) based on MaxEnt and GARP models: A case study of the southern Yellow Sea stock - Guodong Li; Ying Xiong; Xiaming Zhong; Dade Song; Zhongjie Kang; Dongjia Li; Jianhua Tang; Yanping Wang; Lei Wu (Journal of Fish Biology, 2023)
Small yellow croaker ( Larimichthys polyactis ), a commercially essential fish commonly caught in China and South Korea, is now facing a severe decline in resources. The recruitment and surplus of L. polyactis depend selecting a suitable marine environment for overwintering. However, the international overwintering migration habit of L. polyactis limits the investigation of its overwintering environment preferences and suitable grounds. In this study, based on the distribution data of L. polyactis in the southern Yellow Sea in winter from 2010 to 2019 and ocean remote sensing data such as sea bottom temperature (SBT), sea bottom salinity, chlorophyll‐a concentration and water depth (Depth), we used the maximum entropy (MaxEnt) and the genetic algorithm for rule‐set production (GARP) models to investigate the overwintering grounds of the southern Yellow Sea stock (SYS). The jackknife test was used to assess the importance of various environmental factors. For modelling the overwintering ground distribution of SYS, the area under the curve values of both models ​were higher than 0.9. The overwintering ground was at 32°10′ N–33°48′ N, 122°30′ E–125°00′ E. The direction of its distribution was consistent with the Yellow Sea Warm Current in the southern Yellow Sea during the winter. Compared with the suitable overwintering area during 2010–2014, the highly appropriate overwintering area for SYS to overwinter decreased significantly during 2015–2019, showing a trend of moving to the east and north, related to the increase in fishing pressure and strengthening of the Yellow Sea Warm Current in recent years. Depth was the most significant factor for SYS overwintering, followed by SBT. The overwintering ground was at a depth of 40–65 m during the two periods. Additionally, the suitability of overwintering grounds in the coastal waters of south‐western South Korea has gradually increased. This study provides a scientific basis for formulating effective strategies to manage L. polyactis resources under the China–South Korea Fisheries Agreement.

Pentacyclic triterpenoids from spikes of Prunella vulgaris L. with thyroid tumour cell cytostatic bioactivities - Xiu-Qin Zheng; Lei-Xin Song; Zhu-Zhen Han; Ying-Bo Yang; Yi Zhang; Li-Hua Gu; Li Yang; Gui-Xin Chou; Zheng-Tao Wang (Natural Product Research, 2023)

Uptake, accumulation, and translocation of organophosphate esters and brominated flame retardants in water hyacinth (Eichhornia crassipes): A field study - Huiru Li; Zhilang Lao; Yishan Liu; Yufei Feng; Aimin Song; Junjie Hu; Zicong Liao; Longwei Zhang; Mingyang Liu; Yousheng Liu; Guang-Guo Ying (Science of The Total Environment, 2023)

Combining mechanisms of black carbon and magnetic minerals in power plant fly ash - Meng Yao Li; Zhou Xin Peng; You Ying Chen; Shi Yun Xiao; Bo Wen Zhang; Yi Xin Shen; Sheng Kang Wang; Xue Song Wang; Zhao Xiang Han (Science of The Total Environment, 2023)

Insight into the underwater implosion mechanisms of thin-walled metallic cylindrical shells - Song Liu; Zhixin Huang; Ying Li (Ocean Engineering, 2023)

Plasma metallomics reveals potential biomarkers and insights into the ambivalent associations of elements with acute myocardial infarction - Si Ying Lim; Hiranya Dayal; Song Jie Seah; Regina Pei Woon Tan; Zhi En Low; Anna Karen Carrasco Laserna; Sock Hwee Tan; Mark Y. Chan; Sam Fong Yau Li (Journal of Trace Elements in Medicine and Biology, 2023)

Low-temperature and dual-sensing NO2/dimethylamine sensor based on single-crystal WO3 nanoparticles-supported sheets synthesized by simple pyrolysis of spoiled WCl6 powder - Guo-Li Chen; Ming-Song Lv; Li-Li Sui; Zhao-Peng Deng; Ying-Ming Xu; Li-Hua Huo; Shan Gao (Chemical Engineering Journal, 2023)

Kidney tea ameliorates hyperuricemia in mice via altering gut microbiota and restoring metabolic profile - Ye Chen; Chaoying Pei; Ying Chen; Xiaoyi Xiao; Xingyuan Zhang; Kaiwei Cai; Song Deng; Rongyao Liang; Zhiyong Xie; Pei Li; Qiongfeng Liao (Chemico-Biological Interactions, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

A simple and efficient protocol for transient transformation of sliced grape berries - Mao-Song Pei; Hai-Nan Liu; Charles Ampomah-Dwamena; Tong-Lu Wei; Yi-He Yu; Jia-Bing Jiao; Ying-Ying Lv; Feng Li; Hong-Chao Li; Xue-Jie Zhu; Da-Long Guo (Protoplasma, 2023)

Valorization of food waste digestate to ash and biochar composites for high performance adsorption of methylene blue - Caiyun Yang; Hao Wu; Mengyu Cai; Yanghongmiao Li; Chunyu Guo; Ying Han; Yingchao Zhang; Bing Song (Journal of Cleaner Production, 2023)

Bicarbonate-mediated enhanced successive oxidation and adsorption of As(III) in heterogeneous PMS activation process: Mechanism and practicability - Ying Fang; Huihan Xie; Ying Yang; Yang Song; Zhaoguang Yang; Haipu Li (Journal of Environmental Chemical Engineering, 2023)

Antibiotics in soil and water: Occurrence, fate, and risk - Wei-Li Jia; Chao Song; Liang-Ying He; Ben Wang; Fang-Zhou Gao; Min Zhang; Guang-Guo Ying (Current Opinion in Environmental Science & Health, 2023)

CO2-induced reconstruction for ORR-enhanced solid oxide fuel cell cathode - Yuan Zhang; Junbiao Li; Heping Xie; Zhipeng Liu; Suling Shen; Ying Teng; Daqin Guan; Shuo Zhai; Yufei Song; Wei Zhou; Bin Chen; Meng Ni; et al. (Chemical Engineering Journal, 2023)

Structural characterization and anti-osteoporosis effects of polysaccharide purified from Eucommia ulmoides Oliver cortex based on its modulation on bone metabolism - Jiyu Song; Yongfeng Zhang; Yanfeng Zhu; Xinghui Jin; Lanzhou Li; Chunyue Wang; Ying Zhou; Yutong Li; Di Wang; Min Hu (Carbohydrate Polymers, 2023)

Growth of winter wheat adapting to climate warming may face more low‐temperature damage - Yanling Song; Guangsheng Zhou; Hans W. Linderholm; Junfang Wang; Yong Li; Guofu Wang; Yan Fu; Jinxia Xu; Ying Shi; Ying Xu; Hui Gao; Deliang Chen (International Journal of Climatology, 2023)
China's surface air temperature is increasing due to global warming, so it is interesting that how low temperatures would be changed during the growth period of winter wheat in future. We focused on the low temperatures of winter wheat from 2021 to 2050, using temperatures under the high emission scenario Representative Concentration Pathway 8.5 (RCP8.5) projected by the RegCM4.4 regional climate model. The results showed that the annual mean temperature was projected to increase by 0.42°C⋅decade −1 in the northern and by 0.35°C⋅decade −1 in the southern winter wheat region. Furthermore, the temperature was expected to increase rapidly in spring, which could advance the dates of flowering and the start of the grain‐filling period. Using the genetic parameters determined by the calibration and validation of WOFOST and bias‐corrected projected meteorological data, simulations of winter wheat growth were performed over the winter wheat region for 2021–2050. The simulated number of days to the flowering period of winter wheat for 2041–2050 was on average 6.5 days less than in 2021–2030, due to the spring warming. Because of the earlier start of the growing season, winter wheat could face negative effects by being subjected to low temperatures. Indeed, the number of low‐temperature days was projected to increase by 110% from 2041 to 2050 compared to 2021–2030, and the number of killing degree days (KDDs) is projected to increase by 120% at the same time. If the number of days to flowering did not change, the number of low‐temperature days and KDDs only changed slightly, showing that the negative influence of low temperature was mainly caused by the advancement of the flowering date. The effect of low temperature on growth was underestimated when the response of winter wheat growth to global warming was not considered.

Genome-wide identification, structural and evolutionary characteristics, and expression analysis of aquaporin gene family members in Mercenaria mercenaria - Cong Zhou; Zhi-shu Lin; Ying Shi; Jie Feng; Zhi Hu; Mei-jie Yang; Pu Shi; Yong-ren Li; Yong-jun Guo; Tao Zhang; Hao Song (Frontiers in Marine Science, 2023)
Aquaporins (AQPs) are highly-selective transmembrane water transporters that are involved in the adaptation to environmental challenges. However, the structure, function, and evolution of AQPs in bivalves remain largely unknown. In this study, AQP gene family members were identified in nine bivalve species, and their abundance rangs from 7 to 15. Nine AQPs (MmAQPs) were identified in the genome of hard clam ( Mercenaria mercenaria ), which is a euryhaline bivalve that has evolved sophisticated osmoregulatory mechanisms and salinity adaptation. Structurally, all MmAQPs contain 6 or 12 transmembrane α-helices, a major intrinsic protein (MIP) domain, and 2 asparagine-proline-alanine (NPA) motifs. MmAQPs were classified into three subfamilies based on phylogenetic analysis: AQP1-like, AQP3-like, and AQP8-like. No AQP11-like subfamily member was identified in the genome of hard clam. Tandem duplication resulted in a lineage-specific expansion in AQP8-like subfamily in hard clams. MmAQP8 genes showed different expression sensitivity to different environmental stressors. The gene expression patterns of three MmAQP8 were similar under heat, hypoxia, and air exposure stress, but differed greatly under salinity stress, indicating that tandem duplication events may accelerate the functional divergence of AQP8 genes in hard clams. AQP3-like members may have undergone gene loss during evolution, resulting in weakened glycerol and urea penetration in hard clams. Three orthologs of MmAQPs were detected in the genomes of Cyclina sinensis and Archivesica marissinica through synteny analyses. Tissue expression profiles showed that MmAQP genes were highly expressed in the foot and hepatopancreas. Under environmental stress, the expression levels of most of the MmAQP genes changed significantly to maintain metabolic homeostasis. Several MmAQP genes were downregulated to reduce water permeability under salinity and air exposure stress. Several MmAQP genes were significantly upregulated to promote the transmembrane transport of ammonia and reactive oxygen species and activate anti-apoptotic responses to resist stress. This study provides a comprehensive understanding of the AQP gene family in hard clams, and lays a foundation for further studies to explore the functions of AQPs in bivalves.

Phosphorus application promoted the sequestration of orthophosphate within soil microorganisms and regulated the soil solution P supply in a temperate grassland in northern China: A 31P NMR study - Jiayu Shi; Jirui Gong; Xiaobing Li; Zihe Zhang; Weiyuan Zhang; Ying Li; Liangyuan Song; Siqi Zhang; Jiaojiao Dong; Taoge-tao Baoyin (Soil and Tillage Research, 2023)

Rapid expansion of wetlands on the Central Tibetan Plateau by global warming and El Niño - Yang Li; Zhengyang Hou; Liqiang Zhang; Changqing Song; Shilong Piao; Jintai Lin; Shushi Peng; Keyan Fang; Jing Yang; Ying Qu; Yuebin Wang; Jingwen Li; et al. (Science Bulletin, 2023)

Petrogenesis of the Chakabeishan pegmatites, North Qaidam Terrane: Implications for Indosinian lithium mineralization in the northern Tibetan Plateau - Jin-Heng Liu; Qiang Wang; Bing-Zhang Wang; Wu-Fu Li; Chuan-Bing Xu; Shan-Ping Li; Zi-Long Wang; Lu-Lu Hao; Tai-Zhong Song; Chun-Tao Wang; Ying Zheng; Jin-Shou Wang (Lithos, 2023)

One-step preparation of MoO /ZnS/ZnO composite and its excellent performance in piezocatalytic degradation of Rhodamine B under ultrasonic vibration - Song Zheng; Xiaojing Li; Jiayu Zhang; Junfeng Wang; Chunran Zhao; Xin Hu; Ying Wu; Yiming He (Journal of Environmental Sciences, 2023)

Nanoemulsion: A novel delivery approach for thermosensitive IgG on inhibiting milk fat oxidation - An-Qi Zhang; Meng-Qi Liu; Xiao-Yan Li; Di Xu; Yu-Qi Yin; Nan-Nan Song; Ying-Hua Zhang (Food Research International, 2023)

Extrusion production of textured soybean protein: The effect of energy input on structure and volatile beany flavor substances - Lingyu Yang; Zhiwei Ying; He Li; Jian Li; Tianyu Zhang; Yao Song; Xinqi Liu (Food Chemistry, 2023)

Application of non-Saccharomyces yeasts with high β-glucosidase activity to enhance terpene-related floral flavor in craft beer - Xiaoyu Han; Qiuxing Qin; Chenyu Li; Xiaoxuan Zhao; Fangxu Song; Mengjiao An; Ying Chen; Xiuqin Wang; Weidong Huang; Jicheng Zhan; Yilin You (Food Chemistry, 2023)

Development of a Nafion-MWCNTs and in-situ generated Au nanopopcorns dual-amplification electrochemical aptasensor for ultrasensitive detection of OTA - Yujiao Hou; Nan Long; Qingbin Xu; Ying Li; Pengyue Song; Minghan Yang; Jiabo Wang; Lidong Zhou; Ping Sheng; Weijun Kong (Food Chemistry, 2023)

Immunosensing of neuron-specific enolase based on dual signal amplification strategy via electrocatalytic oxygen reduction by iron-porphyrin covalent organic framework - Huihui Liang; Ying Luo; Yawen Xiao; Jianhui Xiong; Rongfang Chen; Yonghai Song; Li Wang (Chemical Engineering Journal, 2023)

Anammox upflow hybrid reactor: Nitrogen removal performance and potential for phosphorus recovery - Ying Song; Jialing Ni; Yan Guo; Kengo Kubota; Wei-Kang Qi; Yu-You Li (Chemosphere, 2023)

Oxidative treatment of NOM by selective oxidants in drinking water treatment and its impact on DBP formation in postchlorination - Juan Li; Yang Song; Jin Jiang; Tao Yang; Ying Cao (Science of The Total Environment, 2023)

Coumaronochromones, flavanones, and isoflavones from the twigs and leaves of Erythrina subumbrans inhibit PTP1B and nitric oxide production - Cai-Ying Liu; Pan Deng; Bin Wang; Ai-Hong Liu; Meng-Ge Wang; Song-Wei Li; Li-Li Chen; Shui-Chun Mao (Phytochemistry, 2023)

Anti-bacterial robust Ag@PDA/PEN electrospinning nanofibrous membrane for oil-water separation - Pan Wang; Mengxue Wang; Tao Song; Jiaqi Chen; Xidi Liu; Xiaoyang Liu; Yong You; Huijin Song; Kui Li; Ying Li; Wei Feng; Xulin Yang (Journal of Water Process Engineering, 2023)

Microplastics reduce nitrogen uptake in peanut plants by damaging root cells and impairing soil nitrogen cycling - Yiyang Liu; Fangji Xu; Liping Ding; Guanchu Zhang; Bo Bai; Yan Han; Lina Xiao; Yan Song; Ying Li; Shubo Wan; Guowei Li (Journal of Hazardous Materials, 2023)

Activity enhancement of core–shell Pd@mCeO2 catalysts for phenol hydrogenation to cyclohexanone by tuning metal-support interactions - Defu Yin; Renjie Ji; Jingyun Zhang; Shitao Yu; Lu Li; Shiwei Liu; Long Jiang; Ying Liu; Zhanqian Song; Yue Liu (Fuel, 2023)

Granitic record of the assembly of the Asian continent - Tao Wang; Ying Tong; He Huang; Hongrui Zhang; Lei Guo; Zhengxiang Li; Xiaoxia Wang; Bruce Eglington; Shan Li; Jianjun Zhang; Tatiana V. Donskaya; Oleg Petrov; et al. (Earth-Science Reviews, 2023)

Highly efficient in-situ purification of Fe(II)-rich high-arsenic groundwater under anoxic conditions: Promotion mechanisms of PMS on oxidation and adsorption - Ying Fang; Qianwen Liu; Yang Song; Hui Cai; Ying Yang; Zhaoguang Yang; Haipu Li (Chemical Engineering Journal, 2023)

Engineering electron redistribution of bimetallic phosphates with CeO2 enables high-performance overall water splitting - Xin Guo; Menggang Li; Longyu Qiu; Fenyang Tian; Lin He; Shuo Geng; Yequn Liu; Ying Song; Weiwei Yang; Yongsheng Yu (Chemical Engineering Journal, 2023)

Increased Soluble Epoxide Hydrolase Activity Positively Correlates with Mortality in Heart Failure Patients with Preserved Ejection Fraction: Evidence from Metabolomics - Liyuan Peng; Ziping Song; Chengcheng Zhao; Kudusi Abuduwufuer; Yanwen Wang; Zheng Wen; Li Ni; Chenze Li; Ying Yu; Yi Zhu; Hualiang Jiang; Jinshan Shen; et al. (Phenomics, 2023)

Correction to: Microplastic pollution and its impact on marine microbes in Zhanjiang, China - Qing-Lang Song; Fang-Hong Nie; Di-Hua Zhu; Yun-Li Wei; Min Zhang; Yao Hu; Meng-Meng Chen; Dan-Ju Kang; Zhi-Bao Chen; Hong-Ying Lin; Jin-Jun Chen (Journal of Coastal Conservation, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Spatiotemporal transitions of organophosphate esters (OPEs) and brominated flame retardants (BFRs) in sediments from the Pearl River Delta, China - Zhilang Lao; Huiru Li; Zicong Liao; Yishan Liu; Guangguo Ying; Aimin Song; Mingyang Liu; Hehuan Liu; Lixin Hu (Science of The Total Environment, 2023)

Sedimentary dinoflagellate cyst records of human-induced environmental changes in Daya Bay, the northern South China Sea - Ping-Ping Shen; Ying Li; Ya-Nan Tang; Qing-Shang Song; Yue Xue (Journal of Marine Systems, 2023)

Polybrominated dibenzo-p-dioxins/furans and their chlorinated analogues in sediments from a historical hotspot for both brominated flame retardants and organochlorine pesticides - Mingyang Liu; Huiru Li; Aimin Song; Ping'an Peng; Hehuan Liu; Jianfang Hu; Guoying Sheng; Guangguo Ying (Environmental Pollution, 2023)

Natural sedimentation-assisted fabrication of Janus functional films for versatile applications in Joule heating, electromagnetic interference shielding and triboelectric nanogenerator - Weiyan Li; Zhongqian Song; Ying He; Jizhen Zhang; Yu Bao; Wei Wang; Zhonghui Sun; Yingming Ma; Zhenbang Liu; Li Niu (Chemical Engineering Journal, 2023)

Structural characterization of SARS-CoV-2 dimeric ORF9b reveals potential fold-switching trigger mechanism - Xiyue Jin; Xue Sun; Yan Chai; Yu Bai; Ying Li; Tianjiao Hao; Jianxun Qi; Hao Song; Catherine C. L. Wong; George F. Gao (Science China Life Sciences, 2023)

Impacts of mowing and N addition on soil organic phosphorus mineralization rates in a semi-natural grassland in Northeast China - Haiying Cui; Mingcai Fan; Yunbo Wang; Xiaochong Zhang; Wanling Xu; Yanan Li; Wenzheng Song; Jian-Ying Ma; Wei Sun (Plant and Soil, 2023)

IL-18BP Alleviates Anxiety-Like Behavior Induced by Traumatic Stress via Inhibition of the IL-18R-NLRP3 Signaling Pathway in a Mouse Model of Hemorrhagic Shock and Resuscitation - Li-Min Zhang; Dong-Xue Zhang; Rong-Xin Song; Jin-Meng Lv; Lu-Ying Wang; Zhi-You Wu; Hui-Tao Miao; Yan-Bo Zhou; Wei Zhang; Yue Xin; Yan Li (Molecular Neurobiology, 2023)

Effect of divalent cations on electrochemiluminescence of metal-organic frameworks in bioassay - Xuyu Feng; Bin Li; Longyi Zhu; Wen Chen; Ying Wu; Yanru Duan; Meiyan Song; Ying Wan; Shengyuan Deng (Analytica Chimica Acta, 2023)

Evaluation of housekeeping genes as references for quantitative real‐time PCR analysis of European eel, Anguilla anguilla - Ying‐Ying Li; Xi Chen; Jin‐Xian Yang; Qiang Chen; Tie‐Ying Song; Jun‐Qing Ge (Journal of Fish Biology, 2023)
Eels are important aquaculture species for which an increasing number of reference genes are being identified and applied. In this study, five housekeeping genes [RPL7 (ribosomal protein L7), 18 S (18 S ribosomal RNA), EF1A (elongation factor 1α), ACTB (β‐actin) and GAPDH (glyceraldehyde‐3‐phosphate dehydrogenase)] were chosen to evaluate their reliability as reference genes for quantitative real‐time PCR (qPCR) for the study of Anguilla anguilla . The expression of the selected genes in different eel tissues was determined using qPCR at different growth stages or upon challenge by Anguillid herpesvirus (AngHV), and the expression levels of these genes were then compared and evaluated using the geNorm and NormFinder algorithms. Then, RefFinder was used to comprehensively rank the examined housekeeping genes. Interestingly, the expression of the evaluated housekeeping genes exhibited tissue‐dependent and treatment‐dependent variations. In different growth periods A. anguilla tissues, the most stable genes were the following: ACTB in mucus; 18 S in skin and kidney; RPL7 in muscle, gill, intestine and brain; EF1A in heart and liver; and GAPDH in spleen. In contrast, in AngHV‐challenged A. anguilla tissues, the most stable genes were the following: 18 S in mucus; RPL7 in skin, gill, heart, spleen, kidney and intestine; EF1A in muscle and liver; and ACTB in brain. Further comparison analysis indicated that the expression of RPL7 and EF1A was stable in multiple A. anguilla tissues in different growth periods and in eels challenged by AngHV. Nonetheless, the expression level of GAPDH in eel tissues was lower, and it was unstable in several tissues. These results indicated that the selection of reference genes for qPCR analysis in A. anguilla should be made in accordance with experimental parameters, and both RPL7 and EF1A could be used as reference genes for qPCR study of A. anguilla at different growth stages or upon challenge by AngHV. The reference genes identified in this study could improve the accuracy of qPCR data and facilitate further studies aimed at understanding the biology of eels.

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

Microplastic pollution and its impact on marine microbes in Zhanjiang, China - Qing-Lang Song; Fang-Hong Nie; Di-Hua Zhu; Yun-Li Wei; Min Zhang; Yao Hu; Meng-Meng Chen; Dan-Ju Kang; Zhi-Bao Chen; Hong-Ying Lin; Jin-Jun Chen (Journal of Coastal Conservation, 2022)

Higher pH is associated with enhanced co‐occurrence network complexity, stability and nutrient cycling functions in the rice rhizosphere microbiome - Yaping Guo; Bin Song; Anqi Li; Qi Wu; Haili Huang; Na Li; Ying Yang; Jonathan Miles Adams; Lin Yang (Environmental Microbiology, 2022)
The rice rhizosphere microbiota is crucial for crop yields and nutrient use efficiency. However, little is known about how co‐occurrence patterns, keystone taxa and functional gene assemblages relate to soil pH in the rice rhizosphere soils. Using shotgun metagenome analysis, the rice rhizosphere microbiome was investigated across 28 rice fields in east‐central China. At higher pH sites, the taxonomic co‐occurrence network of rhizosphere soils was more complex and compact, as defined by higher average degree, graph density and complexity. Network stability was greatest at medium pH (6.5

Synergistic impacts of westerlies and monsoon on interdecadal variations of late spring precipitation over the southeastern extension of the Tibetan Plateau - Jing Wang; Yanju Liu; Chengyu Song; Yihui Ding; Qiaoping Li; Ping Wu; Ying Xu; Xiangde Xu (International Journal of Climatology, 2022)
Based on multiple long‐term observational and reanalysis datasets, this study investigated the characteristics and physical mechanisms of the interdecadal variations in late spring (i.e., May) precipitation (LSP) over the southeastern extension of the Tibetan Plateau (SETP) since 1900. It was revealed that by and large, LSP over the SETP experienced interdecadal decrease during the period preceding 1927, 1962–1988, and 2004 onwards, but saw an increase during the periods of 1928–1961 and 1989–2003. The atmospheric circulations responsible for interdecadal variations in LSP over the SETP were also analysed. These analyses identified significant synergistic impacts of decreased mid‐latitude upstream westerlies and increased low‐latitude monsoonal southerlies over the Central North Bay of Bengal (CNBOB) on interdecadal variations in precipitation, suggesting striking interactions between extratropical eastward cold air and tropical northward warm/humid air. Further observational and modelling evidence suggested that Atlantic Multidecadal Oscillation (AMO) was likely to be a salient oceanic driver for the interdecadal synergy between upstream westerlies and CNBOB monsoonal southerlies. The elevated sea surface temperature anomalies associated with the warm phase of the AMO could spark favourable local atmospheric anomalies, forcing an upper‐tropospheric, planetary‐scale teleconnection emanating from the east of the North Atlantic sector, which may serve as an effective bridge linking the remote AMO signal and the synergy between westerlies and monsoonal southerlies around the SETP on interdecadal timescales. Our findings provided new insights into the understanding of the synergistic roles of westerlies and monsoons in the modulation of interdecadal LSP over the SETP, prior to the peak Asian summer monsoon season.

Correction to: Increased Soluble Epoxide Hydrolase Activity Positively Correlates with Mortality in Heart Failure Patients with Preserved Ejection Fraction: Evidence from Metabolomics - Liyuan Peng; Ziping Song; Chengcheng Zhao; Kudusi Abuduwufuer; Yanwen Wang; Zheng Wen; Li Ni; Chenze Li; Ying Yu; Yi Zhu; Hualiang Jiang; Jinshan Shen; et al. (Phenomics, 2022)

7,8-Dihydroxyflavone attenuates the virulence of Staphylococcus aureus by inhibiting alpha-hemolysin - Nan Bian; Xiangqian Chen; Xinran Ren; Zishu Yu; Mengli Jin; Xiaoyu Chen; Chang Liu; Yanhe Luan; Lin Wei; Ying Chen; Wu Song; Yicheng Zhao; et al. (World Journal of Microbiology and Biotechnology, 2022)

The remediation of uranium-contaminated groundwater via bioreduction coupled to biomineralization with different pH and electron donors - Guohua Wang; Ying Liu; Jiali Wang; Jinjing Xiang; Taotao Zeng; Shiyou Li; Jian Song; Zhiyue Zhang; Jinxiang Liu (Environmental Science and Pollution Research, 2022)

Identification of thioredoxin genes and analysis of their expression under abiotic stresses in Medicago truncatula - Liugen Xu; Yong Zhou; Jie Cheng; Liqing Kang; Yuqi Qiang; Xuemei Yan; Yuhua Yan; Ying Tang; Yihua Wang; Hua Li; Jianbo Song (Acta Physiologiae Plantarum, 2022)

cPKCγ Deficiency Exacerbates Autophagy Impairment and Hyperphosphorylated Tau Buildup through the AMPK/mTOR Pathway in Mice with Type 1 Diabetes Mellitus - Jiayin Zheng; Yue Wang; Yue Liu; Song Han; Ying Zhang; Yanlin Luo; Yi Yan; Junfa Li; Li Zhao (Neuroscience Bulletin, 2022)

Relationship between bitumen and zinc–lead mineralization in the Nanmushu zinc–lead deposit, northern margin of Sichuan Basin, China - Xiaodong Huang; Cuihua Chen; Zhijiao Song; Li Yin; Ying Gu; Xiang Lai; Xiaojie Chen (Arabian Journal of Geosciences, 2022)

FIO-ESM v2.0 CORE2-forced experiment for the CMIP6 Ocean Model Intercomparison Project - Qi Shu; Zhenya Song; Ying Bao; Xiaodan Yang; Yajuan Song; Xinfang Li; Meng Wei; Fangli Qiao (Acta Oceanologica Sinica, 2022)

Transcriptome Analysis of Greenfin Horse-Faced Filefish (Thamnaconus septentrionalis) Gills in Response to Amyloodinium ocellatum (AO) Infection - Li-Guo Yang; Yue Wang; Wen-Bin Xu; Bo Qin; Na Ying; Xue-Feng Song; Yan-Feng Yue; Xiao-Shan Wang; Bian-Bian Zhang; Yan-Qing Wu (Fishes, 2022)
The greenfin horse-faced filefish (Thamnaconus septentrionalis) is susceptible to recurrent Amyloodinium ocellatum (AO) infestation over the grow-out production cycle. This parasite breeds mainly on the gills, causing hypoxia in the fish body, and leading to many deaths. The host-parasite response drives a complex immune reaction, which is poorly understood. To generate a model for host-parasite interaction and the pathogenesis of AO in greenfin horse-faced filefish, an RNA-seq approach, differential gene expression, GO, and KEGG analyses were employed. Overall, 624 new genes and 2076 differentially expressed genes (DEGs) were detected, including 942 upregulated and 1134 downregulated genes in the gills. Compared with the control group, the expression of leptin a, GTPase IMAP family member 4, and NLR family CARD domain-containing protein 3 was significantly higher in the AO-infected group. Conversely, cell wall integrity and stress response component 1-like, and hepcidin-like were significantly downregulated in the gills of AO-infected fish. GO and KEGG enrichment analysis indicated that DEGs were significantly enriched in signaling pathways associated with viral protein interaction with cytokine and cytokine receptor and cytokine–cytokine receptor interaction. Collectively, this transcriptomic study provides novel molecular insights into the pathology caused by AO infestation and alternative theories for future research implementing strategies to control and manage AO.

The Classification and significance of fine-grained deposits of micro-laminae rich in unconventional oil and gas resources - Li Dong; Ying Li; Dongdong Wang; Haiyan Liu; Guangzeng Song; Zengxue Li; Fanfei Kong; Lusheng Yin (Frontiers of Earth Science, 2022)

Proteome Based Comparative Investigation of a High Sucrose Sugarcane Mutant in Contrast to the Low Sucrose Mother Variety by Using TMT Quantitative Proteomics - Qaisar Khan; Ying Qin; Dao-Jun Guo; Zhen Lu; Xian-Qiu Xie; Li-Tao Yang; Qiang Liang; Xiu-Peng Song; Yong-Xiu Xing; Yang-Rui Li (Sugar Tech, 2022)

The contribution of nirK gene-containing thaumarchaea to denitrification and N2O production across coastal sediment and terrestrial ecosystems - Bing Han; Si-Yi Liu; Li-Li Han; Xiao-Tong Song; Liu-Ying Mo; Li-Mei Zhang (Journal of Soils and Sediments, 2022)

Comparative Analysis of Endogenous Hormones and Metabolite Profiles in Early-Spring Flowering Plants and Unflowered Plants Revealing the Strategy of Blossom - Xue Yan; Jia Liu; Ke-Xin Wu; Nan Yang; Li-Ben Pan; Ying Song; Yang Liu; Zhong-Hua Tang (Journal of Plant Growth Regulation, 2022)

PPARγ Dysfunction in the Medial Prefrontal Cortex Mediates High-Fat Diet-Induced Depression - Cong-Cong Fu; Xin-Yi Zhang; Liu Xu; Hui-Xian Huang; Shuang Xu; Qiao-Qi Wu; Zhen Wang; Xi Gu; Li-Fang Lin; Song Lin; Ying-Ying Fang; Xiong Cao; et al. (Molecular Neurobiology, 2022)

Total, bioavailable and free 25-hydroxyvitamin D are associated with the prognosis of patients with non-small cell lung cancer - Si-Min Peng; Na Yu; Jun Che; Jia-Ying Xu; Guo-Chong Chen; Da-Peng Li; Yu-Song Zhang; Li-Qiang Qin (Cancer Causes & Control, 2022)

Canonical transformation for multivariate mixed model association analyses - Li’ang Yang; Ying Zhang; Yuxin Song; Hengyu Zhang; Runqing Yang (Theoretical and Applied Genetics, 2022)

lncRNA BDNF-AS Attenuates Propofol-Induced Apoptosis in HT22 Cells by Modulating the BDNF/TrkB Pathway - Yu-Hai Xu; Yuan Luo; Jiang-Bei Cao; Yan-Hong Liu; Yu-Xiang Song; Xiao-Ying Zhang; Qiang Fu; Wei-Dong Mi; Hao Li (Molecular Neurobiology, 2022)
Propofol is widely used as an intravenous anesthetic in clinical practice. Previous studies have indicated that propofol induces apoptosis in neurons. Brain-derived neurotrophic factor (BDNF), a neurotrophic factor, is associated with neuronal apoptosis. BDNF-AS, a relatively conserved long non-coding RNA, can reverse the transcription of BDNF. This study aimed to investigate the involvement of BDNF-AS in propofol-induced apoptosis in HT22 cells. HT22 cells were treated with various concentrations of propofol at different time points. BDNF-AS was silenced using BDNF-AS-targeting siRNA. TrkB was antagonized by the TrkB inhibitor, ANA-12. Flow cytometry, quantitative reverse-transcription PCR, and western blotting were performed to analyze apoptosis and the expression of genes and proteins, respectively. In propofol-treated HT22 cells, BDNF-AS was upregulated, and BDNF was downregulated in a time- and dose-dependent manner. BDNF-AS downregulation mediated by siRNA mitigated apoptosis, upregulated the expression of Bcl-2, and downregulated the expression of Bax and caspase-3, 7, and 9. ANA-12 downregulated the expression of Bcl-2, upregulated the expression of Bax and caspase-3, 7, and 9, and increased apoptosis. Our study implied that inhibition of BDNF-AS can decrease propofol-induced apoptosis by activating the BDNF/TrkB pathway. Thus, the BDNF-AS-BDNF/TrkB signaling pathway may be a valuable target for treating propofol-induced neurotoxicity.

Identification and management of GCK-MODY complicating pregnancy in Chinese patients with gestational diabetes - Yanyan Jiang; Fusong Jiang; Ming Li; Qingkai Wu; Chenming Xu; Rong Zhang; Mingqiang Song; Yanzhong Wang; Ying Wang; Yating Chen; Juan Zhang; Xiaoxu Ge; et al. (Molecular and Cellular Biochemistry, 2022)

First record of Chaetomium globosum causing leaf spot on Arachis hypogaea in China - Yucheng Chi; Jing Yu; Zhiqing Guo; Zhiliang Zhang; Kang He; Ying Li; Xinying Song; Manlin Xu; Xia Zhang (Journal of Plant Pathology, 2022)

Alkaloids constituents from the roots of Phragmites australis (Cav.) Trin. ex Steud. with their cytotoxic activities - Ying Chen; Li Li; Li-Rui Jiang; Jia-Yin Tan; Li-Na Guo; Xiao-Li Wang; Wei Dong; Wen-Bao Wang; Ji-Kai Sun; Bo Song (Natural Product Research, 2022)

A new isoflavone from the fruits of Ficus auriculata and its antibacterial activity - Tai-Ming Shao; Hai-Xia Liao; Xiao-Bao Li; Guang-Ying Chen; Xiao-Ping Song; Chang-Ri Han (Natural Product Research, 2022)

Bioinformatics Analysis of the MicroRNA-Metabolic Gene Regulatory Network in Neuropathic Pain and Prediction of Corresponding Potential Therapeutics - Huai-Gen Zhang; Li Liu; Zhi-Ping Song; Da-Ying Zhang (Journal of Molecular Neuroscience, 2022)

Geochronology and geochemistry of Early Cretaceous bimodal volcanic rocks from Erguna Massif, NE China: evidence for the back-arc extension of the Mongol–Okhotsk orogenic belt - Fei Yang; Gong-Zheng Chen; Guang Wu; Ying-Lei Li; Yong-Xu Shao; Tie-Gang Li; Guang-Chao Song; Bing Han (International Journal of Earth Sciences, 2022)

Differential expression of long non-coding RNAs in the hippocampus of mice exposed to PM2.5 in Dalian, China - Jie Li; Longying Zhang; Jiaqi Wang; Ruxue Jia; Xiao Zhang; Xiaojing Li; Ying Fu; Laiyu Song (Environmental Science and Pollution Research, 2022)

Geology, fluid inclusion, bitumen and isotope geochemistry of the organic-matter-rich Nanmushu lead–zinc deposit, Mayuan, the northern margin of the Yangtze platform, China - Ying Gu; Cuihua Chen; Yulong Yang; Zhijiao Song; Xiaojie Chen; Wei Jia; Xiang Lai; Hongzhi Li; Li Yin; Xiaodong Huang; Qiumin Wu (Arabian Journal of Geosciences, 2022)

Spatiotemporal characteristics and driving factors of global planetary albedo: an analysis using the Geodetector method - Mingzhu Lv; Yan Song; Xijia Li; Mengsi Wang; Ying Qu (Theoretical and Applied Climatology, 2022)

A Novel De Novo TUBB3 Variant Causing Developmental Delay, Epilepsy and Mild Ophthalmological Symptoms in a Chinese Child - Jiao Xue; Zhenfeng Song; Shuyin Ma; Zhi Yi; Chengqing Yang; Fei Li; Kaixuan Liu; Ying Zhang (Journal of Molecular Neuroscience, 2022)

Experimental investigation and discrete element method simulation on mechanical properties and failure mechanism of polymer-stabilized sand - Wenyue Che; Jin Liu; Hongyang Li; Chengzong He; Yuxia Bai; Zezhuo Song; Ying Wang; Wei Qian; Zhihao Chen (Bulletin of Engineering Geology and the Environment, 2022)

Unsupervised Machine Learning for Improved Delaunay Triangulation - Tao Song; Jiarong Wang; Danya Xu; Wei Wei; Runsheng Han; Fan Meng; Ying Li; Pengfei Xie (Journal of Marine Science and Engineering, 2021)
Physical oceanography models rely heavily on grid discretization. It is known that unstructured grids perform well in dealing with boundary fitting problems in complex nearshore regions. However, it is time-consuming to find a set of unstructured grids in specific ocean areas, particularly in the case of land areas that are frequently changed by human construction. In this work, an attempt was made to use machine learning for the optimization of the unstructured triangular meshes formed with Delaunay triangulation in the global ocean field, so that the triangles in the triangular mesh were closer to equilateral triangles, the long, narrow triangles in the triangular mesh were reduced, and the mesh quality was improved. Specifically, we used Delaunay triangulation to generate the unstructured grid, and then developed a K-means clustering-based algorithm to optimize the unstructured grid. With the proposed method, unstructured meshes were generated and optimized for global oceans, small sea areas, and the South China Sea estuary to carry out data experiments. The results suggested that the proportion of triangles with a triangle shape factor greater than 0.7 amounted to 77.80%, 79.78%, and 79.78%, respectively, in the unstructured mesh. Meanwhile, the proportion of long, narrow triangles in the unstructured mesh was decreased to 8.99%, 3.46%, and 4.12%, respectively.

Overexpression of the PLK4 Gene as a Novel Strategy for the Treatment of Autosomal Recessive Microcephaly by Improving Centrosomal Dysfunction - Ya-Song Xu; Zhi-Ying Su; Li Sun; Xiao-Mei Yang; Shi-Yu Sun; Xiao-Fei Ji; Yi-Zhen Ji; Su-Qing Zhang; Jie Tian; Qi-Chang Wu (Journal of Molecular Neuroscience, 2021)

Echinicola salinicaeni sp. nov., a novel bacterium isolated from saltern mud - Han Zhao; Chun-Yi Song; Rui Yin; Yan-Jun Yi; Shuai-Ting Yun; Ying-Xiu Li; Yan-Xia Zhou (Antonie van Leeuwenhoek, 2021)

Isolation of a novel adomavirus from cultured American eels, Anguilla rostrata , with haemorrhagic gill necrosis disease - Jin‐Xian Yang; Xi Chen; Ying‐Ying Li; Tie‐Ying Song; Jun‐Qing Ge (Journal of Fish Diseases, 2021)
Recently, the culture of American eels (Anguilla rostrate) in China has been impacted by emergence of a disease with signs of haemorrhagic gill necrosis. The gills of diseased eels are covered with petecchia and they bleed when the operculum is pressed. In this study, a novel American eel adomavirus (AEAdoV) was isolated from the diseased eels using the eel ovary cell line (EO). The virus proliferated in the EO cells with a maximum TCID 50 /ml of 10 6.29 ± 0.23 at 6 days post‐infection. The virions were non‐enveloped with a diameter of 75–85 nm and shown to be a DNA virus upon 5‐iodo‐2’‐deoxyuridine (IDU) treatment. PCR assays showed that AEAdoV encodes a superfamily 3 helicases (S3H) replicase and shared high similarities with Anguilla marmorata adomavirus (MEAdoV). Although no clinical signs or mortality was observed among the eels injected with AEAdoV, the virus was reisolated from livers, kidneys and gills of injected eels at 35 days post‐injection. Our results suggested that AEAdoV exhibited a latent infection in A. rostrata . The pathogenicity of the AEAdoV needs to be confirmed further.

Implantation of Bone Marrow Mesenchymal Stem Cells into Small Intestinal Submucosa Improves Bile Duct Injury in Rabbits - Ying Li; Piao Wang; Xiao-dong Hu; Jing-da Zeng; Cheng Fang; Yu Gan; Fang-yi Peng; Xiao-li Yang; De Luo; Bo Li; Song Su (Tissue Engineering and Regenerative Medicine, 2021)

Sandaracinobacteroides hominis gen. nov., sp. nov., isolated from human skin - Ping-Hua Qu; Hai-Min Luo; Jun-Hui Feng; Song Li; Cha Chen; Lei Dong; Yu-Zhen Ming; Wen-Jun Li; Ying Lin (Archives of Microbiology, 2021)

Imaging and clinical features of cervical artery web: report of 41 cases and literature review - Minghui Wang; Ruizhi Zhou; Han Zhao; Lei Niu; Song Liu; Ying Li; Xuejun Liu (Acta Neurologica Belgica, 2021)

The ATP Level in the mPFC Mediates the Antidepressant Effect of Calorie Restriction - Qian Wang; Ying Kong; Song Lin; Ding-Yu Wu; Jian Hu; Lang Huang; Wen-Si Zang; Xiao-Wen Li; Jian-Ming Yang; Tian-Ming Gao (Neuroscience Bulletin, 2021)

Mineralogy, fluid inclusions, H-O isotopes, and trace element of the Dongzigou Pb-Zn deposit in the Sangmuchang metallogenic belt, China - Ying Gu; Cuihua Chen; Yulong Yang; Xuhao Kang; Yin Li; Xiaojie Chen; Xiang Lai; Zhijiao Song; Deping Yang; Cheng Jin; Shuyue Liu (Arabian Journal of Geosciences, 2021)

Gonadal lipidomics profile of an ovoviviparity teleost, black rockfish, during gonadal development - Jianshuang Li; Min Song; Haishen Wen; Ying Zhang; Yun Li; Likang Lyu; Xiaojie Wang; Xin Qi (Fish Physiology and Biochemistry, 2021)

Altered gray matter structural covariance networks at both acute and chronic stages of mild traumatic brain injury - Jie Song; Jie Li; Lixiang Chen; Xingqi Lu; Senning Zheng; Ying Yang; Bolin Cao; Yihe Weng; Qinyuan Chen; Jianping Ding; Ruiwang Huang (Brain Imaging and Behavior, 2021)

Spatio-temporal distribution of Konosirus punctatus spawning and nursing ground in the South Yellow Sea - Xiangyu Long; Rong Wan; Zengguang Li; Yiping Ren; Pengbo Song; Yongjun Tian; Binduo Xu; Ying Xue (Acta Oceanologica Sinica, 2021)

Clinical features of nine cases of leucine-rich glioma inactivated 1 protein antibody-associated encephalitis - Ying Li; Fan Song; Wei Liu; Ying Wang (Acta Neurologica Belgica, 2021)

Genetic Analysis of ZNF Protein Family Members for Early-Onset Parkinson’s Disease in Chinese Population - Chun Yu Li; Ru Wei Ou; Yong Ping Chen; Xiao Jing Gu; Qian Qian Wei; Bei Cao; Ling Yu Zhang; Yan Bing Hou; Kun Cheng Liu; Xue Ping Chen; Wei Song; Bi Zhao; et al. (Molecular Neurobiology, 2021)

Marinifaba aquimaris gen. nov., sp. nov., a novel chitin‐degrading gammaproteobacterium in the family Alteromonadaceae isolated from seawater of the Mariana Trench - Xin Sui; Xiao-yan He; Ning-hua Liu; Yan-ru Dang; Qian-qian Cha; Mei-ling Sun; Chun-yang Li; Hui-hui Fu; Xiao-yan Song; Qi-long Qin; Xiu-lan Chen; Yu-zhong Zhang; et al. (Antonie van Leeuwenhoek, 2021)

Sublethal dose of warfarin induction promotes the accumulation of warfarin resistance in susceptible Norway rats - Xiaohui Ma; Yan Chen; Yaqi Ying; Yuanzhao Geng; Dawei Wang; Ning Li; Xiao-Hui Liu; Ying Song (Journal of Pest Science, 2021)

Accurately Discriminating COVID-19 from Viral and Bacterial Pneumonia According to CT Images Via Deep Learning - Fudan Zheng; Liang Li; Xiang Zhang; Ying Song; Ziwang Huang; Yutian Chong; Zhiguang Chen; Huiling Zhu; Jiahao Wu; Weifeng Chen; Yutong Lu; Yuedong Yang; et al. (Interdisciplinary Sciences: Computational Life Sciences, 2021)

Altered structural and functional connectivity in CSF1R-related leukoencephalopathy - Fei-Xia Zhan; Ze-Yu Zhu; Qing Liu; Hai-Yan Zhou; Xing-Hua Luan; Xiao-Jun Huang; Xiao-Li Liu; Wo-Tu Tian; Shi-Ge Wang; Xiao-Xuan Song; Guang Chen; Ming-Liang Zhao; et al. (Brain Imaging and Behavior, 2021)

Anguillid herpesvirus 1 (AngHV) ORF95 encodes a late, structural envelope protein - Xi Chen; Jin-Xian Yang; Ying-Ying Li; Tie-Ying Song; Jun-Qing Ge (Virus Genes, 2021)

Design of supercontinuum laser hyperspectral light detection and ranging (LiDAR) (SCLaHS LiDAR) - Guoqing Zhou; Xiang Zhou; Youjian Song; Donghui Xie; Long Wang; Guangjian Yan; Minglie Hu; Bowen Liu; Weidong Shang; Chenghu Gong; Cheng Wang; Huaguo Huang; et al. (International Journal of Remote Sensing, 2021)

Elucidating the Effect of Fine Lactose Ratio on the Rheological Properties and Aerodynamic Behavior of Dry Powder for Inhalation - Ying Sun; Lu Qin; Jiayi Li; Jian Su; Ruxiao Song; Xin Zhang; Jian Guan; Shirui Mao (The AAPS Journal, 2021)

Identification of two UDP-glycosyltransferases involved in the main oleanane-type ginsenosides in Panax japonicus var. major - Jun-Rong Tang; Geng Chen; Ying-Chun Lu; Qing-Yan Tang; Wan-Ling Song; Yuan Lin; Ying Li; Su-Fang Peng; Sheng-Chao Yang; Guang-Hui Zhang; Bing Hao (Planta, 2021)

Application of Phage-Displayed Peptides in Tumor Imaging Diagnosis and Targeting Therapy - Chunyan Li; Jia Li; Ying Xu; Ying Zhan; Yu Li; Tingting Song; Jiao Zheng; Hong Yang (International Journal of Peptide Research and Therapeutics, 2021)

Polycyclic aromatic hydrocarbon and n-alkane pollution characteristics and structural and functional perturbations to the microbial community: a case-study of historically petroleum-contaminated soil - Jian Li; Ying Xu; Quanwei Song; Jie Yang; Lin Xie; Shihang Yu; Lei Zheng (Environmental Science and Pollution Research, 2021)

Increased Susceptibility of Atrial Fibrillation Induced by Hyperuricemia in Rats: Mechanisms and Implications - Dingyu Wang; Li Sun; Guowei Zhang; Yang Liu; Zhaoguang Liang; Jing Zhao; Shuangli Yin; Mengqi Su; Song Zhang; Ying Wei; He Liu; Desen Liang; et al. (Cardiovascular Toxicology, 2021)

In vitro antifungal susceptibility of Sporothrix globosa isolates from Jilin Province, northeastern China: comparison of yeast and mycelial phases - Yang Song; Shanshan Li; Ying Shi; Lipei Zhao; Yu Cui; Lei Yao; Yu Zhen; Ruili Chen; Yan Cui (Brazilian Journal of Microbiology, 2021)

Measuring solar irradiance profiles in the Arctic sea ice using fiber optic spectrometry via inclined holes - Zexia Qiu; Hangzhou Wang; Tao Li; Hong Song; Yuanqian Wu; Tingting Yan; Ying Chen (Acta Oceanologica Sinica, 2021)

Network pharmacology uncovers anti-cancer activity of vibsane-type diterpenes from Viburnum odoratissimum - Ying-Ying Zhang; Jing-Jie Chen; Dan-Qi Li; Yan- Zhang; Xiao-Bo Wang; Guo-Dong Yao; Shao-Jiang Song (Natural Product Research, 2021)

Control effects of the synsedimentary faults on the basin-marginal fans in the central part of the deep-water area of early Oligocene Qiongdongnan Basin, South China Sea - Guangzeng Song; Zengxue Li; Haizhang Yang; Dongdong Wang; Ying Chen; Rui Sun (Acta Oceanologica Sinica, 2021)

Satellite Remote Sensing for Estimating PM2.5 and Its Components - Ying Li; Shuyun Yuan; Shidong Fan; Yushan Song; Zihao Wang; Zujun Yu; Qinghua Yu; Yiwen Liu (Current Pollution Reports, 2021)

Using sowing date management to promote micronutrient quality and alleviate cadmium accumulation in rice grains - Lin-lin Shi; Ming-xing Shen; Hong-jun Wu; Chang-ying Lu; Li-juan Mei; Xin-lian Zhu; Hai-hou Wang; Yun-Sheng Song (Cereal Research Communications, 2020)

Greater promotion of DNRA rates and nrfA gene transcriptional activity by straw incorporation in alkaline than in acidic paddy soils - Ren Bai; Yun-Ting Fang; Liu-Ying Mo; Ju-Pei Shen; Lin-Lin Song; Ya-Qi Wang; Li-Mei Zhang; Ji-Zheng He (Soil Ecology Letters, 2020)

LncRNA A2M-AS1 lessens the injury of cardiomyocytes caused by hypoxia and reoxygenation via regulating IL1R2 - Xue-Lian Song; Fei-Fei Zhang; Wen-Jing Wang; Xin-Ning Li; Yi Dang; Ying-Xiao Li; Qian Yang; Mei-Jing Shi; Xiao-Yong Qi (Genes & Genomics, 2020)

Phosphodiesterase 2 inhibitor Hcyb1 reverses corticosterone-induced neurotoxicity and depression-like behavior - Meng-Jia Zhu; Jing Shi; Yong Chen; Guobing Huang; Xiong-Wei Zhu; Sam Zhang; Xian-Feng Huang; Guo-Qiang Song; Han-Ting Zhang; Heng-Ming Ke; James M. O’Donnell; Li-Qun Wang; et al. (Psychopharmacology, 2020)

Low Serum Uric Acid Levels Promote Hypertensive Intracerebral Hemorrhage by Disrupting the Smooth Muscle Cell-Elastin Contractile Unit and Upregulating the Erk1/2-MMP Axis - Ning Xiao; Tian-long Liu; Hao Li; Hao-chen Xu; Jing Ge; Hong-yan Wen; Cong-xia Bai; Li Song; Ying-ying Sun; Yin-hui Zhang; Ru-tai Hui; Wei-hua Song; et al. (Translational Stroke Research, 2020)

IL-6 induces tumor suppressor protein tyrosine phosphatase receptor type D by inhibiting miR-34a to prevent IL-6 signaling overactivation - Fan Zhang; Bo Wang; Tao Qin; Lu Wang; Qingqing Zhang; Ying Lu; Bo Song; Xiaotang Yu; Lianhong Li (Molecular and Cellular Biochemistry, 2020)

Serum LUCAT1 implicates the pathogenesis of muscle-invasive bladder cancer via targeting miR-199a-5p and miR-199b-5p - Yong Zhou; Xuejing Song; Xiameng Li; Huimin Li; Ying Peng (Journal of Molecular Histology, 2020)

Sequence identification and expression profile of seven Dermacentor marginatus glutathione S-transferase genes - Huercha; Ying Ma; Yunwei Hao; Min Li; Zhengxiang Hu; Ruiqi Song; Liting Wei; Shilong Fan; Songqin Chen; Xinli Fan; Xuejie Zhai; Qingyong Guo; et al. (Experimental and Applied Acarology, 2020)

Retrospective analysis of HIV-1 drug resistance mutations in Suzhou, China from 2009 to 2014 - Yanhui Song; Jingping Hu; Jun He; Chunsheng Dong; Ying Yuan; Yuan Li; Ronghua Li; Xuerong Ya (Virus Genes, 2020)

FIO-ESM v2.0 Outputs for the CMIP6 Global Monsoons Model Intercomparison Project Experiments - Yajuan Song; Xinfang Li; Ying Bao; Zhenya Song; Meng Wei; Qi Shu; Xiaodan Yang (Advances in Atmospheric Sciences, 2020)
Three tiers of experiments in the Global Monsoons Model Intercomparison Project (GMMIP), one of the endorsed model intercomparison projects of phase 6 of the Coupled Model Intercomparison Project (CMIP6), are implemented by the First Institute of Oceanography Earth System Model version 2 (FIO-ESM v2.0), following the GMMIP protocols. Evaluation of global mean surface air temperature from 1870 to 2014 and climatological precipitation (1979–2014) in tier-1 shows that the atmosphere model of FIO-ESM v2.0 can reproduce the basic observed atmospheric features. In tier-2, the internal variability is captured by the coupled model, with the SST restoring to the model climatology plus the observed anomalies in the tropical Pacific and North Atlantic. Simulation of the Northern Hemisphere summer monsoon circulation is significantly improved by the SST restoration in the North Atlantic. In tier-3, five orographic perturbation experiments are conducted covering the period 1979–2014 by modifying the surface elevation or vertical heating in the prescribed region. In particular, the strength of the South Asian summer monsoon is reduced by removing the topography or thermal forcing above 500 m over the Asian continent. Monthly and daily simulated outputs of FIO-ESM v2.0 are provided through the Earth System Grid Federation (ESGF) node to contribute to a better understanding of the global monsoon system.

First case of Shewanella indica isolated from a Bryde’s whale (Balaenoptera edeni) stranded in the northern Beibu Gulf, China - Jia Li; Richard W. McLaughlin; Mo Chen; Ying Li Liu; Hia Xia Xie; Xiao Ling Wan; Jun Ying Zhou; Jin Song Zheng (Antonie van Leeuwenhoek, 2020)

A fundamental theorem for eco-environmental surface modelling and its applications - Tianxiang Yue; Na Zhao; Yu Liu; Yifu Wang; Bin Zhang; Zhengping Du; Zemeng Fan; Wenjiao Shi; Chuanfa Chen; Mingwei Zhao; Dunjiang Song; Shihai Wang; et al. (Science China Earth Sciences, 2020)

Impaired Parahippocampal Gyrus–Orbitofrontal Cortex Circuit Associated with Visuospatial Memory Deficit as a Potential Biomarker and Interventional Approach for Alzheimer Disease - Lin Zhu; Zan Wang; Zhanhong Du; Xinyang Qi; Hao Shu; Duan Liu; Fan Su; Qing Ye; Xuemei Liu; Zheng Zhou; Yongqiang Tang; Ru Song; et al. (Neuroscience Bulletin, 2020)

Design and synthesis of novel 7-[( N -substituted-thioureidopiperazinyl)-methyl]-camptothecin derivatives as potential cytotoxic agents - Zi-Long Song; Guan-Zhou Yang; Jun-Cai Li; Ying-Qian Liu; Chen-Jie Yang; Masuo Goto; Zhi-Jun Zhang; Susan L. Morris-Natschke; Hua Liu; Kuo-Hsiung Lee (Natural Product Research, 2020)

Comparative transcriptome analysis reveals a gene expression profile that contributes to rhizome swelling in Panax japonicus var. major - Jun Rong Tang; Ying Chun Lu; Zheng Jie Gao; Wan Ling Song; Kun Hua Wei; Yan Zhao; Qing Yan Tang; Xue Jiao Li; Jun Wen Chen; Guang Hui Zhang; Guang Qiang Long; Wei Fan; et al. (Plant Biosystems, 2020)

Identification of Ala2Thr mutation in insulin gene from a Chinese MODY10 family - Juan Zhang; Yanjun Liu; Ming Li; Xiaoxu Ge; Ying Wang; Xin Huang; Di Yang; Rong Zhang; Yating Chen; Ming Lu; Jun Yin; Mingqiang Song; et al. (Molecular and Cellular Biochemistry, 2020)

Evaluating the effects of transgenic Bt rice cultivation on soil stability - Ying-ying Song; Jia-wen Liu; Li-kun Li; Man-qiang Liu; Xiao-yun Chen; Fa-jun Chen (Environmental Science and Pollution Research, 2020)

Identification and genetic analysis of a totivirus isolated from the Culex tritaeniorhynchus in northern China - Fan Li; Jiang Du; Zhiqiang Wu; Weijia Zhang; Shihong Fu; Jingdong Song; Qianying Wang; Ying He; Wenwen Lei; Songtao Xu; Aiqiang Xu; Li Zhao; et al. (Archives of Microbiology, 2020)

Application of the Tumor Site Recognizable and Dual-Responsive Nanoparticles for Combinational Treatment of the Drug-Resistant Colorectal Cancer - Ying Shi; Shufang Shan; Chenghui Li; Xuejiao Song; Chaoxiong Zhang; Jiayi Chen; Jia You; Jingyuan Xiong (Pharmaceutical Research, 2020)

Pedobacter indicus sp. nov., isolated from deep-sea sediment - Xiao-yan He; Na Li; Xiu-lan Chen; Yu-zhong Zhang; Xi-ying Zhang; Xiao-yan Song (Antonie van Leeuwenhoek, 2020)

Global biogeographic synthesis and priority conservation regions of the relict tree family Juglandaceae - Yi‐Gang Song; Yann Fragnière; Hong‐Hu Meng; Ying Li; Sébastien Bétrisey; Adriana Corrales; Steven Manchester; Min Deng; Anna K. Jasińska; Hoàng Văn Sâm; Gregor Kozlowski (Journal of Biogeography, 2020)
Aim To establish a complete database of Juglandaceae at a spatiotemporal scale and develop a phylogeographic framework with which to elucidate the distributional patterns, diversity patterns, origins, evolution, and conservation priority regions of this family. Location Worldwide. Taxon Walnut family (Juglandaceae). Methods Data on the distribution of all the extant and fossil species of Juglandaceae were collected, followed by analyses of its latitudinal distribution, elevational distribution, and species and generic diversity. Furthermore, based on all genera and 87% of the species, we reconstructed phylogenetic relationships, estimated divergence times, calculated phylogenetic diversity and inferred ancestral distributions. Results Extant Juglandaceae (10 genera and 60 species) are mainly distributed in eastern Asia and North America (principally between 20 and 40°N). Tropical Juglandaceae mainly inhabit mountainous areas higher than 1,000 m, especially in the New World. Southwest China and northern Vietnam are characterized by high species, generic and phylogenetic diversity. The United States of America has only high species diversity. The area of origin of Juglandaceae was North America and Europe in the early Eocene, and its widespread dispersal mainly occurred between 13 and 26 Ma. Main conclusions The members of Juglandaceae inhabit areas with temperate climatic conditions. The diversification centre has shifted intercontinentally from North America and Europe to Southwest China and northern Vietnam, which are identified as conservation priority regions. The high‐latitude cooling during the Oligocene followed by a long‐term stable warmer climate in the early and middle Miocene drove the southward translocation of the family.

Neogenkwanine I from the flower buds of Daphne genkwa with its stereostructure confirmation using quantum calculation profiles and antitumor evaluation - Xue-Wen Hou; Shuang Han; Ying-Ying Zhang; Hai-Bi Su; Pin-Yi Gao; Ling-Zhi Li; Shao-Jiang Song (Natural Product Research, 2020)

Lonicerae japonicae flos and Lonicerae flos: a systematic review of ethnopharmacology, phytochemistry and pharmacology - Yuke Li; Wen Li; Chaomei Fu; Ying Song; Qiang Fu (Phytochemistry Reviews, 2020)

Relative roles of formation and preservation on gold endowment along the Sanshandao gold belt in the Jiaodong gold province, China: importance for province- to district-scale gold exploration - Liang Zhang; David I. Groves; Li-Qiang Yang; Gong-Wen Wang; Xiang-Dong Liu; Da-Peng Li; Ying-Xin Song; Wei Shan; Si-Chen Sun; Zhao-Kun Wang (Mineralium Deposita, 2020)

The DI–DII linker of human parainfluenza virus type 3 fusion protein is critical for the virus - Ying Liu; Miaomiao Chi; Hongling Wen; Li Zhao; Yanyan Song; Na Liu; Lianli Chi; Zhiyu Wang (Virus Genes, 2020)

Development of Climate and Earth System Models in China: Past Achievements and New CMIP6 Results - Tianjun Zhou; Ziming Chen; Liwei Zou; Xiaolong Chen; Yongqiang Yu; Bin Wang; Qing Bao; Ying Bao; Jian Cao; Bian He; Shuai Hu; Lijuan Li; et al. (Journal of Meteorological Research, 2020)

cDNA-AFLP analysis of differentially expressed genes during microspore embryogenesis in non-heading Chinese cabbage - Ya Zhang; Su-yan Gao; Huan-huan Liu; Xi-lin Zhang; Ai-song Zeng; Jian-jun Wang; Xi-lin Hou; Ying Li (In Vitro Cellular & Developmental Biology - Plant, 2020)

DNA methylation levels in different tissues in tea plant via an optimized HPLC method - Ying Gao; Jia-Li Hao; Zhen Wang; Kwan-Jeong Song; Jian-Hui Ye; Xin-Qiang Zheng; Yue-Rong Liang; Jian-Liang Lu (Horticulture, Environment, and Biotechnology, 2019)

Asymmetric responses of plant community structure and composition to precipitation variabilities in a semi-arid steppe - Mingxing Zhong; Jian Song; Zhenxing Zhou; Jingyi Ru; Mengmei Zheng; Ying Li; Dafeng Hui; Shiqiang Wan (Oecologia, 2019)

Genome-wide association analysis of salt tolerance QTLs with SNP markers in maize (Zea mays L.) - Yonghong Xie; Yan Feng; Qi Chen; Feike Zhao; Shuijuan Zhou; Ying Ding; Xianliang Song; Ping Li; Baohua Wang (Genes & Genomics, 2019)

Structure analysis and anti-fatigue activity of a polysaccharide from Lepidium meyenii Walp - Yun Tang; Zhen-Yuan Zhu; Li-Chao Pan; Huiqing Sun; Qiao-Ying Song; Yongmin Zhang (Natural Product Research, 2019)

Dynamic expressions of hypothalamic genes regulate seasonal breeding in a natural rodent population - Dawei Wang; Ning Li; Lin Tian; Fei Ren; Zhengguang Li; Yan Chen; Lan Liu; Xiangfa Hu; Xuechang Zhang; Ying Song; Roelof A. Hut; Xiao‐Hui Liu (Molecular Ecology, 2019)
Seasonal breeding is a universal reproductive strategy in many animals. Hypothalamic genes, especially type 2 and 3 iodothyronine deiodinases ( Dio2 / 3 ), RFamide‐related peptide 3 ( Rfrp‐3 ), kisspeptin ( Kiss‐1 ) and gonadotropin‐releasing hormone ( GnRH ), are involved in a photoperiodic pathway that encodes seasonal signals from day length in many vertebrate species. However, the seasonal expression patterns of these genes in wild mammals are less studied. Here, we present a four‐year field investigation to reveal seasonal rhythm and age‐dependent reproductive activity in male Brandt's voles ( Lasiopodomys brandtii ) and to detect relationships among seasonal expression profiles of hypothalamic genes, testicular activity, age and annual day length. From breeding season (April) to nonbreeding season (October), adult male voles displayed a synchronous peak in gonadal activity with annual day length around summer solstice, which was jointly caused by age structure shifts and age‐dependent gonadal development patterns. Overwintered males maintained reproductive activity until late in the breeding season, whereas most newborn males terminated gonadal development completely, except for a minority of males born early in spring. Consistently, the synchronous and opposite expression profiles of Dio2/3 suggest their central function to decode photoperiodic signals and to predict the onset of the nonbreeding season. Moreover, changes in Dio2/3 signals may guide the actions of Kiss‐1 and Rfrp‐3 to regulate the age‐dependent divergence of reproductive strategy in wild Brandt's vole. Our results provide evidence on how hypothalamic photoperiod genes regulate seasonal breeding in a natural rodent population.

Structure and features of the complete chloroplast genome of Melastoma dodecandrum - Xiasheng Zheng; Changwei Ren; Song Huang; Jing Li; Ying Zhao (Physiology and Molecular Biology of Plants, 2019)

PARK14 (D331Y) PLA2G6 Causes Early-Onset Degeneration of Substantia Nigra Dopaminergic Neurons by Inducing Mitochondrial Dysfunction, ER Stress, Mitophagy Impairment and Transcriptional Dysregulation in a Knockin Mouse Model - Ching-Chi Chiu; Chin-Song Lu; Yi-Hsin Weng; Ying-Ling Chen; Ying-Zu Huang; Rou-Shayn Chen; Yi-Chuan Cheng; Yin-Cheng Huang; Yu-Chuan Liu; Szu-Chia Lai; Kun-Jun Lin; Yan-Wei Lin; et al. (Molecular Neurobiology, 2019)

iTRAQ-based proteomic analysis of resistant Nicotiana tabacum in response to Bemisia tabaci infestation - Song-tao Zhang; Yue Long; Song-jie Zhang; Ning Li; De-xin Chen; Hong-fang Jia; Hong-ying Zhang; Yong-xia Yang (Arthropod-Plant Interactions, 2019)

Transcriptome analysis of Panax zingiberensis identifies genes encoding oleanolic acid glucuronosyltransferase involved in the biosynthesis of oleanane-type ginsenosides - Qing-Yan Tang; Geng Chen; Wan-Ling Song; Wei Fan; Kun-Hua Wei; Si-Mei He; Guang-Hui Zhang; Jun-Rong Tang; Ying Li; Yuan Lin; Sheng-Chao Yang (Planta, 2019)

A new12-membered lactone from the stems of Ficus auriculata - Tai-Ming Shao; Cai-Juan Zheng; Xiao-Bao Li; Guang-Ying Chen; Xiao-Ping Song; Chang-Ri Han (Natural Product Research, 2018)

The Dysfunction of the Cerebellum and Its Cerebellum-Reward-Sensorimotor Loops in Chronic Spontaneous Urticaria - Yuming Wang; Jiliang Fang; Ping Song; Yan Bao; Wenwen Song; Jiao Liu; Courtney Lang; Kristen Jorgenson; Minyoung Jung; Dong Shen; Shasha Li; Ruirui Sun; et al. (The Cerebellum, 2018)

Feasibility Investigation of 3D Printing Technology for Geotechnical Physical Models: Study of Tunnels - Leibo Song; Quan Jiang; Ying-En Shi; Xia-Ting Feng; Yuanhui Li; Fangsheng Su; Chang Liu (Rock Mechanics and Rock Engineering, 2018)

Co-targeting PLK1 and mTOR induces synergistic inhibitory effects against esophageal squamous cell carcinoma - Ting-Ting Liu; Kai-Xia Yang; Jing Yu; Ying-Ya Cao; Jian-Song Ren; Jia-Jie Hao; Bei-Qing Pan; Sai Ma; Li-Yan Yang; Yan Cai; Ming-Rong Wang; Yu Zhang (Journal of Molecular Medicine, 2018)

Autophagic Modulation by Trehalose Reduces Accumulation of TDP-43 in a Cell Model of Amyotrophic Lateral Sclerosis via TFEB Activation - Ying Wang; Feng-Tao Liu; Yi-Xuan Wang; Rong-Yuan Guan; Chen Chen; Da-Ke Li; Lu-Lu Bu; Jie Song; Yu-Jie Yang; Yi Dong; Yan Chen; Jian Wang (Neurotoxicity Research, 2018)

Pre-Injection of Small Interfering RNA (siRNA) Promotes c-Jun Gene Silencing and Decreases the Survival Rate of Axotomy-Injured Spinal Motoneurons in Adult Mice - Ying-qin Li; Fa-huan Song; Ke Zhong; Guang-yin Yu; Prince Last Mudenda Zilundu; Ying-ying Zhou; Rao Fu; Ying Tang; Ze-min Ling; Xiaoying Xu; Li-hua Zhou (Journal of Molecular Neuroscience, 2018)

Variable hydrological effects of herbs and shrubs in the arid northeastern Qinghai-Tibet Plateau, China - Ya-bin Liu; Ying Zhang; Jiang-tao Fu; Dong-mei Yu; Xia-song Hu; Xi-lai Li; Zhao-xin Qi; Shu-xia Li (Journal of Mountain Science, 2018)

Focusing quorum sensing signalling by nano‐magnetic assembly - Yongguang Guan; Chen‐Yu Tsao; David N. Quan; Ying Li; Lei Mei; Yingying Song; Boce Zhang; Yi Liu; Gregory F. Payne; William E. Bentley; Qin Wang (Environmental Microbiology, 2018)
Summary Quorum sensing (QS) exists widely among bacteria, enabling a transition to multicellular behaviour after bacterial populations reach a particular density. The coordination of multicellularity enables biotechnological application, dissolution of biofilms, coordination of virulence, and so forth. Here, a method to elicit and subsequently disperse multicellular behaviour among QS‐negative cells is developed using magnetic nanoparticle assembly. We fabricated magnetic nanoparticles (MNPs, ∼5 nm) that electrostatically collect wild‐type (WT) Escherichia coli BL21 cells and brings them into proximity of bioengineered E. coli [CT104 (W3110 lsrFG − luxS − pCT6 + pET‐DsRed)] reporter cells that exhibit a QS response after receiving autoinducer‐2 (AI‐2). By shortening the distance between WT and reporter cells (e.g., increasing local available AI‐2 concentrations), the QS response signalling was amplified four‐fold compared to that in native conditions without assembly. This study suggests potential applications in facilitating intercellular communication and modulating multicellular behaviours based on user‐specified designs.

Characterization of the complete sequences and stability of plasmids carrying the genes aac(6′)-Ib-cr or qnrS in Shigella flexneri in the Hangzhou area of China - Xiao-Ying Pu; Yaming Gu; Jun Li; Shu-Juan Song; Zhe Lu (World Journal of Microbiology and Biotechnology, 2018)

Functional analysis of amino acids at stalk/head interface of human parainfluenza virus type 3 hemagglutinin-neuraminidase protein in the membrane fusion process - Jingjing Jiang; Hongling Wen; Miaomiao Chi; Ying Liu; Jingxue Liu; Zhankui Cao; Li Zhao; Yanyan Song; Na Liu; Lianli Chi; Zhiyu Wang (Virus Genes, 2018)

Insights into the redox components of dissolved organic matters during stabilization process - Ying Yuan; Bei-Dou Xi; Xiao-Song He; Yan Ma; Hui Zhang; Dan Li; Xin-Yu Zhao (Environmental Science and Pollution Research, 2018)

Displacement and Dissolution Characteristics of CO $$_{2}$$ 2 /Brine System in Unconsolidated Porous Media - Lanlan Jiang; Minghao Yu; Ying Teng; Mingjun Yang; Yu Liu; Weizhong Li; Yongchen Song (Transport in Porous Media, 2018)

Mutation screening of Chinese Treacher Collins syndrome patients identified novel TCOF1 mutations - Ying Chen; Luo Guo; Chen-long Li; Jing Shan; Hai-song Xu; Jie-ying Li; Shan Sun; Shao-juan Hao; Lei Jin; Gang Chai; Tian-yu Zhang (Molecular Genetics and Genomics, 2018)

Intramuscular Delivery of scAAV9-hIGF1 Prolongs Survival in the hSOD1G93A ALS Mouse Model via Upregulation of D-Amino Acid Oxidase - HuiQian Lin; HaoJie Hu; WeiSong Duan; YaLing Liu; GuoJun Tan; ZhongYao Li; YaKun Liu; BinBin Deng; XueQin Song; Wan Wang; Di Wen; Ying Wang; et al. (Molecular Neurobiology, 2018)

Effect of corticosteroids on atrial fibrillation after catheter ablation: a meta-analysis - Sanjay Jaiswal; Xian-bao Liu; Qu-cheng Wei; Ying-hao Sun; Li-han Wang; Liu-guang Song; Dan-dan Yang; Jian-an Wang (Journal of Zhejiang University-SCIENCE B, 2018)

Genome sequencing and phylogenetic analysis of Banna virus (genus Seadornavirus, family Reoviridae) isolated from Culicoides - Song Song; Yuanyuan Li; Shihong Fu; Wenwen Lei; Xiaofang Guo; Yun Feng; Xiaoyan Gao; Xiaolong Li; Zhonghua Yang; Ziqian Xu; Ying He; Huanyu Wang; et al. (Science China Life Sciences, 2017)

ZIKA virus isolated from mosquitoes: a field and laboratory investigation in China, 2016 - Shihong Fu; Song Song; Hong Liu; Yuanyuan Li; Xiaolong Li; Xiaoyan Gao; Ziqian Xu; Guoping Liu; Dingming Wang; Zhenzao Tian; Jingzhu Zhou; Ying He; et al. (Science China Life Sciences, 2017)

Carbon balance under four double-season cropping systems in North China Plain - Jian Song; Yan Hui; Chengde Yu; Qian Zhang; Yaqiong Zhou; Ying Li; Xianghui Liu; Lili Zhu; Dafeng Hui; Shiqiang Wan (Plant and Soil, 2017)

Let-7d microRNA Attenuates 6-OHDA-Induced Injury by Targeting Caspase-3 in MN9D Cells - Li Li; Hui Liu; Haijing Song; Yingsong Qin; Ying Wang; Ming Xu; Chaoxia Liu; Jin Gao; Shen Sun (Journal of Molecular Neuroscience, 2017)

Fertility outcomes in infertile women with complex hyperplasia or complex atypical hyperplasia who received progestin therapy and in vitro fertilization - Miao Li; Jia-lun Song; Ying Zhao; She-ling Wu; Hong-bin Liu; Rong Tang; Lei Yan (Journal of Zhejiang University-SCIENCE B, 2017)

Two new phenolic glycosides from the stem of Zanthoxylum armatum DC - Tao Guo; Li-Ping Dai; Xiao-Feng Tang; Tong-Tong Song; Ya Wang; Ai-Hong Zhao; Ying-Ying Cao; Jun Chang (Natural Product Research, 2017)

A new biphenyl derivative from the mangrove endophytic fungus Phomopsis longicolla HL-2232 - Xiao-Bao Li; Guang-Ying Chen; Rui-Jie Liu; Cai-Juan Zheng; Xin-Ming Song; Chang-Ri Han (Natural Product Research, 2017)

A genetic variant in the placenta-derived MHC class I chain-related gene A increases the risk of preterm birth in a Chinese population - Junjiao Song; Jing Li; Han Liu; Yuexin Gan; Yang Sun; Min Yu; Yongjun Zhang; Fei Luo; Ying Tian; Weiye Wang; Jun Zhang; Julian Little; et al. (Human Genetics, 2017)

Secretory expression of a novel human spermatozoa antigen in E. coli and its application to a protein chip - Ming-zhu Wang; Zhuo-lin Qiu; Xiang-Sheng Cai; Jing-jing Li; Miao-qin She; Yuan-feng Xu; Ying-song Wu (Biotechnology Letters, 2017)

Influence of host tree species on isolation and communities of mycorrhizal and endophytic fungi from roots of a tropical epiphytic orchid, Dendrobium sinense (Orchidaceae) - Xiaoming Wang; Yijia Li; Xiqiang Song; Qianwan Meng; Jie Zhu; Ying Zhao; Wengang Yu (Mycorrhiza, 2017)

Salt-response analysis in two rice cultivars at seedling stage - Yan Liu; Baoxiang Wang; Jian Li; Zhaoqiang Song; Baiguan Lu; Ming Chi; Bo Yang; Jinbo Liu; Ying-Wai Lam; Jiaxu Li; Dayong Xu (Acta Physiologiae Plantarum, 2017)

Changes in Serum Adiponectin in Mice Chronically Exposed to Inorganic Arsenic in Drinking Water - Xuanbo Song; Ying Li; Junqiu Liu; Xiaohong Ji; Lijun Zhao; Yudan Wei (Biological Trace Element Research, 2017)

Effects of salvianolic acid B on L-type calcium channels and myocardial contractility in isolated rat ventricular myocytes and hERG K+ channels expressed in HEK293 cells - Qiongtao Song; Xue Han; Yuchong Xue; Tao Song; Xi Chu; Xuan Zhang; Yuanyuan Zhang; Ying Zhang; Jianping Zhang; Li Chu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2017)

miR-30a-5p enhances paclitaxel sensitivity in non-small cell lung cancer through targeting BCL-2 expression - Xiaojie Xu; Shuai Jin; Yongfu Ma; Zhongyi Fan; Zhifeng Yan; Wenchao Li; Qi Song; Wenye You; Zhaohui Lyu; Yeqiong Song; Pingan Shi; Ying Liu; et al. (Journal of Molecular Medicine, 2017)

A new norsesquiterpene from the roots of Polyalthia laui - Zhang-Xin Yu; Ming-Ye Zhuo; Xiao-Bao Li; Yan-Hui Fu; Guang-Ying Chen; Xiao-Ping Song; Chang-Ri Han; Xin-Ming Song; Qi-Jing Fan (Natural Product Research, 2017)

A WRF-based engineering wind field model for tropical cyclones and its applications - Lin Xue; Ying Li; Lili Song; Wenchao Chen; Binglan Wang (Natural Hazards, 2017)

The response and osmotic pressure regulation mechanism of Haliotis discus hannai (Mollusca, Gastropoda) to sudden salinity changes - Xiaolong Gao; Yong Li; Xian Li; Fucun Wu; Changbin Song; Ying Liu (Hydrobiologia, 2017)

Effect of phosphate additive on the nitrogen transformation during pig manure composting - Juan Wu; Shengzhou He; Ying Liang; Guoxue Li; Song Li; Shili Chen; Faisal Nadeem; Jingwei Hu (Environmental Science and Pollution Research, 2017)

One new lignan derivative from the Combretum alfredii Hance - Meng Bai; Li-Jun Wu; Yue Cai; Shou-Yuan Wu; Xiao-Ping Song; Guang-Ying Chen; Cai-Juan Zheng; Chang-Ri Han (Natural Product Research, 2017)

Highly undersampled MR image reconstruction using an improved dual-dictionary learning method with self-adaptive dictionaries - Jiansen Li; Ying Song; Zhen Zhu; Jun Zhao (Medical & Biological Engineering & Computing, 2017)

RNAi as a tool to control the sex ratio of mouse offspring by interrupting Zfx/Zfy genes in the testis - YongSheng Zhang; JiFeng Xi; Bin Jia; XiangZu Wang; XuHai Wang; ChaoCheng Li; YaQiang Li; XianCun Zeng; RuiWen Ying; Xin li; Song Jiang; FangYuan Yuan (Mammalian Genome, 2017)

Aminopeptidase N5 (APN5) as a Putative Functional Receptor of Cry1Ac Toxin in the Larvae of Athetis lepigone - Li-yu Wang; Shao-hua Gu; Zi-yan Nangong; Ping Song; Qin-ying Wang (Current Microbiology, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

A Review of the Functional and Anatomical Default Mode Network in Schizophrenia - Mao-Lin Hu; Xiao-Fen Zong; J. John Mann; Jun-Jie Zheng; Yan-Hui Liao; Zong-Chang Li; Ying He; Xiao-Gang Chen; Jin-Song Tang (Neuroscience Bulletin, 2017)

Prediction of primary climate variability modes at the Beijing Climate Center - Hong-Li Ren; Fei-Fei Jin; Lianchun Song; Bo Lu; Ben Tian; Jinqing Zuo; Ying Liu; Jie Wu; Chongbo Zhao; Yu Nie; Peiqun Zhang; Jin Ba; et al. (Journal of Meteorological Research, 2017)

Global water vapor content decreases from 2003 to 2012: An analysis based on MODIS data - Kebiao Mao; Jingming Chen; Zhaoliang Li; Ying Ma; Yang Song; Xuelan Tan; Kaixian Yang (Chinese Geographical Science, 2017)

Altered Resting-State Signals in Patients with Acute Stroke In or Under the Thalamus - Lijun Chen; Chuanfu Li; Jian Zhai; Anqin Wang; Qin Song; Ying Liu; Ru Ma; Long Han; Yamikani Ndasauka; Xiaoming Li; Hai Li; Xiaochu Zhang (Neuroscience Bulletin, 2016)

Sublethal and transgenerational effects of sulfoxaflor on the biological traits of the cotton aphid, Aphis gossypii Glover (Hemiptera: Aphididae) - Xuewei Chen; Kangsheng Ma; Fen Li; Pingzhuo Liang; Ying Liu; Tianfeng Guo; Dunlun Song; Nicolas Desneux; Xiwu Gao (Ecotoxicology, 2016)

Microsatellite records for volume 8, issue 4 - Alejandra Paola Ojeda; Alexandre Wagner Silva Hilsdorf; Ana Caroline Leite; Ao-ao Yang; Ayako Izuno; Chongbo He; Chun-ya Zhou; Daisuke Kyogoku; Danilo Caneppele; Dongmei Zhu; Fernando Stopato da Fonseca; Hao Yin; et al. (Conservation Genetics Resources, 2016)

One new berberine from the branches and leaves of Polyalthia obliqua Hook.f. & Thomson - Li-Jun Wu; Cai-Juan Zheng; Liu-Kai Wang; Chang-Ri Han; Xiao-Ping Song; Guang-Ying Chen; Xue-ming Zhou; Shou-yuan Wu; Xiao-bao Li; Meng Bai; Chun-xin Liu; Jun Yao (Natural Product Research, 2016)

MYCN-mediated miR-21 overexpression enhances chemo-resistance via targeting CADM1 in tongue cancer - Guopei Zheng; Nan Li; Xiaoting Jia; Cong Peng; Liyun Luo; Yingen Deng; Jiang Yin; Ying Song; Hao Liu; Minying Lu; Zhijie Zhang; Yixue Gu; et al. (Journal of Molecular Medicine, 2016)

Erratum to: Thermo-Sensitive Liposome co-Loaded of Vincristine and Doxorubicin Based on Their Similar Physicochemical Properties had Synergism on Tumor Treatment - Mingyuan Li; Zhiping Li; Yang Yang; Zhiyuan Wang; Zhenbo Yang; Bingsheng Li; Xiangyang Xie; Jinwen Song; Hui Zhang; Ying Li; Guangyu Gao; Jingyuan Yang; et al. (Pharmaceutical Research, 2016)

Metabolic engineering of Corynebacterium glutamicum for methionine production by removing feedback inhibition and increasing NADPH level - Ying Li; Hua Cong; Bingnan Liu; Jinzhu Song; Xueying Sun; Junzheng Zhang; Qian Yang (Antonie van Leeuwenhoek, 2016)

Thermo-Sensitive Liposome co-Loaded of Vincristine and Doxorubicin Based on Their Similar Physicochemical Properties had Synergism on Tumor Treatment - Mingyuan Li; Zhiping Li; Yang Yang; Zhiyuan Wang; Zhenbo Yang; Bingsheng Li; Xiangyang Xie; Jinwen Song; Hui Zhang; Ying Li; Guangyu Gao; Jingyuan Yang; et al. (Pharmaceutical Research, 2016)

Enhanced Neuroprotection of Acetyl-11-Keto-β-Boswellic Acid (AKBA)-Loaded O-Carboxymethyl Chitosan Nanoparticles Through Antioxidant and Anti-Inflammatory Pathways - Yi Ding; Youbei Qiao; Min Wang; Huinan Zhang; Liang Li; Yikai Zhang; Jie Ge; Ying Song; Yuwen Li; Aidong Wen (Molecular Neurobiology, 2016)

Characterization of CDOM from urban waters in Northern-Northeastern China using excitation-emission matrix fluorescence and parallel factor analysis - Ying Zhao; Kaishan Song; Sijia Li; Jianhang Ma; Zhidan Wen (Environmental Science and Pollution Research, 2016)

A pilot study on using chlorine dioxide gas for disinfection of gastrointestinal endoscopes - Ying Yi; Li-mei Hao; Shu-ren Ma; Jin-hui Wu; Tao Wang; Song Lin; Zong-xing Zhang; Jian-cheng Qi (Journal of Zhejiang University-SCIENCE B, 2016)

Enhanced short-cut nitrification in an airlift reactor by CaCO3 attachment on biomass under high bicarbonate condition - Mohammad Ali; Li-Yuan Chai; Hai-Ying Wang; Chong-Jian Tang; Xiao-Bo Min; Xu Yan; Cong Peng; Yu-Xia Song; Ping Zheng (Biodegradation, 2016)

Liposomes as a Novel Ocular Delivery System for Brinzolamide: In Vitro and In Vivo Studies - Huili Li; Yongmei Liu; Ying Zhang; Dailong Fang; Bei Xu; Lijing Zhang; Tong Chen; Ke Ren; Yu Nie; Shaohua Yao; Xiangrong Song (AAPS PharmSciTech, 2016)

Inverse Association Between Serum Uric Acid Levels and Alzheimer’s Disease Risk - Na Du; Donghua Xu; Xu Hou; Xuejia Song; Cancan Liu; Ying Chen; Yangang Wang; Xin Li (Molecular Neurobiology, 2016)

A Fluorescence Immunochromatographic Assay Using Europium (III) Chelate Microparticles for Rapid, Quantitative and Sensitive Detection of Creatine Kinase MB - Xiao-Hong Lai; Rong-Liang Liang; Tian-Cai Liu; Zhi-Ning Dong; Ying-Song Wu; Lin-Hai Li (Journal of Fluorescence, 2016)

Characterizing the compositional variation of dissolved organic matter over hydrophobicity and polarity using fluorescence spectra combined with principal component analysis and two-dimensional correlation technique - Ben-Sheng Su; Zhen Qu; Xiao-Song He; Ying-Hao Song; Li-Min Jia (Environmental Science and Pollution Research, 2016)

Ammonium removal of drinking water at low temperature by activated carbon filter biologically enhanced with heterotrophic nitrifying bacteria - Wen Qin; Wei-Guang Li; Duo-Ying Zhang; Xiao-Fei Huang; Yang Song (Environmental Science and Pollution Research, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Advanced oxidation protein products induce chondrocyte apoptosis via receptor for advanced glycation end products-mediated, redox-dependent intrinsic apoptosis pathway - Qian Wu; Zhao-Ming Zhong; Si-Yuan Zhu; Cong-Rui Liao; Ying Pan; Ji-Huan Zeng; Shuai Zheng; Ruo-Ting Ding; Qing-Song Lin; Qing Ye; Wen-Bin Ye; Wei Li; et al. (Apoptosis, 2016)

A novel large deletion mutation of FERMT1 gene in a Chinese patient with Kindler syndrome - Ying Gao; Jin-li Bai; Xiao-yan Liu; Yu-jin Qu; Yan-yan Cao; Jian-cai Wang; Yu-wei Jin; Hong Wang; Fang Song (Journal of Zhejiang University-SCIENCE B, 2015)

Betacellulin ameliorates hyperglycemia in obese diabetic db/db mice - Yoon Sin Oh; Seungjin Shin; Hui Ying Li; Eun-Young Park; Song Mi Lee; Cheol Soo Choi; Yong Lim; Hye Seung Jung; Hee-Sook Jun (Journal of Molecular Medicine, 2015)

Transcriptome profiling of trichome-less reveals genes associated with multicellular trichome development in Cucumis sativus - Jun-Long Zhao; Yun-Li Wang; Dan-Qing Yao; Wen-Ying Zhu; Long Chen; Huan-Le He; Jun-Song Pan; Run Cai (Molecular Genetics and Genomics, 2015)

Effect of Zn stresses on physiology, growth, Zn accumulation, and chlorophyll of Phyllostachys pubescen s - Danli Peng; Mohammad Shafi; Ying Wang; Song Li; Wenbo Yan; Junren Chen; Zhengqian Ye; Dan Liu (Environmental Science and Pollution Research, 2015)

Protective effect of L-carnitine in cyclophosphamide-induced germ cell apoptosis - Bin Zhu; Yan-fei Zheng; Yue-ying Zhang; Yun-song Cao; Lei Zhang; Xin-gang Li; Teng Liu; Zhao-zhu Jiao; Qi Wang; Zhi-gang Zhao (Journal of Zhejiang University-SCIENCE B, 2015)

Overexpression of the Monodehydroascorbate Reductase Gene from Non-heading Chinese Cabbage Reduces Ascorbate Level and Growth in Transgenic Tobacco - Jun Ren; Weike Duan; Zhongwen Chen; Shuo Zhang; Xiaoming Song; Tongkun Liu; Xilin Hou; Ying Li (Plant Molecular Biology Reporter, 2015)

Assessing the early changes of cerebral glucose metabolism via dynamic 18FDG-PET/CT during cardiac arrest - Ying-Qing Li; Xiao-Xing Liao; Jian-Hua Lu; Rong Liu; Chun-Lin Hu; Gang Dai; Xiang-Song Zhang; Xin-Chong Shi; Xin Li (Metabolic Brain Disease, 2015)

Age, petrogenesis and tectonic significance of the ferrobasalts in the Chagangnuoer iron deposit, western Tianshan - Ning-Bo Li; He-Cai Niu; Xing-Chun Zhang; Qiao-Song Zeng; Qiang Shan; Cong-Ying Li; Shuang Yan; Wu-Bin Yang (International Geology Review, 2015)

P2X7 receptor of rat dorsal root ganglia is involved in the effect of moxibustion on visceral hyperalgesia - Shuangmei Liu; Qingming Shi; Qicheng Zhu; Ting Zou; Guilin Li; An Huang; Bing Wu; Lichao Peng; Miaomiao Song; Qin Wu; Qiuyu Xie; Weijian Lin; et al. (Purinergic Signalling, 2015)

CRISPR/Cas9 Systems: The Next Generation Gene Targeted Editing Tool - Shengchun Guo; Ying Lv; Yuxiang Lin; Kaixuan Lin; Peng Peng; Yangxiu Wu; Jingli Peng; Shaoyun Song; Zhining Li; Qiuyun Liu (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2015)

Establishment and maintenance of a standardized glioma tissue bank: Huashan experience - Abudumijiti Aibaidula; Jun-feng Lu; Jin-song Wu; He-jian Zou; Hong Chen; Yu-qian Wang; Zhi-yong Qin; Yu Yao; Ye Gong; Xiao-ming Che; Ping Zhong; Shi-qi Li; et al. (Cell and Tissue Banking, 2015)

Induction and development of microspore-derived embryos in broccoli × white-headed cabbage hybrids microspore culture - Aisong Zeng; Jiyong Yan; Lixiao Song; Bing Gao; Yunxia Zhang; Jianqi Li; Huanhuan Liu; Xilin Hou; Ying Li (Euphytica, 2015)

Deletion of d-ribulose-5-phosphate 3-epimerase (RPE1) induces simultaneous utilization of xylose and glucose in xylose-utilizing Saccharomyces cerevisiae - Ming-Hua Shen; Hao Song; Bing-Zhi Li; Ying-Jin Yuan (Biotechnology Letters, 2015)

Genome-wide identification of phenolic acid biosynthetic genes in Salvia miltiorrhiza - Bo Wang; Wei Sun; Qiushi Li; Ying Li; Hongmei Luo; Jingyuan Song; Chao Sun; Jun Qian; Yingjie Zhu; Alice Hayward; Haibin Xu; Shilin Chen (Planta, 2015)

Significantly Decreased and More Variable Expression of Major CYPs and UGTs in Liver Microsomes Prepared from HBV-Positive Human Hepatocellular Carcinoma and Matched Pericarcinomatous Tissues Determined Using an Isotope Label-free UPLC-MS/MS Method - Tongmeng Yan; Song Gao; Xiaojuan Peng; Jian Shi; Cong Xie; Qiang Li; Linlin Lu; Ying Wang; Fuyuan Zhou; Zhongqiu Liu; Ming Hu (Pharmaceutical Research, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Three-dimensional tensor controlled-source electromagnetic modeling based on the vector finite-element method - Ying-Cai Hu; Tong-Lin Li; Cui-Song Fan; Da-Yong Wang; Jian-Ping Li (Applied Geophysics, 2015)

Accumulation and localization of cadmium in moso bamboo (Phyllostachys pubescens) grown hydroponically - Song Li; Ejazul Islam; Danli Peng; Junren Chen; Ying Wang; Jiasen Wu; Zhengqian Ye; Wenbo Yan; Kouping Lu; Dan Liu (Acta Physiologiae Plantarum, 2015)

Genome-wide analysis of the MADS-box gene family in Brassica rapa (Chinese cabbage) - Weike Duan; Xiaoming Song; Tongkun Liu; Zhinan Huang; Jun Ren; Xilin Hou; Ying Li (Molecular Genetics and Genomics, 2015)

Design and applications of bifunctional cinnamide derivatives as potential antimycobacterial agents with few hepatotoxic effects - Zheng-Rong Wu; De-Juan Zhi; Li-Fang Zheng; Jian-Ying Li; Yang Li; Qing-Jian Xie; Na Feng; Yan-Fang Bao; Qi-Yu Gao; Ying Song; Hong-Yu Li (Medicinal Chemistry Research, 2015)

Contamination of commercially available seafood by key diarrhetic shellfish poisons along the coast of China - Chao Lin; Zeng-Shan Liu; Cai-Yun Tan; Yi-Ping Guo; Lin Li; Hong-Lin Ren; Yan-Song Li; Pan Hu; Sheng Gong; Yu Zhou; Shi-Ying Lu (Environmental Science and Pollution Research, 2015)

Isolation and genetic characterization of avian influenza virus H4N6 from ducks in China - Xiao-yuan Yuan; You-ling Wang; Ke-Xiang Yu; Yu-xia Zhang; Huai-ying Xu; Jin-xing Yang; Feng Li; Min-xun Song (Archives of Virology, 2015)

The Expression of CAP1 After Traumatic Brain Injury and Its Role in Astrocyte Proliferation - Haiyan Zhang; Yonghua Liu; Yao Li; Ying Zhou; Dongjian Chen; Jianhong Shen; Yaohua Yan; Song Yan; Xinmin Wu; Aihong Li; Aisong Guo; Chun Cheng (Journal of Molecular Neuroscience, 2014)

Hypouricemic Actions of Exopolysaccharide Produced by Cordyceps militaris in Potassium Oxonate-Induced Hyperuricemic Mice - Li Ma; Song Zhang; Ying Yuan; Jianhua Gao (Current Microbiology, 2014)

Genome-Wide Analysis and Expression Patterns of NAC Transcription Factor Family Under Different Developmental Stages and Abiotic Stresses in Chinese Cabbage - Tongkun Liu; Xiaoming Song; Weike Duan; Zhinan Huang; Gaofeng Liu; Ying Li; Xilin Hou (Plant Molecular Biology Reporter, 2014)

Expression, cloning, and IgE-binding of the full-length dust mite allergen Der f 8 - Yu-bao Cui; Ying Zhou; Nan Wang; Fei-xiang Teng; Li-li Yu; Yong-hua Bian; Jin-xia Song; Li Yang; Cheng-bo Zhang (Immunologic Research, 2014)

Assessment of dietary phytoestrogen intake via plant-derived foods in China - Xiao Juan Hu; Wan Rui Song; Li Ying Gao; Shao Ping Nie; Gerhard Eisenbrand; Ming Yong Xie (Food Additives & Contaminants: Part A, 2014)

Genome-wide identification, classification and expression analysis of the heat shock transcription factor family in Chinese cabbage - Xiaoming Song; Gaofeng Liu; Weike Duan; Tongkun Liu; Zhinan Huang; Jun Ren; Ying Li; Xilin Hou (Molecular Genetics and Genomics, 2014)

Correlation of the UGT1A4 gene polymorphism with serum concentration and therapeutic efficacy of lamotrigine in Han Chinese of Northern China - Ying Chang; Li-ya Yang; Meng-chao Zhang; Song-Yan Liu (European Journal of Clinical Pharmacology, 2014)

A novel deletion mutation of the ADAR1 gene in a Chinese patient with dyschromatosis symmetrica hereditaria - WEI-WEI LI; QIU-YUE WU; NA LI; DE-QUAN DENG; RU-SONG ZHANG; YING-XIA CUI; XIAO-JUN LI; XIN-YI XIA (Journal of Genetics, 2014)

A Novel Risk Haplotype of ALOX5AP Gene is Associated with Ischemic Stroke in Chinese Han Population - Dongzhi Yang; Ying He; Manyu Li; Congcong Shi; Guoying Song; Qing Wang; Yujia Fan; Qingchuan Feng; Hong Zheng (Journal of Molecular Neuroscience, 2014)

Differential necrotic lesion formation in soybean cultivars in response to soybean mosaic virus - Kai Zhang; Ying Pei Song; Yu Wang; Kai Li; Le Gao; Yong Kun Zhong; A. Karthikeyan; Hai Jian Zhi (European Journal of Plant Pathology, 2014)

Characterizing the heavy metal-complexing potential of fluorescent water-extractable organic matter from composted municipal solid wastes using fluorescence excitation–emission matrix spectra coupled with parallel factor analysis - Xiao-Song He; Bei-Dou Xi; Hong-Wei Pan; Xiang Li; Dan Li; Dong-Yu Cui; Wen-Bin Tang; Ying Yuan (Environmental Science and Pollution Research, 2014)

Functionalized Magnetic Microparticles for Fast and Efficient Removal of Textile Dyes from Aqueous Solution - Qing-Song Zhao; Yan-Feng Huang; Ying Li; Ji-Mei Zhang; Hong-Yi Wang (Water, Air, & Soil Pollution, 2014)

Instability in mitochondrial membranes in Polima cytoplasmic male sterility of Brassica rapa ssp. chinensis - Ying Li; Tongkun Liu; Weike Duan; Xiaoming Song; Gongjun Shi; Jingyi Zhang; Xiaohui Deng; Shuning Zhang; Xilin Hou (Functional & Integrative Genomics, 2014)

Effect of bone marrow-derived CD11b+F4/80+ immature dendritic cells on the balance between pro-inflammatory and anti-inflammatory cytokines in DBA/1 mice with collagen-induced arthritis - Jingjing Fu; Lingling Zhang; Shanshan Song; Kangliang Sheng; Ying Li; Peipei Li; Shasha Song; Qingtong Wang; Jianhong Chu; Wei Wei (Inflammation Research, 2014)

Identification of BACH2 as a susceptibility gene for Graves’ disease in the Chinese Han population based on a three-stage genome-wide association study - Wei Liu; Hai-Ning Wang; Zhao-Hui Gu; Shao-Ying Yang; Xiao-Ping Ye; Chun-Ming Pan; Shuang-Xia Zhao; Li-Qiong Xue; Hui-Jun Xie; Sha-Sha Yu; Cui-Cui Guo; Wen-Hua Du; et al. (Human Genetics, 2014)

17β-Estradiol protects against apoptosis induced by levofloxacin in rat nucleus pulposus cells by upregulating integrin α2β1 - Si-Dong Yang; Lei Ma; Ti-Xin Gu; Wen-Yuan Ding; Feng Zhang; Yong Shen; Ying-Ze Zhang; Da-Long Yang; Di Zhang; Ya-Peng Sun; Yan-Li Song (Apoptosis, 2014)

Identification of the substrate recognition region in the Δ6-fatty acid and Δ8-sphingolipid desaturase by fusion mutagenesis - Li-Ying Song; Yan Zhang; Shu-Fen Li; Jun Hu; Wei-Bo Yin; Yu-Hong Chen; Shan-Ting Hao; Bai-Lin Wang; Richard R.-C. Wang; Zan-Min Hu (Planta, 2014)

cDNA Clones and Expression Analysis of cpHSC70 and mtHSC70 in Non-Heading Chinese Cabbage - Hongbing Song; Xiaoming Song; Huanhuan Liu; Tongkun Liu; Ying Li; Xilin Hou (Plant Molecular Biology Reporter, 2014)

CRP Gene polymorphism contributes genetic susceptibility to dyslipidemia in Han Chinese population - Wenbin Wei; Song Yang; Yingru Qiu; Hairu Wang; Xianghai Zhao; Yanping Zhao; Yun Li; Ming Wu; Yanchun Chen; Wen Wang; Xiaoming Shi; Sijun Liu; et al. (Molecular Biology Reports, 2014)

Major QTLs reduce the deleterious effects of high temperature on rice amylose content by increasing splicing efficiency of Wx pre-mRNA - Hua Zhang; Lian Duan; Ji-Song Dai; Chang-Quan Zhang; Juan Li; Ming-Hong Gu; Qiao-Quan Liu; Ying Zhu (Theoretical and Applied Genetics, 2014)

Genome-wide analysis of the bHLH transcription factor family in Chinese cabbage (Brassica rapa ssp. pekinensis) - Xiao-Ming Song; Zhi-Nan Huang; Wei-Ke Duan; Jun Ren; Tong-Kun Liu; Ying Li; Xi-Lin Hou (Molecular Genetics and Genomics, 2014)

The effect of lansoprazole, an OCT inhibitor, on metformin pharmacokinetics in healthy subjects - Yi Ding; YanYan Jia; Ying Song; ChengTao Lu; YuWen Li; MinChun Chen; MingMing Wang; AiDong Wen (European Journal of Clinical Pharmacology, 2014)

A meta-analysis of the association between induced abortion and breast cancer risk among Chinese females - Yubei Huang; Xiaoliang Zhang; Weiqin Li; Fengju Song; Hongji Dai; Jing Wang; Ying Gao; Xueou Liu; Chuan Chen; Ye Yan; Yaogang Wang; Kexin Chen (Cancer Causes & Control, 2014)

Investigation and integrated molecular diagnosis of root-knot nematodes in Panax notoginseng root in the field - Linlin Dong; Hui Yao; Qiushi Li; Jingyuan Song; Ying Li; Hongmei Luo; Shilin Chen (European Journal of Plant Pathology, 2013)

Overweight and Obesity Associated With Increased Total Serum Calcium Level: Comparison of Cross-sectional Data in the Health Screening for Teaching Faculty - Xiao-hua Ren; Ying-shui Yao; Lian-ping He; Yue-long Jin; Wei-wei Chang; Jie Li; Yan Chen; Xiu-li Song; Hui Tang; Ling-ling Ding; Dao-xia Guo; Chao-ping Li (Biological Trace Element Research, 2013)

Association between SNPs in microRNA-machinery genes and tuberculosis susceptibility in Chinese Tibetan population - Xingbo Song; Siyue Li; MeiLang QuCuo; Yi Zhou; Xin Hu; Juan Zhou; Xiaojun Lu; Jun Wang; Wei Hua; Yuanxin Ye; Binwu Ying; Lanlan Wang (Molecular Biology Reports, 2013)

Discovery of WRKY transcription factors through transcriptome analysis and characterization of a novel methyl jasmonate-inducible PqWRKY1 gene from Panax quinquefolius - Yongzhen Sun; Yunyun Niu; Jiang Xu; Ying Li; Hongmei Luo; Yingjie Zhu; Mingzhu Liu; Qiong Wu; Jingyuan Song; Chao Sun; Shilin Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Remote estimation of phycocyanin (PC) for inland waters coupled with YSI PC fluorescence probe - Kaishan Song; Lin Li; Lenore Tedesco; Nicole Clercin; Bob Hall; Shuai Li; Kun Shi; Dawei Liu; Ying Sun (Environmental Science and Pollution Research, 2013)

QTL mapping and correlation analysis for 1000-grain weight and percentage of grains with chalkiness in rice - JIAN-MIN BIAN; HUAN SHI; CUI-JUAN LI; CHANG-LAN ZHU; QIU-YING YU; XIAO-SONG PENG; JUN-RU FU; XIAO-PENG HE; XIAO-RONG CHEN; LI-FANG HU; LIN-JUAN OUYANG; HAO-HUA HE (Journal of Genetics, 2013)

Synthesis and in vitro antitumor activity of 1-(3-dimethylamino)propyl indolin-2-one derivatives - Kai Lv; Li-Li Wang; Xin-Bo Zhou; Ming-Liang Liu; Hong-Ying Liu; Zhi-Bing Zheng; Song Li (Medicinal Chemistry Research, 2013)

Circulating Tumor Cells (CTCs) Detected by Triple-Marker EpCAM, CK19, and hMAM RT-PCR and Their Relation to Clinical Outcome in Metastatic Breast Cancer Patients - Shu Zhao; Huike Yang; Minghui Zhang; Dekai Zhang; Yupeng Liu; Yan Liu; Ying Song; Xiaosan Zhang; Hongbin Li; Wenjie Ma; Qingyuan Zhang (Cell Biochemistry and Biophysics, 2013)

Erratum to: Low Strength Static Magnetic Field Inhibits the Proliferation, Migration and Adhesion of Human Vascular Smooth Muscle Cells in a Restenosis Model Through Mediating Integrins β1- FAK, Ca2+ Signaling Pathway - Yan Li; Li-Qiang Song; Michael Q. Chen; Ying-Mei Zhang; Jingxia Li; Xu-Yang Feng; Weijie Li; Wenyi Guo; Guoliang Jia; Haichang Wang; Jin Yu (Annals of Biomedical Engineering, 2013)

Analysis of average standardized SSR allele size supports domestication of soybean along the Yellow River - Ying-hui Li; Chen Zhang; Marinus J. M. Smulders; Wei Li; Yan-song Ma; Qu Xu; Ru-zhen Chang; Li-juan Qiu (Genetic Resources and Crop Evolution, 2013)

Influence of Pseudomonas aeruginosa pvdQ Gene on Altering Antibiotic Susceptibility Under Swarming Conditions - Lili Wang; Chunling Zhang; Fengyun Gong; Hongtao Li; Xuhua Xie; Chao Xia; Jia Chen; Ying Song; Aixia Shen; Jianxin Song (Current Microbiology, 2013)

Lipoic acid attenuates the expression of adhesion molecules by increasing endothelial nitric-oxide synthase activity - Hong-Bo Jin; Yong-Bin Yang; Ying-Li Song; Yong-chun Zhang; Yu-Rong Li (Molecular Biology Reports, 2013)

Protective roles of quercetin in acute myocardial ischemia and reperfusion injury in rats - Hong-Bo Jin; Yong-Bin Yang; Ying-Li Song; Yong-chun Zhang; Yu-Rong Li (Molecular Biology Reports, 2012)

Fraction characteristics of rare earth elements in the surface sediment of Bohai Bay, North China - Yayan Xu; Jinming Song; Liqin Duan; Xuegang Li; Huamao Yuan; Ning Li; Peng Zhang; Ying Zhang; Sisi Xu; Mo Zhang; Xiaodan Wu; Xuebo Yin (Environmental Monitoring and Assessment, 2012)

Low Strength Static Magnetic Field Inhibits the Proliferation, Migration, and Adhesion of Human Vascular Smooth Muscle Cells in a Restenosis Model Through Mediating Integrins β1-FAK, Ca2+ Signaling Pathway - Yan Li; Li-Qiang Song; Michael Q. Chen; Ying-Mei Zhang; Jingxia Li; Xu-Yang Feng; Weijie Li; Wenyi Guo; Guoliang Jia; Haichang Wang; Jin Yu (Annals of Biomedical Engineering, 2012)

Association of 10q23 with colorectal cancer in a Chinese population - Fen-Xia Li; Xue-Xi Yang; Xuan-Qiu He; Ni-Ya Hu; Ying-Song Wu; Ming Li (Molecular Biology Reports, 2012)

Functional redundancy of the two 5-hydroxylases in monolignol biosynthesis of Populus trichocarpa: LC–MS/MS based protein quantification and metabolic flux analysis - Jack P. Wang; Christopher M. Shuford; Quanzi Li; Jina Song; Ying-Chung Lin; Ying-Hsuan Sun; Hsi-Chuan Chen; Cranos M. Williams; David C. Muddiman; Ronald R. Sederoff; Vincent L. Chiang (Planta, 2012)

A maize stress-responsive NAC transcription factor, ZmSNAC1, confers enhanced tolerance to dehydration in transgenic Arabidopsis - Min Lu; Sheng Ying; Deng-Feng Zhang; Yun-Su Shi; Yan-Chun Song; Tian-Yu Wang; Yu Li (Plant Cell Reports, 2012)

Production of monoclonal antibody and application in indirect competitive ELISA for detecting okadaic acid and dinophytoxin-1 in seafood - Shi-Ying Lu; Yu Zhou; Yan-Song Li; Chao Lin; Xian-Mei Meng; Dong-Ming Yan; Zhao-Hui Li; Shi-Yu Yu; Zeng-Shan Liu; Hong-Lin Ren (Environmental Science and Pollution Research, 2012)

Molecular characterization and phylogenetic analysis of porcine epidemic diarrhea virus (PEDV) field strains in south China - Zhi-Li Li; Ling Zhu; Jing-Yun Ma; Qing-Feng Zhou; Yan-Hua Song; Bao-Li Sun; Rui-Ai Chen; Qing-Mei Xie; Ying-Zuo Bee (Virus Genes, 2012)

Risk stratification of spontaneous bacterial peritonitis in cirrhosis with ascites based on classification and regression tree analysis - Ke-Qing Shi; Yu-Chen Fan; Li Ying; Xian-Feng Lin; Mei Song; Ling-Fei Li; Xie-Yan Yu; Yong-Ping Chen; Ming-Hua Zheng (Molecular Biology Reports, 2012)

The distribution of organochlorine pesticides (OCPs) in surface sediments of Bohai Sea Bay, China - Yu Liu; Chengwen Song; Ying Li; Yuan Liu; Jinming Song (Environmental Monitoring and Assessment, 2012)

Cloning and characterization of a maize bZIP transcription factor, ZmbZIP72, confers drought and salt tolerance in transgenic Arabidopsis - Sheng Ying; Deng-Feng Zhang; Jing Fu; Yun-Su Shi; Yan-Chun Song; Tian-Yu Wang; Yu Li (Planta, 2012)

Induction of Mitogynogenetic Diploids and Identification of WW Super-female Using Sex-Specific SSR Markers in Half-Smooth Tongue Sole (Cynoglossus semilaevis) - Song-Lin Chen; Xiang-Shan Ji; Chang-Wei Shao; Wen-Long Li; Jing-Feng Yang; Zuo Liang; Xiao-Lin Liao; Gen-Bo Xu; Ying Xu; Wen-Tao Song (Marine Biotechnology, 2012)

Protein sequence analysis based on hydropathy profile of amino acids - Xiao-li Xie; Li-fei Zheng; Ying Yu; Li-ping Liang; Man-cai Guo; John Song; Zhi-fa Yuan (Journal of Zhejiang University-SCIENCE B, 2012)

Human amniotic membrane derived-mesenchymal stem cells induce C6 glioma apoptosis in vivo through the Bcl-2/caspase pathways - Hongliang Jiao; Fangxia Guan; Bo Yang; Jianbin Li; Laijun Song; Xiang Hu; Ying Du (Molecular Biology Reports, 2012)

Association between polymorphisms in the signal transducer and activator of transcription and dilated cardiomyopathy in the Chinese Han population - Ying Peng; Bin Zhou; Yanyun Wang; Yu Chen; Hui Li; Yaping Song; Lin Zhang; Li Rao (Molecular and Cellular Biochemistry, 2012)

The mechanism of mimecan transcription induced by glucocorticoid in pituitary corticotroph cells - Xiao Na Zhang; Li Qiong Xue; He Jiang; Shao Ying Yang; Huai Dong Song; Qin Yun Ma (Molecular and Cellular Biochemistry, 2012)

Association study of single nucleotide polymorphisms in pre-miRNA and rheumatoid arthritis in a Han Chinese population - Bin Yang; Jun Long Zhang; Yun Ying Shi; Dong Dong Li; Jie Chen; Zhuo Chun Huang; Bei Cai; Xing Bo Song; Li Xin Li; Bin Wu Ying; Lan Lan Wang (Molecular Biology Reports, 2011)

Depletion of CD4+CD25+Foxp3+ regulatory T cells with anti-CD25 antibody may exacerbate the 1,3-β-glucan-induced lung inflammatory response in mice - Fangwei Liu; Dong Weng; Ying Chen; Laiyu Song; Cuiying Li; Lei Dong; Yuan Wang; Shasha Tao; Jie Chen (Archives of Toxicology, 2011)

Influence of Pseudomonas aeruginosa pvdQ Gene on Altering Antibiotic Susceptibility Under Swarming Conditions - Lili Wang; Chunling Zhang; Fengyun Gong; Hongtao Li; Xuhua Xie; Chao Xia; Jia Chen; Ying Song; Aixia Shen; Jianxin Song (Current Microbiology, 2011)

Inactivation of the extracytoplasmic function sigma factor Sig6 stimulates avermectin production in Streptomyces avermitilis - Libin Jiang; Yanping Liu; Pan Wang; Ying Wen; Yuan Song; Zhi Chen; Jilun Li (Biotechnology Letters, 2011)

A cDNA Clone of BcHSP81-4 from the Sterility Line (Pol CMS) of Non-heading Chinese Cabbage (Brassica campestris ssp. chinensis) - Tongkun Liu; Xilin Hou; Jingyi Zhang; Yuping Song; Shuning Zhang; Ying Li (Plant Molecular Biology Reporter, 2011)

Cloning and characterization of a maize SnRK2 protein kinase gene confers enhanced salt tolerance in transgenic Arabidopsis - Sheng Ying; Deng-Feng Zhang; Hui-Yong Li; Ying-Hui Liu; Yun-Su Shi; Yan-Chun Song; Tian-Yu Wang; Yu Li (Plant Cell Reports, 2011)

Association of pre-microRNAs genetic variants with susceptibility in systemic lupus erythematosus - Junlong Zhang; Bin Yang; Binwu Ying; Dongdong Li; Yunying Shi; Xingbo Song; Bei Cai; Zhuochun Huang; Yongkang Wu; Lanlan Wang (Molecular Biology Reports, 2011)

Degradation of dye rhodamine B under visible irradiation with Prussian blue as a photo-Fenton reagent - Shou-Qing Liu; Shi Cheng; Li Luo; Hong-Ying Cheng; Song-Jun Wang; Shuai Lou (Environmental Chemistry Letters, 2011)

Fine mapping and analyses of R SC8 resistance candidate genes to soybean mosaic virus in soybean - Dagang Wang; Ying Ma; Yongqing Yang; Ning Liu; Chunyan Li; Yingpei Song; Haijian Zhi (Theoretical and Applied Genetics, 2011)

Silica-supported sulfonic acid-functionalized ionic liquid coated with [bmim][PF6] as a scavenger for the synthesis of amides - Li-Qin Kang; Yue-Qin Cai; Yan-Qing Peng; Xi-Li Ying; Gong-Hua Song (Molecular Diversity, 2011)

Effects of intercropping with aromatic plants on the diversity and structure of an arthropod community in a pear orchard - Bei Zhou Song; Hong Ying Wu; Yun Kong; Jie Zhang; Yan Li Du; Jing Hui Hu; Yun Cong Yao (BioControl, 2010)

Evidence that herpes simplex virus DNA derived from quiescently infected cells in vitro , and latently infected cells in vivo , is physically damaged - Scott Millhouse; Ying-Hsiu Su; Xianchao Zhang; Xiaohe Wang; Benjamin P Song; Li Zhu; Emily Oppenheim; Nigel W Fraser; Timothy M Block (Journal of NeuroVirology, 2010)

Evaluation and Structure-Activity Relationship Study of Acute Toxicity of Naphthoquinones to Photobacterium phosphoreum, Photobacterium T3B - Feng Ding; Jing Guo; Zhen Li; Li Ying Li; Jin Yang Zhang; Jin Hua Zhang; Jie Lian; Wen Hua Song; Lin Zhu (Bulletin of Environmental Contamination and Toxicology, 2010)

Genomic imprinting status of IGF-II and H19 in placentas of fetal growth restriction patients - Ying Wang; Jing Li Fu; Wei Wei Song; Li Li Wang (Journal of Genetics, 2010)

Bovine prolactin promotes the expression of human transferrin in the milk of transgenic mice - Song Li; Xinbing Guo; Xiuli Gong; Miao Xu; Jingbin Yan; Ying Huang; Zhaorui Ren (Biotechnology Letters, 2010)

Elevated CO2 increases energy-use efficiency of invasive Wedelia trilobata over its indigenous congener - Li-Ying Song; Chang-Han Li; Shao-Lin Peng (Biological Invasions, 2010)

Isolation of a new glycoside from starfish, Asterias amurensis Lutken, and its stimulation activity on the proliferation of the UMR106 cell - Hong-Wei Liu; Jian-Kuan Li; Da-Wei Zhang; Jing-Chao Zhang; Xue Zhang; Xiao-Hong Song; Ying Xia; Nai-Li Wang; Xin-Sheng Yao; Guo-Ping Cai (Natural Product Research, 2010)

Change of season-specific telomere lengths in Ginkgo biloba L. - Han Song; Di Liu; Xin Chen; Zehua Ying; Bo Zhang; Fenglan Li; Hai Lu (Molecular Biology Reports, 2010)

Characteristics of the precipitation over the eastern edge of the Tibetan Plateau - Yueqing Li; Dejun Li; Song Yang; Cao Liu; Aihua Zhong; Ying Li (Meteorology and Atmospheric Physics, 2010)

A “GC-rich” method for mammalian gene expression: A dominant role of non-coding DNA GC content in regulation of mammalian gene expression - Qian Jia; HongTao Wu; XingJun Zhou; Jian Gao; Wei Zhao; JouDi Aziz; JingShuang Wei; Lihua Hou; Shuyin Wu; Ying Zhang; XiangFeng Dong; YanMin Huang; et al. (Science China Life Sciences, 2010)

Extended expression of B-class MADS-box genes in the paleoherb Asarum caudigerum - Yin-He Zhao; Michael Möller; Jun-Bo Yang; Ting-Song Liu; Jin-Feng Zhao; Li-Na Dong; Jin-Peng Zhang; Cheng-Yun Li; Guo-Ying Wang; De-Zhu Li (Planta, 2010)

Isolation and Analysis of Rice Rf1-Orthologus PPR Genes Co-segregating with Rf3 in Maize - Xiang-Bo Xu; Zhan-Xian Liu; Deng-Feng Zhang; Ying Liu; Wei-Bin Song; Jian-Sheng Li; Jing-Rui Dai (Plant Molecular Biology Reporter, 2009)

Improvement of chloroperoxidase stability by covalent immobilization on chitosan membranes - Li-Hua Zhang; Chao-Hong Bai; Ying-Song Wang; Yu-Cheng Jiang; Man-Cheng Hu; Shu-Ni Li; Quan-Guo Zhai (Biotechnology Letters, 2009)

Effects of Ethanol on Benzene Degradation Under Denitrifying Conditions - Yaoguo Wu; Yunfeng Li; Lin Hui; Ying Tan; Song Jin (Bulletin of Environmental Contamination and Toxicology, 2009)

Heavy Metal Contamination in a Typical Mining Town of a Minority and Mountain Area, South China - Xin-Ying Zhang; Li-Song Tang; Gan Zhang; Hao-Dong Wu (Bulletin of Environmental Contamination and Toxicology, 2009)

Response of antioxidant activity to excess copper in two cultivars of Brassica campestris ssp. chinensis Makino - Ying Li; Yuping Song; Gongjun Shi; Jianjun Wang; Xilin Hou (Acta Physiologiae Plantarum, 2009)

Mapping QTLs for mineral accumulation and shoot dry biomass under different Zn nutritional conditions in Chinese cabbage (Brassica rapa L. ssp. pekinensis) - Jian Wu; Yu-Xiang Yuan; Xiao-Wei Zhang; Jianjun Zhao; Xiaofei Song; Ying Li; Xiaonan Li; Rifei Sun; Maarten Koornneef; Mark G. M. Aarts; Xiao-Wu Wang (Plant and Soil, 2008)

Changes in nitrogen resorption traits of six temperate grassland species along a multi-level N addition gradient - Ju-Ying Huang; Xiao-Guang Zhu; Zhi-You Yuan; Shi-Huan Song; Xin Li; Ling-Hao Li (Plant and Soil, 2008)

Synthesis and structure characterization of new 1,2,4-oxadiazolo[4,5-d]-1,5-benzothiazepines derivatives containing 2-phenyl-1,2,3-triazole through 1,3-dipolar cycloaddition reaction - De-Bao Yang; Fang-Ming Liu; Feng Xu; Chun Yang; Jia-Wei Ye; Song-Wei Shen; Ying-Lei Zhou; Wei Li (Molecular Diversity, 2008)

Pinacidil reduces neuronal apoptosis following cerebral ischemia-reperfusion in rats through both mitochondrial and death-receptor signal pathways - Hong Zhang; Li-Chun Song; Yan-Yan Liu; Ying Ma; Yong-Li Lu (Neuroscience Bulletin, 2007)

Development of EST-SSR in foxtail millet (Setaria italica) - Xiao-Ping Jia; Yun-Su Shi; Yan-Cun Song; Guo-Ying Wang; Tian-Yu Wang; Yu Li (Genetic Resources and Crop Evolution, 2007)

BRD2 is one of BRD7-interacting proteins and its over-expression could initiate apoptosis - Ming Zhou; Xiao-Jie Xu; Hou-De Zhou; Hua-Ying Liu; Jia-Jin He; Xiao-Ling Li; Cong Peng; Wei Xiong; Song-Qing Fan; Jian-Hong Lu; Jue Ouyang; Shou-Rong Shen; et al. (Molecular and Cellular Biochemistry, 2006)

Human Homologue of Seta Binding Protein 1 Interacts with Cathepsin B and Participates in TNF-Induced Apoptosis in Ovarian Cancer Cells - Jian-Ping Liu; Nan-Song Liu; Han-Ying Yuan; Qian Guo; Hong Lu; Yu-Yang Li (Molecular and Cellular Biochemistry, 2006)

Edaravone protects PC12 cells from ischemic-like injury via attenuating the damage to mitochondria - Ying Song; Meng Li; Ji-cheng Li; Er-qing Wei (Journal of Zhejiang University-SCIENCE B, 2006)

A simple, rapid and effective method for total RNA extraction from Lentinula edodes - Jun-hui Li; Chuan-hong Tang; Chun-yan Song; Ming-jie Chen; Zhi-yong Feng; Ying-jie Pan (Biotechnology Letters, 2006)

Localization of putative stem cells and four cell populations with different differentiation degree in mouse mammary anlagen - Jianyong Han; Suying Cao; Hong Jin; Ying Liu; Meili Wang; Jiazhe Song; Ning Li (Histochemistry and Cell Biology, 2006)

A novel dual peroxisome proliferator-activated receptors α and γ agonist with beneficial effects on insulin resistance and lipid metabolism - Cheng Xu; Li-Li Wang; Hong-Ying Liu; Cheng-Mai Ruan; Xing-Bo Zhou; Ying-Lin Cao; Song Li (Biotechnology Letters, 2006)

Tissue distribution of the secretory protein, SPLUNC1, in the human fetus - Hou-De Zhou; Song-Qin Fan; Jin Zhao; Dong-Hai Huang; Ming Zhou; Hua-Ying Liu; Zhao-Yang Zeng; Yi-Xing Yang; He Huang; Xiao-Ling Li; Shou-Rong Shen; Gui-Yuan Li (Histochemistry and Cell Biology, 2006)

In vivo chondrogenesis of adult bone-marrow-derived autologous mesenchymal stem cells - Jinwu Chen; Changyong Wang; Shuanghong L; Junzheng Wu; Ximin Guo; Cuimi Duan; Lingzhi Dong; Ying Song; Junchuan Zhang; Dianying Jing; Linbo Wu; Jiandong Ding; et al. (Cell and Tissue Research, 2005)